Effects of Cholesterol and Solution pH on Daptomycin-bilayer Interactions - Samuel R. Pennock; Maggie Cortes; Megha D. Salecha; Neil X. Sevilla; Nicole R. Rementer; Kevin Rana; Luke C. Hicks; Emmaleigh Fox; Ahmed Grine; Patience S. Hammel; Timothy D. Vaden; Benjamin R. Carone; et al. (The Journal of Membrane Biology, 2026)

Selecting temperate urban trees for resistance to drought: Relevance of leaf turgor loss point - Abigail C. Tumino; Marvin Lo; Deborah Duong; Brendon C. Reidy; Jason W. Miesbauer; Andrew Hirons; Christine R. Rollinson; M. Luke McCormack (Urban Forestry & Urban Greening, 2026)

LAI assimilation schedules to constrain uncertain cultivars and soils in CERES-Maize - Luke Monhollon; Alex C. Ruane; William D. Batchelor (Computers and Electronics in Agriculture, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Hybridization and introgression as underexplored factors in cophylogeny and coevolution - Luke Sparreo; Robert F. C. Naczi (Evolutionary Ecology, 2026)

Stable isotopes reveal that gelatinous zooplankton diets group by taxonomy and feeding traits in a coastal upwelling system - Elizabeth Wallace; Luke A. Bobay; Lucas C. R. Silva; Su Sponaugle; Robert K. Cowen; Kelly R. Sutherland (Limnology and Oceanography, 2026)
Gelatinous zooplankton are abundant in marine ecosystems, yet their trophic roles and functional diversity in food webs have only recently gained attention. Gelatinous zooplankton taxa including hydromedusae, ctenophores, siphonophores, chaetognaths, and pelagic tunicates span multiple phyla and are often grouped taxonomically, but trait‐based categorizations have emerged as an ecologically meaningful alternative. Considering their wide variety of diets and feeding modes, we examined whether gelatinous zooplankton diet diversity can be described by feeding mode or phylum categorizations. We analyzed the carbon and nitrogen stable isotope composition (δ 13 C and δ 15 N values) of 490 gelatinous zooplankton samples of 32 genera/species collected across seasons and shelf positions in the northern California Current ecosystem. The δ 13 C and δ 15 N values fell into distinct groups when taxa were categorized three ways—by phylum, feeding mode, and feeding anatomy—indicating that both taxonomic and trait‐based approaches are useful for describing the trophic diversity of gelatinous zooplankton. Even when gelatinous specimens cannot be identified taxonomically, their diets likely resemble those of taxa sharing the same feeding mode or anatomy. These insights refine our knowledge of marine food webs and facilitate the incorporation of these ubiquitous members of the food web into ecosystem models.

The Effects of Peracetic Acid on Post‐Larvae and Juvenile Pacific White Shrimp ( Litopenaeus vannamei ) and Seven Vibrio Species Isolates at Two Salinities - James T. Tuttle; Timothy J. Bruce; Luke A. Roy; Hisham A. Abdelrahman; Julio C. García; Benjamin H. Beck; David L. Straus; Anita M. Kelly (Journal of Fish Diseases, 2026)
Pacific white shrimp ( Litopenaeus vannamei ) are among the most important aquaculture species but are highly susceptible to Vibrio infections. Novel disease management strategies are necessary. Previous studies have reported that peracetic acid (PAA) is an effective disinfectant, but its application in shrimp aquaculture remains underexplored. This study aimed to determine the median lethal concentration (LC 50 ) of PAA at two life stages of L. vannamei under two salinities and assess its in vitro growth‐inhibitory effects against Vibrio spp. Two groups of 180 juveniles (~5 g) and post‐larvae (maintained at either 4 or 30 g L −1 ) were exposed to six geometrically increasing concentrations of PAA to determine 24‐h LC 50 estimates. Representative juvenile shrimp tissues were histologically assessed. Seven isolates of Vibrio spp. inocula were exposed to PAA and enumerated to determine growth inhibition. The LC 50 estimates varied from 29.09 to 82.40 mg L −1 of PAA. Gill and hepatopancreas tissues were notably damaged at 40.5 and 75 mg L −1 of PAA at 4 and 30 g L −1 , respectively. Growth of all Vibrio spp. was inhibited at the lowest PAA dose tested, that being 0.03125 mg L −1 after 45 min. These findings will help progress the further application of peracetic acid in shrimp aquaculture.

The phasmid Carausius morosus efficiently digests stachyose, oleuropein, pectin and hemicelluloses, but only weakly digests native leaf cellulose - Luke Yuan; E. Alanie Lapina; Lenka Franková; Stephen C. Fry (Insect Biochemistry and Molecular Biology, 2026)

The ghost of glaberrima: descriptions of two new Leiopathes species - Jeremy Horowitz; Dennis M. Opresko; Declan Morrissey; Victoria Polit; Heather C. Shull; Teresa Cerqueira; Luke J. McCartin; Samuel A. Vohsen; Marina Carreiro-Silva; Andrea M. Quattrini (Coral Reefs, 2026)
Two new species of black coral are described herein: Leiopathes dumosa nov. sp. and Leiopathes brugleri nov. sp. Samples were collected between depths of 244 and 617 m on the North American continental slope between Texas and Florida, USA, and recognized in the family Leiopathidae Haeckel, 1896. L. dumosa nov. sp. is characterized by short stems and short branches forming bush-like colonies (usually less than 1 m tall and 0.25 m wide), with branchlets 1.5–2 cm in length, polyps 1–1.6 mm in transverse diameter, and spines 0.02–0.04 mm tall. L. brugleri nov. sp. is characterized by short stems and long branches forming tree-like colonies (can exceed 2 m in width and height), with branchlets 8–10 cm in length, polyps 2 mm in transverse diameter, and spines 0.03–0.06 mm tall. Additionally, we revise the description of Leiopathes glaberrima (Esper 1792) to facilitate morphological comparison with the new species described herein and to support future studies on Leiopathidae. Historically, Leiopathes from this region were misidentified as L. glaberrima (Esper 1792). Our findings reveal that the North American continental slope between Texas and Florida harbors at least two distinct species of Leiopathes and we have yet to collect L. glaberrima in the region. Following the Deepwater Horizon oil spill in 2010, Leiopathes was designated as a priority taxon for regional conservation and management by the National Oceanic and Atmospheric Administration, prompting restoration efforts and population studies. The discovery of multiple species distinct from L. glaberrima has major implications for the success of ongoing and future conservation and restoration strategies. ZooBank registration: urn:lsid:zoobank.org:pub:E3ECAAD7-B68E-4E53-BE99-7C138F44CA43.

Estimating the value of ecosystem services: A machine learning approach for Missouri wetlands - Luke Maddock; Frank Nelson; Levi Altringer; Sophie C. McKee (Ecosystem Services, 2026)

Emulation of peak storm surge across extended spatial domains using separable Gaussian process techniques - Christopher Irwin; WoongHee Jung; Alexandros A. Taflanidis; Norberto C. Nadal-Caraballo; Luke A. Aucoin; Madison C. Yawn (Coastal Engineering, 2026)

Raising practitioner awareness to improve conservation of Data Deficient species: Evidence from before-and-after interviews - Luke R. Bonifacio; Jules E. Farquhar; David G. Chapple; Jessica C. Walsh (Biological Conservation, 2026)

Depth is a strong driver of functional diversity in Caribbean reef-fish communities - Juliette Jacquemont; Simon J. Brandl; Carole C. Baldwin; Luke Tornabene (Oecologia, 2026)
Functional diversity patterns have been thoroughly described for reef fishes across geographic gradients, but the effect of depth on these patterns remains largely unknown. Using diet, life-history, and behavioral traits, we evaluated the functional diversity of Caribbean reef-fishes from the surface to 450 m depth to test if taxonomically distinct communities along the reef slope are characterized by similar or distinct ecological traits. Core ecological traits found in shallow reef-fish communities were conserved in the upper section of deep reefs (i.e., mesophotic zone) across three taxonomically distinct assemblages. By contrast, the deepest reef communities (i.e., rariphotic zone) displayed a distinct functional structure, mainly driven by trait loss. Functional redundancy was highest in the deepest reef communities and was generated by intrageneric diversification and functional convergence across phylogenetic lineages. The decrease in functional richness and divergence combined with an increase in functional redundancy suggest that environmental filtering is the dominant evolutionary constraint shaping the functional diversity of deep-reef fishes.

Small skeletal fossils associated with Archaeocyath reefs from the Xiannüdong Formation (Cambrian Series 2), southern Shaanxi, China - Baopeng Song; Fan Liu; Jiayue Wang; Mei Luo; Yue Liang; Yazhou Hu; Jingliang Zhao; Lars E. Holmer; Luke C. Strotz; Zhifei Zhang (Palaeobiodiversity and Palaeoenvironments, 2026)
Improved understanding of both the Small Skeletal Fossil (SSF) assemblages and archaeocyath reefs of the early Cambrian Period is important to best elucidate the evolution of early marine ecosystems during the Cambrian Radiation. To address this issue, we investigate the well-preserved SSF fauna associated with archaeocyaths of the early Cambrian Xiannüdong Formation (Dayingcun Section, Nanzheng area, southern Shaanxi). The Xiannüdong fossil assemblage includes sphenothallids, archaeocyaths, brachiopods, bradoriids, hyoliths, helcionelloid molluscs, trilobite sclerites, lobopods, tommotiids, chancelloriids, as well as echinoderm plates. Thin-section analysis, field observations and examination of fossil material indicate the Xiannüdong Formation assemblage consists primarily of an archaeocyath- Sphenothallus dominated ecosystem from a well-structured shallow-water mixed shelf featuring oolite shoals, archaeocyath reefs, adjacent fossiliferous allochthonous floatstone and bioclastic grain-packstone. The fossil assemblage reflects a benthic community which has not been previously described from other Cambrian reef strata of the Yangtze Platform. This unique community indicates that complex reef ecosystems were already present in the early Cambrian in this palaeogeographic region.

A randomised, double-blind, placebo-controlled trial examining the dose-dependent effects of acute alcohol intoxication on neurocognitive performance - Blair Aitken; Brook Shiferaw; Luke A. Downey; Brooke Manning; Thomas Arkell; Michael G. Lenné; Jonny Kuo; Amie C. Hayley (Psychopharmacology, 2026)
Rationale Acute alcohol intoxication impairs cognitive and motor control, elevating risk in safety–critical contexts. While blood alcohol concentration (BAC) quantifies exposure, it does not reflect real-time functional impairment. Mobile, performance-based assessments may offer scalable detection tools, but their sensitivity under controlled alcohol challenge requires further validation. Objectives To evaluate the sensitivity of a mobile cognitive assessment (DRUID®) to alcohol-induced impairment across low and moderate intoxication levels and examined objective cognitive performance and subjective intoxication within a unified framework. Methods In a randomised, double-blind, placebo-controlled, within-subjects trial, 30 healthy adults (33% female; aged 23–49 years) completed neurocognitive testing following placebo, low-dose alcohol (mean peak BAC 0.04%), and moderate-dose alcohol (mean peak BAC 0.07%). Cognitive performance was measured using the Cambridge Neuropsychological Test Automated Battery (CANTAB) and DRUID®, while subjective effects were assessed via the Brief Biphasic Alcohol Effects Scale and a single-item intoxication rating. Results Moderate alcohol intoxication significantly impaired spatial working memory, sustained attention, and psychomotor control (all p < 0.05), and elevated DRUID® impairment scores at 130 min post-dose relative to placebo ( p < 0.001). Low-dose alcohol increased subjective intoxication and sedation (both p < 0.001) without measurable cognitive impairment. Conclusions Moderate alcohol produced persistent neurocognitive deficits despite dissociation between subjective and objective measures. Findings support performance-based impairment models and highlight mobile cognitive tools such as DRUID® as practical candidates for real-time functional assessment in applied safety settings. Trial registration ACTRN12623000528651, 19/05/2023.

Lead (Pb) exposure results in cell type specific changes in the mouse retina and optic nerve - Labony Khandokar; Luke L. Liu; Wei Zheng; Patrick C. Kerstein (NeuroToxicology, 2026)

Weak Bonded Interface and Shear Block Design for Validating Fracture Caging’s Effect in Induced Seismic Mitigation - Meng Meng; Yerkezhan Madenova; Luke P. Frash; K. C. Bijay; Weicheng Zhang; Wenfeng Li (Rock Mechanics and Rock Engineering, 2026)

Particulate nitrate over the Northwest Atlantic: Insights gained by comparing airborne AMS and PILS measurements - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Eva-Lou Edwards; Johnathan W. Hair; Christopher A. Hostetler; Simon Kirschler; John B. Nowak; Michael Shook; et al. (Atmospheric Environment, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Precision of age assignment from four structures of smallmouth buffalo [Ictiobus bubalus, (Rafinesque, 1818)] in the Southeastern United States - Jason C. Doll; Autumn Morin; Jason Marsik; Gatlin Edge; Gavin McAbee; Luke Etchison (Environmental Biology of Fishes, 2026)
Accurate and precise age determination is essential for estimating key life-history parameters in fishes. Recent studies suggest that some fisheries management metrics, such as mortality, may be robust to biased age estimates. Thus, it can be more important to identify the most precise structure for age assignment. However, precision can vary geographically, highlighting the need for location-specific evaluations. Smallmouth buffalo [ Ictiobus bubalus , (Rafinesque, 1818)] have received little attention in this regard, particularly outside their native range. We compared the precision of four structures, scales, opercles, otoliths, and anal fin rays, for assigning ages to smallmouth buffalo from a large river in the Southeastern United States. Anal fin rays showed the highest between-reader agreement, with the lowest coefficient of variation (CV) and average percent error (APE), followed by otoliths, opercles, and scales. Ages assigned from scales, opercles, and anal rays were generally consistent with otolith ages up to age 12. Variability in age assignments had little effect on von Bertalanffy growth parameters or mortality estimates between otoliths and anal rays, and these models were generally consistent across readers. Overall, our results indicate that anal fin rays provided the most precise age estimates for smallmouth buffalo in this system. Although bias was not assessed, the close agreement between anal fin ray and otolith ages suggests that anal fin rays are a reliable, non-lethal option for aging individuals less than 12 years old.

Proceedings of the 2024 FDA-CRCG Workshop: Scientific and Regulatory Considerations for Assessment of Immunogenicity Risk for Generic Peptide and Oligonucleotide Drug Products - Jennifer K. Lee; Ha-Na Lee; Sudhir Agrawal; Joseph A. Balsamo; Andrew Clerman; Sofie Denies; Anne De Groot; Jeremy Fry; Nicolas Gaudenzio; Andrew J. Graves; Kristina E. Howard; SuJin Hwang; et al. (The AAPS Journal, 2026)

Virtual deliberation on genetics research: report-out of key themes from Diné (Navajo) research & healthcare professionals - Carissa A. Sherman; Luke C. Nez; Kaja M. Aagaard; Dalaki J. Livingston; Erika Blacksher; Justin Reedy; Vanessa Y. Hiratsuka; Walter Phelps; Jessica W. Blanchard; Justin R. Lund; Julie A. Beans; F. Leah Nez; et al. (Journal of Community Genetics, 2026)

Development and pilot testing of AYA-RISE, a risk information and screening education intervention for adolescents and young adults with cancer risk syndromes - Junne Kamihara; Lauren Fisher; Jaclyn Schienda; Rebecca Vanderwall; Moran Snir; Guy Snir; Emilie Simmons; Andrew Khalaj; Evan Goler; Kayla V. Hamilton; Christopher C. Porter; Bojana Pencheva; et al. (Familial Cancer, 2026)

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

A multi-tiered Bayesian network coastal compound flood analysis framework - Ziyue Liu; Meredith L. Carr; Norberto C. Nadal-Caraballo; Luke A. Aucoin; Madison C. Yawn; Michelle T. Bensi (Coastal Engineering, 2026)

Subsaturated aerosol hygroscopicity over the northwest Atlantic: Impacts of seasonal factors, offshore location, and clouds - Genevieve Rose Lorenzo; Luke D. Ziemba; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Richard A. Ferrare; Simon Kirschler; John B. Nowak; Michael A. Shook; Kenneth L. Thornhill; Christiane Voigt; et al. (Atmospheric Environment, 2026)

Aboveground living plant-based methane production does not dominate methane emissions in terrestrial ecosystems - Zhi-Ping Wang; Luke C. Jeffrey; Josep Barba; Katerina Machacova; Xi-Mei Zhang; Ang Li; Shi-Jie Han (Planta, 2026)

The potential for unwanted genetic rescue in invasive fallow deer populations - Lauren C. White; Erin Hill; Eliane D. McCarthy; Andrew J. Bengsen; Sebastien Comte; Sandie Czarka; David M. Forsyth; Catherine E. Grueber; Jake Haddad; Jordan O. Hampton; Michelle Hanslow; Scott Jennings; et al. (Biological Invasions, 2026)

Estimating PM2.5 in Fort Collins, Colorado using a robust drive-by correction of low-cost air quality monitors deployed on school buses - Priyanka deSouza; Jessa Ellenburg; Andrew Turnipseed; Craig Williford; Helena Pliszka; Story Schwantes; Timothy Dye; Luke Greenidge; Austin Bailly; Thomas Kopala; Evan Vaughan; Michael Samon; et al. (Science of The Total Environment, 2025)

Species delimitation in the Eviota sigillata species complex, a widely distributed group of cryptobenthic coral reef fishes - Marta C. Gómez-Buckley; Carmen del R Pedraza-Marrón; Mark V. Erdmann; Luke M. Tornabene (Molecular Phylogenetics and Evolution, 2025)

Multispecies approach shows high tolerance of temperate marine sponges to nitrogenous fertiliser - Gabriela Wood; Rob McAllen; Lisa Woods; Alan C. Wood; Luke Harman; James J. Bell (Journal of Experimental Marine Biology and Ecology, 2025)

Two-phased ITCZ-driven upper salinity stratification in the western equatorial Atlantic during Heinrich Stadial 11 - Marília C. Campos; Rodrigo A. Nascimento; Tainã M.L. Pinho; Laura Kraft; Stefano Crivellari; Svetlana Radionovskaya; Luke Skinner; Bruna B. Dias; Rodrigo C. Portilho-Ramos; Gelvam A. Hartmann; Paul A. Baker; Cleverson G. Silva; et al. (Global and Planetary Change, 2025)

Health benefits of traffic emissions controls in melbourne, Australia - Timothy B. Chaston; Steven Utembe; Jason Choi; Karthik Gopi; Cassandra Yuen; Luke Knibbs; Ivan C. Hanigan; Richard Broome; Sotiris Vardoulakis; Suzanne Mavoa; Geoffrey Morgan (Environmental Research, 2025)

Spatial variation in toll-like receptor diversity in koala populations across their geographic distribution - Jian Cui; Kimberley C. Batley; Luke W. Silver; Elspeth A. McLennan; Carolyn J. Hogg; Katherine Belov (Immunogenetics, 2025)
The koala ( Phascolarctos cinereus ) is an iconic Australian species that is listed as endangered in the northern parts of its range due to loss of habitat, disease, and road deaths. Diseases contribute significantly to the decline of koala populations, primarily Chlamydia and koala retrovirus. The distribution of these diseases across the species’ range, however, is not even. Toll-like receptors (TLRs) play a crucial role in innate immunity by recognising and responding to various pathogens. Variations in TLR genes can influence an individual’s susceptibility or resistance to infectious diseases. The aim of this study was to identify koala TLR diversity across the east coast of Australia using 413 re-sequenced genomes at 30 × coverage. We identified 45 single-nucleotide polymorphisms (SNP) leading to 51 alleles within ten TLR genes. Our results show that the diversity of TLR genes in the koala forms four distinct genetic groups, which are consistent with the diversity of the koala major histocompatibility complex (MHC), another key immune gene family. The bioinformatics approach presented here has broad applicability to other threatened species with existing genomic resources.

Boost or Bust? The Impact of Supplementation on Functional Genetic Diversity and Selective Processes in Tasmanian Devils - Andrea L. Schraven; Katherine A. Farquharson; Kimberley C. Batley; Samantha Fox; Andrew V. Lee; Katherine Belov; Luke W. Silver; Carolyn J. Hogg (Molecular Ecology, 2025)
Translocating individuals into existing populations of conspecifics can support threatened species by increasing population size, maintaining genetic diversity and reducing the risk of inbreeding. However, for species whose adaptive potential is compromised due to ongoing threats, like disease, the outcome of such management interventions becomes more complex. The Tasmanian devil ( Sarcophilus harrisii ) is a prime example, where the emergence of Devil Facial Tumour Disease (DFTD) has led to significant population declines, raising concerns about their long‐term survival. It is therefore critical to understand if the introduction of new functional genetic variants through supplementation actions enhances, or potentially hinders, their long‐term persistence. We investigated changes in functional gene diversity at both the population‐ and individual‐levels, pre‐ and post‐supplementation, across multiple wild devil sites (four supplemented and four not supplemented). We found that functional diversity increased post‐supplementation. Though the magnitude of change was varied among sites, a similar site‐specific pattern was also evident in genome‐wide diversity. Importantly, we saw no evidence of swamping of local alleles or those putatively associated with DFTD regressions. This is likely due to the source population representing the broad wild genetic diversity and supplementations facilitating gene flow across the current fragmented landscape. Continued and long‐term monitoring at multiple wild sites will be necessary to determine whether future generations retain this introduced genetic variation.

Assessing recovery and conservation of Australian freshwater fishes with the IUCN Green Status of Species and structured expert elicitation - Maiko L. Lutz; David G. Chapple; Molly K. Grace; Luciano B. Beheregaray; Chris J. Brauer; Iain Ellis; Adam Kerezsy; John D. Koehn; Mark Lintermans; Jarod P. Lyon; Matthew McLellan; Luke Pearce; et al. (Conservation Biology, 2025)
The International Union for Conservation of Nature (IUCN) Green Status of Species (GSS), introduced in 2021, is a global standard of measurement used to assess the level to which a species has recovered (i.e., is viable and providing its ecological function across its entire range). It is also used to evaluate how a species has responded to past conservation actions and the expected conservation gains and recovery potential it would receive in the short‐ and long‐term future. Preliminary application of the GSS method has relied on expert knowledge from individuals or small groups of specialists. However, more accurate and reliable results are likely to be produced by formally eliciting individual judgments from a diverse range of experts, followed by discussion, reevaluation, and synthesis of these judgments. We developed a method in which 2 structured expert elicitation workshops are used to conduct GSS assessments and applied this method to 8 Australian freshwater fish species from the Murray–Darling Basin. We integrated the investigate, discuss, evaluate, aggregate protocol into the GSS methods; experts assessed the species’ IUCN Green Score (percent recovery) in the current state and for 5 other scenarios in the past and future with and without conservation. Four GSS conservation impact metrics were calculated based on the averages of expert judgments. Experts forecasted that impact in the short‐term would be minimal (i.e., conservation gain metric = zero or low) for 5 of the 8 species because targeted and maintained conservation actions are often lacking. In contrast, experts indicated long‐term recovery potential would be considerably higher if implementation of appropriate recovery activities could be sustained (all 8 species had medium or high recovery potential). We concluded that the GSS is well suited to a modified workshop approach because it aims to reduce biases associated with expert judgments and encourages valuable knowledge sharing among experts.

Corrigendum to “Links between high fecal indicator bacteria levels and rain, winds, and tides at Connecticut beaches” [Ocean Coast. Manag. 266 (2025) 107664] - Luke C. Glass; Michael M. Whitney; Peter Linderoth (Ocean & Coastal Management, 2025)

Modeling cell differentiation in neuroblastoma: Insights into development, malignancy, and treatment relapse - Simon F. Martina-Perez; Luke A. Heirene; Jennifer C. Kasemeier; Paul M. Kulesa; Ruth E. Baker (Journal of Theoretical Biology, 2025)

“Magnetic carbon fibre” for multifunctional composites with improved recyclability - Bhagya Dharmasiri; Andrew D.M. Charles; Ashleigh L. Farnsworth; Marcus J. Giansiracusa; Colette Boskovic; Elmer Austria; Behnam Akhavan; Jaineel K. Shah; Ken Aldren S. Usman; Joselito M. Razal; Luke C. Henderson (Chemical Engineering Journal, 2025)

Expanding tropism: Avian B cells as novel cellular target of infectious bronchitis virus - Sufna M. Suhail; Motamed E. Mahmoud; Ishara M. Isham; Ahmed Ali; Muhammad Farooq; Anne Shehara Perera; Lahiru W. Waduge; Luke Xiu; Susan C. Cork; Ashish Gupta; Mohamed Faizal Abdul-Careem (Veterinary Immunology and Immunopathology, 2025)

Proton spin network fingerprints for dereplication, pharmacophore identification and standardization of the botanical supplement Centella asiatica - Harianantenaina L. Rakotondraibe; Sara Neiheisel; Caroline Wittman; Luke C. Marney; Jaewoo Choi; Liping Yang; Nora Gray; Jan F. Stevens; Claudia S. Maier; Amala Soumayanath (Phytochemistry Letters, 2025)

Assessing virgin and reclaimed carbon fibre electrodes in structural batteries - James D. Randall; Aqeel Muhammad; Emma G. Hogan; Timothy Harte; Žan Simon; Bhagya Dhamarsiri; Leif E. Asp; Luke C. Henderson (Chemical Engineering Journal, 2025)

Adaptive covariance tapering for large datasets and application to spatial interpolation of storm surge - Christopher Irwin; Alexandros A. Taflanidis; Norberto C. Nadal-Caraballo; Luke A. Aucoin; Madison C. Yawn (Coastal Engineering, 2025)

Advances in spatiotemporal storm surge emulation: database imputation and multi-mode latent space projection - WoongHee Jung; Alexandros A. Taflanidis; Norberto C. Nadal-Caraballo; Luke A. Aucoin; Madison C. Yawn (Coastal Engineering, 2025)

Enhancing the flowability of woody biomass slurries in wet biorefineries - Sampath Gunukula; Glenn Matamoros; Ehsan Ullah Sardar; M. Clayton Wheeler; C. Luke Williams (Biomass and Bioenergy, 2025)

Fossilisation of Fish Soft Tissue in Oxidative Microniches of Anoxic Sediments - Amy L. Elson; Lorenz Schwark; Paul F. Greenwood; Madison Tripp; Alex I. Holman; Michael E. Böttcher; Peter Hopper; Robert H. C. Madden; Luke M. Brosnan; Jessica H. Whiteside; Stephen F. Poropat; Lance Grande; et al. (Environmental Microbiology, 2025)
Organic analyses of past organisms enhance our understanding of Earth's evolutionary history, complementing the macrofossil record. Biomolecular remains are typically vulnerable to diagenetic mineralisation, but can persist in exceptional depositional settings such as Lagerstätten. Their preservation is usually linked to anoxic conditions that exclude aerobic degraders. However, we report intact skin tissue of the fossil fish Diplomystus dentatus from the Fossil Basin Lagerstätte (USA), preserved through phosphate permineralisation in an oxygen‐enriched microenvironment. Notably, only the skin with scales retained tissue integrity, and this organic material was closely associated with fluorapatite absent from the surrounding matrix. Geochemical analyses revealed higher oxidation states in the skin than in vertebrae and bones, likely due to early degradation of the fatty acid‐rich dermis. Redox‐sensitive biomarkers and isotopic data (δ 15 N) indicated a less reducing environment in the skin region compared to bones and the eye, yet more reducing than the surrounding sediment. This localised oxygen enrichment fostered sulphide‐oxidising bacteria, evidenced by mineral sulphates (barite) found only in the skin. Phosphatisation was likely driven by dermal breakdown and the release of H+, reducing alkalinity and enabling phosphate mineralisation over the carbonate system.

The Mechanisms Through Which Fire Drives Population Change in Terrestrial Biota - Ella Plumanns‐Pouton; Julianna L. Santos; Cristina Aponte; Lluís Brotons; Luke T. Kelly; Stephen C. Mason; Kirsten Parris; Lauren Ponisio; David A. Keith (Global Change Biology, 2025)
Global fire regime change is threatening terrestrial biodiversity. Understanding how these changes affect biota is essential to protect biodiversity now and into the future. A targeted examination of the mechanisms through which fire influences populations will help achieve this by enabling comparisons and connections across taxa. Here, we develop a cross‐taxa framework that identifies mechanisms through which fire regimes influence terrestrial species populations over different time scales, and traits on which those mechanisms depend. We focus on amphibians, birds, fungi, insects, mammals, plants, and reptiles. First, we identify key mechanisms through which fire regimes influence species populations across different taxonomic groups. Second, we link these mechanisms to functional traits that influence the relevance to different species. Third, we identify traits that shape the vulnerability—or conversely, resilience—of species populations to frequent, high‐intensity, and large wildfires that are emerging as a threat in many parts of the world. Finally, we highlight how this integrative framework can be useful for understanding and identifying fire‐related threats common to different taxa across the globe and for guiding future research on fire‐related population change.

Advances in Imputation Strategies Supporting Peak Storm Surge Surrogate Modeling - WoongHee Jung; Christopher Irwin; Alexandros A. Taflanidis; Norberto C. Nadal-Caraballo; Luke A. Aucoin; Madison C. Yawn (Journal of Marine Science and Engineering, 2025)
Surrogate models are widely recognized as effective, data-driven predictive tools for storm surge risk assessment. For such applications, surrogate models (referenced also as emulators or metamodels) are typically developed using existing databases of synthetic storm simulations, and once calibrated can provide fast-to-compute approximations of the storm surge for a variety of downstream analyses. The storm surge predictions need to be established for different geographic locations of interest, typically corresponding to the computational nodes of the original numerical model. A number of inland nodes will remain dry for some of the database storm scenarios, requiring an imputation for them to estimate the so-called pseudo-surge in support of the surrogate model development. Past work has examined the adoption of kNN (k-nearest neighbor) spatial interpolation for this imputation. The enhancement of kNN with hydraulic connectivity information, using the grid or mesh of the original numerical model, was also previously considered. In this enhancement, neighboring nodes are considered connected only if they are connected within the grid. This work revisits the imputation of peak storm surge within a surrogate modeling context and examines three distinct advancements. First, a response-based correlation concept is considered for the hydraulic connectivity, replacing the previous notion of connectivity using the numerical model grid. Second, a Gaussian Process interpolation (GPI) is examined as alternative spatial imputation strategy, integrating a recently established adaptive covariance tapering scheme for accommodating an efficient implementation for large datasets (large number of nodes). Third, a data completion approach is examined for imputation, treating dry instances as missing data and establishing imputation using probabilistic principal component analysis (PPCA). The combination of spatial imputation with PPCA is also examined. In this instance, spatial imputation is first deployed, followed by PPCA for the nodes that were misclassified in the first stage. Misclassification corresponds to the instances for which imputation provides surge estimates higher than ground elevation, creating the illusion that the node is inundated even though the original predictions correspond to the node being dry. In the illustrative case study, different imputation variants established based on the aforementioned advancements are compared, with comparison metrics corresponding to the predictive accuracy of the surrogate models developed using the imputed databases. Results show that incorporating hydraulic connectivity based on response similarity into kNN enhances the predictive performance, that GPI provides a competitive (to kNN) spatial interpolation approach, and that the combination of data completion and spatial interpolation emerges as the recommended approach.

Freshwater fish condition responses to hydrological disturbance are species‐ and scale dependent - Maxwell C. Mallett; Jason D. Thiem; Gavin L. Butler; Luke Carpenter‐Bundhoo; Mark J. Kennard (Journal of Fish Biology, 2025)
Modification of river flows is a major cause of freshwater fish population declines in many parts of the world. Identifying the precise mechanisms of these declines represents a significant challenge, as a range of stressors can simultaneously impact various components of fish health, fitness and population dynamics. Here we investigate the role of river flows and other biophysical factors on spatio‐temporal variation in freshwater fish body condition in Australia's highly modified Murray‐Darling Basin using three widely distributed native (Murray cod Maccullochella peelii , golden perch Macquaria ambigua and bony herring Nematalosa erebi ) and one introduced (common carp Cyprinus carpio ) species. Our aim was to uncover drivers of spatio‐temporal variation in fish condition at two spatial extents: at the basin scale, utilising a flow regime disturbance index, and at the river‐valley scale, employing individual flow gauge data to assess responses in fish condition to multiple measures of antecedent (365 day) flow. Linear mixed effects modelling revealed that at the basin scale, M. peelii and M. ambigua were in better condition in rivers with lower flow regime disturbance, and temporal trends in the condition of N. erebi , C. carpio and M. peelii reflected boom and bust dynamics related to wet and dry climate periods. At the river‐valley scale, mean antecedent daily flow magnitude was significantly positively related to the condition of M. peelii , M. ambigua and C. carpio , whereas the number of high‐flow days was negatively related to condition of N. erebi . Our study demonstrates that a simple body condition index calculated from routinely collected length–weight data is sensitive to multiple measures of hydrological disturbance in river systems that experience substantial temporal and spatial variability. We emphasise that studies considering multiple spatial scales are important for understanding complex scale‐dependent mechanisms influencing fish condition.

Combining Observations and Models: A Review of the CARDAMOM Framework for Data‐Constrained Terrestrial Ecosystem Modeling - Matthew A. Worden; T. Eren Bilir; A. Anthony Bloom; Jianing Fang; Lily P. Klinek; Alexandra G. Konings; Paul A. Levine; David T. Milodowski; Gregory R. Quetin; T. Luke Smallman; Yinon M. Bar‐On; Renato K. Braghiere; et al. (Global Change Biology, 2025)
The rapid increase in the volume and variety of terrestrial biosphere observations (i.e., remote sensing data and in situ measurements) offers a unique opportunity to derive ecological insights, refine process‐based models, and improve forecasting for decision support. However, despite their potential, ecological observations have primarily been used to benchmark process‐based models, as many past and current models lack the capability to directly integrate observations and their associated uncertainties for parameterization. In contrast, data assimilation frameworks such as the CARbon DAta MOdel fraMework (CARDAMOM) and its suite of process‐based models, known as the Data Assimilation Linked Ecosystem Carbon Model (DALEC), are specifically designed for model‐data fusion. This review, motivated by a recent CARDAMOM community workshop, examines the development and applications of CARDAMOM, with an emphasis on its role in advancing ecosystem process understanding. CARDAMOM employs a Bayesian approach, using a Markov Chain Monte Carlo algorithm to enable data‐driven calibration of DALEC parameters and initial states (i.e., carbon pool sizes) through observation operators. CARDAMOM's unique ability to retrieve localized model process parameters from diverse datasets—ranging from in situ measurements to global satellite observations—makes it a highly flexible tool for analyzing spatially variable ecosystem responses to environmental change. However, assimilating these data also presents challenges, including data quality issues that propagate into model skill, as well as trade‐offs between model complexity, parameter equifinality, and predictive performance. We discuss potential solutions to these challenges, such as reducing parameter equifinality by incorporating new observations. This review also offers community recommendations for incorporating emerging datasets, integrating machine learning techniques, strengthening collaboration with remote sensing, field, and modeling communities, and expanding CARDAMOM's relevance for localized ecosystem monitoring and decision‐making. CARDAMOM enables a deep, mechanistic understanding of terrestrial ecosystem dynamics that cannot be achieved through empirical analyses of observational datasets or weakly constrained models alone.

Changes in community composition and functional diversity of European bats under climate change - Penelope C. Fialas; Luca Santini; Danilo Russo; Francisco Amorim; Hugo Rebelo; Roberto Novella‐Fernandez; Francisco Marques; Adi Domer; Adriana Vella; Adriano Martinoli; Aleksandra Figurek; Asaf Tsoar; et al. (Conservation Biology, 2025)
Climate change is predicted to drive geographical range shifts that will result in changes in species diversity and functional composition and have potential repercussions for ecosystem functioning. However, the effect of these changes on species composition and functional diversity (FD) remains unclear, especially for mammals, specifically bats. We used species distribution models and a comprehensive ecological and morphometrical trait database to estimate how projected future climate and land‐use changes could influence the distribution, composition, and FD of the European bat community. Future bat assemblages were predicted to undergo substantial shifts in geographic range and trait structure. Range suitability decreased substantially in southern Europe and increased in northern latitudes. Our findings highlight the potential for climate change to drive shifts in bat FD, which has implications for ecosystem function and resilience at a continental scale. It is important to incorporate FD in conservation strategies. These efforts should target species with key functional traits predicted to be lost and areas expected to experience losses in FD. Conservation strategies should include habitat and roost protection, enhancing landscape connectivity, and international monitoring to preserve bat populations and their ecosystem services.

The prospective associations between parental feeding practices and fruit & vegetable consumption in young children aged 1–6 years: A systematic review - Luke Pullar; Megan Jarman; Alison C. Spence; Hannah Povall; Alissa J. Burnett; Jacqueline Blissett (Appetite, 2025)

Links between high fecal indicator bacteria levels and rain, wind, and tides at Connecticut beaches - Luke C. Glass; Michael M. Whitney; Peter Linderoth (Ocean & Coastal Management, 2025)

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Insect-parasitic fungi as a model system to investigate coinfections - Eduardo C. Costantin; José A. Roxinol; Pablo F. Braga; Simon Luke Elliot (Journal of Invertebrate Pathology, 2025)

Temporal and Spatial Changes in Water Quality and Phytoplankton Populations in the Lower St. Johns River, Florida - Gretchen K. Bielmyer-Fraser; Julia M. Courville; Kaitlyn Bowers; Samantha O’Keefe; Sarah Paulsen; Luke Stoeber; Megan Wise; Adam C. Ryan; James A. Nienow (Archives of Environmental Contamination and Toxicology, 2025)

Repeated toluene inhalation in male and female adolescent rats induces persistent drug preference and impairs cognitive and social behavior - Joannes Luke B. Asis; Ajina C. Carampel; Jariel Naomi B. Bacar; Johanna C. Munar; Cynthia Grace C. Gregorio; Paul Mark B. Medina; Leslie Michelle M. Dalmacio; Jesus Emmanuel A. D. Sevilleja; Gregory J. Quirk; Rohani Cena-Navarro (Psychopharmacology, 2025)

Forest citizens and people‐centered conservation in the Brazilian Amazon - Luke Parry; Thiago F. Morello; James A. Fraser; Natalia Guerrero; Gabriela S. Lotta; Rodrigo C. Martins; Peter Newton; Jessica C. Pires Cardoso; Andreza A. Souza Santos; Mauricio Torres (Conservation Biology, 2025)
Demands for territorial recognition are foundational to the claiming of rights by forest‐proximate people who attempt to conserve their forests. The rights of these often‐marginalized populations have been largely overlooked by conservationists, yet they are central to achieving people‐centered conservation. We further developed the concept of forest citizenship as a normative framework and analytical tool based on Brazilian social environmentalism ( socioambientalismo ), florestania (a former political project in Acre state), Latin American scholarship on ecological citizenship, and Eurocentric political philosophy. Decades of struggle for territorial recognition and social inclusion have solidified the right to have rights for Amazonia's forest citizens. Hence, forest citizens are people who have become so through the sociopolitical dynamics of their rights claims. Forest citizenship is built on community mobilization to create legally recognized territories with participatory governance but becomes tangible only if individuals and communities can successfully claim other rights from institutions through everyday practices of citizenship. We also assessed the current number and distribution of forest citizens across Brazilian Amazonia based on gridded population data and spatial analyses to calculate the resident population in four territorial categories that meet these democratic preconditions: Indigenous lands, extractive reserves, sustainable development reserves, ecological settlement projects, and Afro‐descendent Quilombola territories. The territories covered 31% of the Legal Amazon, were home to 1.05 million forest citizens, and had diverse primary policy objectives but shared goals of empowering communities and conserving forests. To be emancipatory, forest citizenship must be bottom‐up, socially inclusive, and improve people's lives. We suggest that conservationists pay greater attention to power relations and decision‐making structures related to forest territories. Territory‐based forest citizenship may be relevant for other countries where environmentalism has intersected with struggles for land rights and democracy.

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Evaluation of the Anti-Inflammatory Effects of Novel Fatty Acid-Binding Protein 4 Inhibitors in Microglia - Yi Ling Low; Ethan Kreutzer; Indu R. Chandrashekaran; Luke A. Adams; Jason Pun; Bradley C. Doak; Yijun Pan; Jennifer L. Short; Martin J. Scanlon; Joseph A. Nicolazzo (Journal of Neuroimmune Pharmacology, 2025)
Fatty acid-binding protein 4 (FABP4) is a key lipid binding protein expressed in microglia, which has been demonstrated to play a critical role in microglial-mediated neuroinflammation, a component of many neurodegenerative diseases. Compounds able to inhibit the function of FABP4 have shown promise in reducing microglial-mediated neuroinflammation, however, their physicochemical properties would prevent their ability to be easily formulated and traverse the blood–brain barrier (BBB) in order to access microglial FABP4. To this end, this study assessed the ability of a series of FABP4 inhibitors, with more desirable physicochemical properties, to attenuate microglial inflammation in an in vitro setting. Four inhibitors with varying affinity to FABP4, as measured by isothermal titration calorimetry (MFP-0011462, MFP-0012314, MFP-0012318, and MFP-0012328), were assessed for their ability to induce toxicity and attenuate reactive oxygen species (ROS) generation and tumour necrosis factor-α (TNF-α) release from lipopolysaccharide (LPS)-activated BV-2 microglia. All FABP4 inhibitors were determined to be soluble in the aqueous buffers at the highest concentration used in the assays (100 µM). Isothermal titration calorimetry demonstrated that the compounds had varying affinities for FABP4 (K D values of 316 nM to > 100 µM). The ability of FABP4 inhibitors to reduce LPS-mediated ROS production aligned with their K D for FABP4, with the most effective inhibitor (MFP-0012328) also able to reduce TNF-α production (by RT-qPCR) and TNF-α release from LPS-activated BV-2 cells by 17% and 25%, respectively. These studies have demonstrated that a series of FABP4 inhibitors with more appropriate physicochemical properties for BBB penetration are able to reduce microglial-mediated inflammation, which may be of benefit in diseases where overactivation of microglia leads to neurodegeneration.

Thermal properties of native and densified hardwood, softwoods, and agricultural residue - Jordan Klinger; Tyler Westover; Nepu Saha; Chad Sibbett; C. Luke Williams (Biomass and Bioenergy, 2025)

Carcass use by mesoscavengers varied across modified landscapes in the absence of top carnivores - Matthew W. Fielding; Luke A. Yates; Jessie C. Buettel; Dejan Stojanovic; Barry W. Brook (Oecologia, 2025)
The decomposition of carrion is crucial to the functioning and nutrient cycling of ecosystems, and many species use this high-quality resource. However, the availability and reliability of carrion differs across environments. Modified landscapes, such as farms and roads, often produce a high density of carcasses, with disproportionate benefits for generalist mesoscavengers that can tolerate, or are attracted to, human presence. In this study, we placed carcasses strategically across two large islands in southern Australia and used camera traps to investigate how different scavengers locate and use carrion in forested, farmland and roadside habitats. Forest ravens, an avian generalist, were the dominant scavengers across all three habitat types but were three times more likely to discover carcasses deployed in modified landscapes. Raptors were twice as likely to discover and use carcasses in farmland habitats, indicating enhanced scavenging opportunities in these areas. The discovery rate and use of carcasses by feral cats did not differ between habitat types. In this setting, differences in carrion use between diurnal and nocturnal scavengers are potentially due to the absence of top mammalian carnivores (Tasmanian devils and quolls). Diurnal scavengers, such as forest ravens and raptors, followed expected habitat preferences, albeit with greater access to carrion due to increased persistence. However, feral cats demonstrated no preference for carcasses across habitats, likely due to the reduced landscape of fear. Overall, our study underscores the important role of native mammalian carnivores in structuring scavenger communities and further validates the value of trophic rewilding to restore key ecological functions.

A small area analysis of acute exposure to temperatures and mental health in North Carolina - Sophia C Ryan; Luke Wertis; Margaret M. Sugg; Jennifer D. Runkle (International Journal of Biometeorology, 2025)
Increasing evidence suggests that temperatures adversely impact mental and behavioral disorders (MBD). This study explores the effects of temperatures on mental health outcomes using over 5.9 million MBD-related emergency department (ED) visits across three geographical regions of North Carolina (i.e., Mountains, Piedmont, and Coast) from 2016 to 2019. A distributed lag non-linear model (DLNM) with a generalized linear model and quasi-Poisson distribution adjusted for humidity, long-term seasonal time trends, and day of the week examined the acute impact (i.e., 7-day) of temperature on daily MBD-related ED visits at zip code tabulation area (ZCTA) locations. Results were pooled at the region and state levels and reported in reference to the median temperature using a case-time series design for the analysis of small-area data. Stratified analyses were conducted for age, sex, and specific mental-health related ED visits (substance use, mood disorders, anxiety disorders). At the state level, we found significant positive associations between high temperatures (97.5th percentile) and an increase in relative risk (RR) for total MBDs (RR:1.04, 95% CI,1.03–1.05) and psychoactive substance use (RR:1.04, 95% CI, 1.02–1.06). Low air temperatures (2.5th percentile) only increased risk for the elderly (i.e., 65 and older) and predominantly white communities (RR: 1.03, CI: 1.03–1.05). During high temperatures (97.5th percentile), majority-white communities (RR:1.06, CI: 1.01–1.10) and low-income communities had the highest risk for MBDs (RR: 1.05, CI: 1.03–1.07). Our findings suggest there is a positive association between exposure to high temperatures and increased MBD-related ED visits, modified by patient age and place-based sociodemographic (ie., race and income) context.

Soil microbiome community composition shaped by soil depth in a wetland with diel variations in methane emissions - Stacey M. Trevathan-Tackett; Luke C. Jeffrey; Anne Yusuf; Paul E. Carnell; Damien T. Maher; Scott G. Johnston; Peter I. Macreadie (Applied Soil Ecology, 2025)

Degradation rates and ageing effects of UV on tyre and road wear particles - Marloes F. van Os; Merel G.A. Nooijens; Alex van Renesse van Duivenbode; Peter C. Tromp; Elena M. Höppener; Kalouda Grigoriadi; Arjen Boersma; Luke A. Parker (Chemosphere, 2025)

Using seasonal palaeo-flow reconstructions and artificial neural networks for daily water balance modelling: A case study from Tasmania, Australia - Danielle C. Verdon-Kidd; Kathryn J. Allen; Luke J. Kidd; Carolyn Maxwell; Mark Willis; Patrick Baker (Global and Planetary Change, 2025)

Utilization of Ti3C2Tx MXenes on carbonyl functionalized carbon fiber electrodes - Piers Coia; Bhagya Dharmasiri; David J. Hayne; Timothy Harte; Sabina Dann; Ben Newman; Elmer Austria; Behnam Akhavan; Mia Angela N. Judicpa; Kevinilo P. Marquez; Ken Aldren S. Usman; Jizhen Zhang; et al. (Chemical Engineering Journal, 2025)

Harnessing the Power of Next-Generation Sequencing in Wastewater-Based Epidemiology and Global Disease Surveillance - Kata Farkas; Rachel C. Williams; Luke S. Hillary; Alvaro Garcia-Delgado; Eleanor Jameson; Jessica L. Kevill; Matthew J. Wade; Jasmine M. S. Grimsley; Davey L. Jones (Food and Environmental Virology, 2025)
Wastewater-based epidemiology (WBE) has emerged as a valuable surveillance tool for SARS-CoV-2 and other pathogens globally, providing insights into community-level infections, including asymptomatic and pre-symptomatic cases. While most WBE programmes focus on quantitative pathogen assessment, next-generation sequencing (NGS) approaches have enabled more detailed analyses, including variant and recombinant genotype identification for viruses like SARS-CoV-2 and poliovirus. Despite recent NGS advancements allowing for the detection of known and novel viruses in wastewater, many of these tools remain underutilised in routine WBE. This short review critically evaluates the applicability of common NGS tools in routine WBE programmes, assessing their capability for identifying emerging threats with epidemic or pandemic potential. Here, we provide evidence-based recommendations for integrating NGS techniques into WBE and the use of results for informed decision-making within a One Health framework, aiming to enhance global infectious disease surveillance and pandemic preparedness.

Predicting the invasiveness of alpine newts in the UK - Alexandra C. North; Luke J. Sutton; Jason L. Brown; Trenton W. J. Garner; Richard A. Billington; John W. Wilkinson; Manuela Truebano; Robert Puschendorf (Biological Invasions, 2025)
Predicting invasion risk to novel environments is essential for risk management and conservation decision making but the evolutionary lineage at which to make these predictions is often unclear. Here we predict the current suitability across the United Kingdom (UK) for the alpine newt Ichthyosaura alpestris , a species with a complex evolutionary history, a broad native range, a growing number of introduced populations and anecdotal reports of ecological consequences to native amphibian communities. We use species distribution and ecological niche modelling to predict environmental suitability of the alpine newt in the UK at both the species-level and lineage-level and to quantify evolutionary lineage niche overlap. We show good model transferability at the species-level and parts of the UK—especially central and eastern England and parts of central and northern Scotland—to be highly environmentally suitable for the alpine newt. Our findings provide evidence of environmental niche differences at the lineage-level, with the Greek lineage being distinct from most other lineages, but with low confidence in maxent predictions for the Greek, Balkan and Italian lineages due to high levels of extrapolation. In contrast, the niche of the UK records appear to share the same niche as the Central lineage. We find 66% of currently known alpine newt records to fall within areas predicted to be environmentally suitable at the species-level, providing a series of testable hypotheses to better understand the invasion ecology of this species in the UK.

Fracture caging in a lab fault to prevent seismic rupture during fluid injection - Yerkezhan Madenova; Luke P. Frash; Wenfeng Li; Meng Meng; Bijay K C; Jesse Hampton; Qiquan Xiong; Hari S. Viswanathan (Geothermics, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

The effect of nightly use of 150 mg cannabidiol on daytime neurocognitive performance in primary insomnia: a randomized controlled pilot trial - Andrea J. Narayan; Amie C. Hayley; Sarah Rose; Lauren Di Natale; Luke A. Downey (Psychopharmacology, 2025)
Rationale Cannabidiol (CBD) is increasingly used as a sleep aid for insomnia; yet neurocognitive and subjective state effects following daily therapeutic use are unclear. Objectives To measure the effect of daily CBD use on neurocognitive performance and daily subjective mood in a population with primary insomnia. Methods This study used a randomized, placebo-controlled, parallel design incorporating a single-blind placebo run-in week followed by a two-week double-blind dosing period, during which participants consumed 150 mg CBD ( N = 15) or placebo ( N = 15) sublingually 60-minutes daily before bed. Attention, executive function, reasoning, information processing, working and episodic memory were assessed using the CogPro system at the beginning of the placebo run-in, after 1-week and 2-weeks of dosing. Subjective states using visual analogue scales and side effects were recorded daily. Results Cognitive performance was unaffected by nightly CBD supplementation (all p > 0.05). From baseline to trial conclusion, those receiving CBD reported greater experience of calmness, clear-headedness, coordination and were more likely to report side-effects of dry mouth relative to placebo (all p < 0.05). Conclusions Relative to placebo, daytime cognitive functioning following nightly supplementation as a therapeutic aid for primary insomnia was preserved under trial conditions. Results suggested an overall favourable safety profile, with larger controlled trials and thorough analyses of varying insomnia phenotypes necessary to corroborate these findings.

Prediction of the Extent of Blood–Brain Barrier Transport Using Machine Learning and Integration into the LeiCNS-PK3.0 Model - Berfin Gülave; Helle W. van den Maagdenberg; Luke van Boven; Gerard J. P. van Westen; Elizabeth C. M. de Lange; J. G. Coen van Hasselt (Pharmaceutical Research, 2025)
Introduction The unbound brain-to-plasma partition coefficient (K p,uu,BBB ) is an essential parameter for predicting central nervous system (CNS) drug disposition using physiologically-based pharmacokinetic (PBPK) modeling. K p,uu,BBB values for specific compounds are however often unavailable, and are moreover time consuming to obtain experimentally. The aim of this study was to develop a quantitative structure–property relationship (QSPR) model to predict the K p,uu,BBB and to demonstrate how QSPR-model predictions can be integrated into a physiologically-based pharmacokinetic model for the CNS. Methods Rat K p,uu,BBB values were obtained for 98 compounds from literature or in house historical data. For all compounds, 2D and 3D physico-chemical and structural properties were derived using the Molecular Operating Environment (MOE) software. Multiple machine learning (ML) regression models were compared for prediction of the K p,uu,BBB , including random forest, support vector machines, K-nearest neighbors, and (sparse-) partial least squares. Finally, we demonstrate how the developed QSPR model predictions can be integrated into a CNS PBPK modeling workflow. Results Among all ML algorithms, a random forest showed the best predictive performance for K p,uu,BBB on test data with R 2 value of 0.61 and 61% of all predictions were within twofold error. The obtained K p,uu,BBB were successfully integrated into the LeiCNS-PK3.0 CNS PBPK model. Conclusions The developed random forest QSPR model for K p,uu,BBB prediction was found to have adequate performance, and can support drug discovery and development of novel investigational drugs targeting the CNS in conjunction with CNS PBPK modeling.

Millennial- to centennial-scale Atlantic ITCZ swings during the penultimate deglaciation - Marília C. Campos; Cristiano M. Chiessi; Rodrigo A. Nascimento; Laura Kraft; Svetlana Radionovskaya; Luke Skinner; Bruna B. Dias; Tainã M.L. Pinho; Marcus V.L. Kochhann; Stefano Crivellari; Thays D. Mineli; Vinícius R. Mendes; et al. (Quaternary Science Reviews, 2025)

Analysis of bulk stable isotopes and trophic positions of invasive lionfish (Pterois volitans) on deep versus shallow reefs at Curacao - Megan M. Ewing; Rachel Welicky; Carole C. Baldwin; D. Ross Robertson; Katherine P. Maslenikov; Luke Tornabene (Biological Invasions, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Groundwater discharge and bank overtopping drive large carbon exports from Indian Sundarban mangroves - Douglas R. Tait; James Z. Sippo; Luke C. Jeffrey; Damien T. Maher; Abhijit Mukherjee; Christopher Ralph; Kousik Das (Science of The Total Environment, 2024)

Experimental constraints on the role of temperature and pyrogenic mineral assemblage in wildfire-induced major and trace element mobilisation - Kristy Guerin; David Murphy; Stefan C. Löhr; Luke Nothdurft (Geochimica et Cosmochimica Acta, 2024)

Hazard-consistent scenario selection for long-term storm surge risk assessment over extended coastal regions - WoongHee Jung; Alexandros A. Taflanidis; Norberto C. Nadal-Caraballo; Madison C. Yawn; Luke A. Aucoin (Coastal Engineering, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

A comprehensive analysis of new particle formation across the northwest Atlantic: Analysis of ACTIVATE airborne data - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Simon Kirschler; Hongyu Liu; John B. Nowak; Michael A. Shook; Cassidy Soloff; Kenneth L. Thornhill; et al. (Atmospheric Environment, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Accelerated cognitive aging in chronically infected HIV-1 positive individuals despite effective long-term antiretroviral therapy - Hemalatha Babu; Gladys Rachel; Ujjwal Neogi; Alangudi Natarajan Palaniappan; Aswathy Narayanan; Chinnaiyan Ponnuraja; Vijila Sundaraj; Vinod Kumar Viswanathan; C. P. Girish Kumar; Srikanth P. Tripathy; Luke Elizabeth Hanna (Metabolic Brain Disease, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Vertical transport of anthropogenic lead by reversible scavenging in the South Atlantic Ocean - Arianna Olivelli; Maxence Paul; Hui Xu; Katharina Kreissig; Barry J. Coles; Rebekah E.T. Moore; Luke Bridgestock; Micha Rijkenberg; Rob Middag; Maeve C. Lohan; Dominik J. Weiss; Mark Rehkämper; et al. (Earth and Planetary Science Letters, 2024)

Accounting for multiple uncertainties in a decision-support population viability assessment - Erica M. Christensen; Abigail J. Lawson; Erin Rivenbark; Paula K. London; David Castellanos; Jan C. Culbertson; Stephanie M. DeMay; Carly Eakin; Luke S. Pearson; Karen Soileau; Hardin Waddle; Conor P. McGowan (Biological Conservation, 2024)

Review of plant cellulose-based aerogel materials for oil/water mixture separation - Yitong Zhai; Xiaowen Yuan; Cameron C. Weber; Russell J. Varley; Luke C. Henderson (Journal of Environmental Chemical Engineering, 2024)

On-field Head Acceleration Exposure Measurements Using Instrumented Mouthguards: Multi-stage Screening to Optimize Data Quality - Adam C. Clansey; Daniel Bondi; Rebecca Kenny; David Luke; Zaryan Masood; Yuan Gao; Marko Elez; Songbai Ji; Alexander Rauscher; Paul van Donkelaar; Lyndia C. Wu (Annals of Biomedical Engineering, 2024)

Mitochondrial DNA copy number associated dementia risk by somatic mutations and frailty - Qu Tian; David A. Zweibaum; Yong Qian; Richard F. Oppong; Luke C. Pilling; Francesco Casanova; Janice L. Atkins; David Melzer; Jun Ding; Luigi Ferrucci (GeroScience, 2024)
Mitochondrial dysfunction is linked to physical impairment and dementia. Mitochondrial DNA copy number (mtDNAcn) from blood may predict cognitive decline and dementia risk, but the effect of somatic mutations or frailty is unknown. We estimated mtDNAcn using fastMitoCalc and microheteroplasmies using mitoCaller , from Whole Genome Sequencing (WGS) data. In 189,566 participants free of dementia at study entry (mean age = 56 ± 8), we examined the association between mtDNAcn and subsequent dementia diagnosis using Cox regression. Cognition was assessed in a subset on average 8.9 years later. We examined the associations between mtDNAcn and cognitive measures using multivariable linear regression, adjusted for demographic factors, mtDNAcn-related parameters, and apolipoprotein E ε4 status. We further stratified by frailty and microheteroplasmies. Over an average follow-up of 13.2 years, 3533 participants developed dementia. Each SD higher mtDNAcn (16) was associated with 4.2% lower all-cause dementia hazard (HR = 0.958, p = 0.030), 6% lower non-AD dementia hazard (HR = 0.933, p = 0.022), and not-AD dementia hazard. The associations between mtDNAcn and all-cause dementia and non-AD dementia were stronger among those who were pre-frail or frail or with higher microheteroplasmies. Higher mtDNAcn was associated with higher DSST scores ( p = 0.036) and significant only among those with higher microheteroplasmies or frailty ( p = 0.029 and 0.048, respectively). mtDNAcn was also associated with delta TMT and paired associate learning only in pre-frail/frail participants ( p = 0.007 and 0.045, respectively). Higher WGS-based mtDNAcn in human blood is associated with lower dementia risk, specifically non-AD dementia, and specific cognitive function. The relationships appear stronger in high somatic mutations or frailty. Future studies are warranted to investigate biological underpinnings.

Correction to: Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)

In-situ mapping of monocrystalline regions on Mars - Brendan J. Orenstein; Michael W.M. Jones; David T. Flannery; Austin P. Wright; Scott Davidoff; Michael M. Tice; Luke Nothdurft; Abigail C. Allwood (Icarus, 2024)

Proximal microclimate: Moving beyond spatiotemporal resolution improves ecological predictions - David H. Klinges; J. Alex Baecher; Jonas J. Lembrechts; Ilya M. D. Maclean; Jonathan Lenoir; Caroline Greiser; Michael Ashcroft; Luke J. Evans; Michael R. Kearney; Juha Aalto; Isabel C. Barrio; Pieter De Frenne; et al. (Global Ecology and Biogeography, 2024)
Aim The scale of environmental data is often defined by their extent (spatial area, temporal duration) and resolution (grain size, temporal interval). Although describing climate data scale via these terms is appropriate for most meteorological applications, for ecology and biogeography, climate data of the same spatiotemporal resolution and extent may differ in their relevance to an organism. Here, we propose that climate proximity, or how well climate data represent the actual conditions that an organism is exposed to, is more important for ecological realism than the spatiotemporal resolution of the climate data. Location Temperature comparison in nine countries across four continents; ecological case studies in Alberta (Canada), Sabah (Malaysia) and North Carolina/Tennessee (USA). Time Period 1960–2018. Major Taxa Studied Case studies with flies, mosquitoes and salamanders, but concepts relevant to all life on earth. Methods We compare the accuracy of two macroclimate data sources (ERA5 and WorldClim) and a novel microclimate model ( microclimf ) in predicting soil temperatures. We then use ERA5, WorldClim and microclimf to drive ecological models in three case studies: temporal (fly phenology), spatial (mosquito thermal suitability) and spatiotemporal (salamander range shifts) ecological responses. Results For predicting soil temperatures, microclimf had 24.9% and 16.4% lower absolute bias than ERA5 and WorldClim respectively. Across the case studies, we find that increasing proximity (from macroclimate to microclimate) yields a 247% improvement in performance of ecological models on average, compared to 18% and 9% improvements from increasing spatial resolution 20‐fold, and temporal resolution 30‐fold respectively. Main Conclusions We propose that increasing climate proximity, even if at the sacrifice of finer climate spatiotemporal resolution, may improve ecological predictions. We emphasize biophysically informed approaches, rather than generic formulations, when quantifying ecoclimatic relationships. Redefining the scale of climate through the lens of the organism itself helps reveal mechanisms underlying how climate shapes ecological systems.

The frequency and chemical phenotype of neighboring plants determine the effects of intraspecific plant diversity - Andrea E. Glassmire; Kayleigh C. Hauri; Daniel B. Turner; Luke N. Zehr; Koichi Sugimoto; Gregg A. Howe; William C. Wetzel (Ecology, 2024)
Associational effects, whereby plants influence the biotic interactions of their neighbors, are an important component of plant–insect interactions. Plant chemistry has been hypothesized to mediate these interactions. The role of chemistry in associational effects, however, has been unclear in part because the diversity of plant chemistry makes it difficult to tease apart the importance and roles of particular classes of compounds. We examined the chemical ecology of associational effects using backcross‐bred plants of the Solanum pennellii introgression lines. We used eight genotypes from the introgression line system to establish 14 unique neighborhood treatments that maximized differences in acyl sugars, proteinase inhibitor, and terpene chemical diversity. We found that the chemical traits of the neighboring plant, rather than simply the number of introgression lines within a neighborhood, influenced insect abundance on focal plants. Furthermore, within‐chemical class diversity had contrasting effects on herbivore and predator abundances, and depended on the frequency of neighboring plant chemotypes. Notably, we found insect mobility—flying versus crawling—played a key role in insect response to phytochemistry. We highlight that the frequency and chemical phenotype of plant neighbors underlie associational effects and suggest this may be an important mechanism in maintaining intraspecific phytochemical variation within plant populations.

Simulated radiocarbon cycle revisited by considering the bipolar seesaw and benthic 14C data - Peter Köhler; Luke C. Skinner; Florian Adolphi (Earth and Planetary Science Letters, 2024)

The future of Southeast Asia's biodiversity: A crisis with a hopeful alternative - Thomas Botterill-James; Luke A. Yates; Jessie C. Buettel; Barry W. Brook (Biological Conservation, 2024)

Regional foraging areas of green turtles (Chelonia mydas) nesting at Aldabra Atoll: insights from stable isotopes and satellite telemetry - Cheryl L. Sanchez; Paolo Casale; Nancy Bunbury; Luke A’Bear; Maria Bielsa; Christopher W. Jones; Martin C. van Rooyen; Brian Souyana; Frauke Fleischer-Dogley; Simona A. Ceriani (Biodiversity and Conservation, 2024)
Sea turtles spend the majority of their lives at foraging grounds. These areas are important for population persistence but generally occur in coastal habitats, which are under increasing human pressure. Identifying key foraging areas is therefore an important step to understanding critical sea turtle habitats, and therefore their threats. Isotope ratios ( δ 15 N, δ 13 C) from skin tissues of 90 green turtles ( Chelonia mydas ) nesting at the regionally important rookery of Aldabra Atoll, Seychelles, were analyzed with samples collected during two periods: 51 samples from March to September 2021, and 39 samples from January to April 2022. These analyses were complemented by nine satellite tracks to identify key foraging areas. Hierarchical clustering and discriminant function analysis identified two main foraging areas: the East African coast (Tanzania and Somalia) and northern Madagascar. Isotopic values indicated that the majority of green turtles nesting at Aldabra forage at one of these two areas, with slightly more green turtles visiting the East African coast. Geographical isotopic patterns were not found latitudinally, suggesting a potential limit to this approach for coastal areas in the Western Indian Ocean. However, we found longitudinal variation of δ 13 C and δ 15 N that few studies have reported. This is the first study in this region to combine satellite telemetry and stable isotope analysis to assign likely foraging areas of green turtles and advances understanding of the complex migration patterns and foraging ecology of this species. We demonstrate the potential and the limitations of stable isotope analysis for identifying/characterizing green turtle foraging areas in this region.

Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)
Immunogenicity testing and characterization is an important part of understanding the immune response to administration of a protein therapeutic. Neutralizing antibody (NAb) assays are used to characterize a positive anti-drug antibody (ADA) response. Harmonization of reporting of NAb assay performance and results enables efficient communication and expedient review by industry and health authorities. Herein, a cross-industry group of NAb assay experts have harmonized NAb assay reporting recommendations and provided a bioanalytical report (BAR) submission editable template developed to facilitate agency filings. This document addresses key bioanalytical reporting gaps and provides a report structure for documenting clinical NAb assay performance and results. This publication focuses on the content and presentation of the NAb sample analysis report including essential elements such as the method, critical reagents and equipment, data analysis, study samples, and results. The interpretation of immunogenicity data, including the evaluation of the impact of NAb on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Demographic change and loss of big trees in resprouting eucalypt forests exposed to megadisturbance - Eli R. Bendall; Luke C. Collins; Kirsty V. Milner; Michael Bedward; Matthias M. Boer; Brendan Choat; Rachael V. Gallagher; Belinda E. Medlyn; Rachael H. Nolan (Global Ecology and Biogeography, 2024)
Aim Increased tree mortality linked to droughts and fires is occurring across temperate regions globally. Vegetation recovery has been widely reported; however, less is known about how disturbance may alter forests structurally and functionally across environmental gradients. We examined whether dry forests growing on low‐fertility soils were more resilient to coupled extreme drought and severe fire owing to lower tree mortality rates, higher resprouting success and persistence of juveniles relative to wetter forests on more fertile soils. Location Fire‐tolerant eucalypt forests of temperate southeastern Australia. Time period 2020–2023. Major taxa studied Eucalyptus , Corymbia , Angophora . Methods Demographic surveys of tree mortality and regeneration in all combinations of dry/wet forest, fertile/less fertile substrates exposed to extreme drought and fire were conducted. We used Bayesian regression modelling to compare tree mortality, diameter, response traits, population structure and occurrence of fire scars between substrates/forest types. Results Overall mortality (20%–33%) and topkill (34%–41%) were within historically reported ranges for various forests and soil types. However, we observed an atypical trend of increased mortality and topkill in the largest trees, particularly when they had structural damage from past fires. Trees in wet forests on more fertile soils had the highest levels of mortality. Numbers of persistent resprouting juveniles were highest in dry forests on low‐fertility soils. Dry forests growing on low‐fertility soils appear more resilient to compound disturbances due to lower rates of mortality and higher rates of juvenile persistence. Wet forests on more fertile soils may experience greater demographic change due to higher mortality of small and large trees. Main conclusions Mesic forests on relatively fertile soils were found to be at relatively high risk of demographic change from compound disturbances. Combined, fire and drought are likely to reduce the number of large trees in affected areas, with consequences for forest carbon cycling and storage.

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Fine-scale foraging ecology and habitat use of sympatric green and hawksbill turtles in the Western Indian ocean - Cheryl L. Sanchez; Paolo Casale; Nancy Bunbury; Luke A'Bear; Veronique Banane; Frances Benstrong; Maria Bielsa; Christopher W. Jones; Anna Koester; Susan Murasko; Martin C. van Rooyen; Frauke Fleischer-Dogley; et al. (Marine Environmental Research, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Comparative analysis of joint distribution models for tropical cyclone atmospheric parameters in probabilistic coastal hazard analysis - Ziyue Liu; Meredith L. Carr; Norberto C. Nadal-Caraballo; Luke A. Aucoin; Madison C. Yawn; Michelle T. Bensi (Stochastic Environmental Research and Risk Assessment, 2024)

Reclamation and reformatting of waste carbon fibers: A paradigm shift towards sustainable waste management - Pejman Heidarian; Fatemeh Mokhtari; Minoo Naebe; Luke C. Henderson; Russell J. Varley (Resources, Conservation and Recycling, 2024)

Small-scale movements and site fidelity of two sympatric sea turtle species at a remote atoll - Cheryl L. Sanchez; Nancy Bunbury; Jeanne A. Mortimer; Luke A’Bear; Jennifer Appoo; Michael Betts; Rainer von Brandis; Lorraine Cook; Janske van de Crommenacker; Jock C. Currie; Naomi Doak; Frauke Fleischer-Dogley; et al. (Marine Biology, 2024)
Understanding natural movement patterns and ecological roles of marine megafauna is a research priority best studied in areas with minimal human impact. The spatial distribution patterns specifically for immature turtles at foraging grounds have been highlighted as a research gap for effective management and conservation strategies for sea turtle populations. Capture–mark–recapture (CMR) records ( n = 2287) of 1672 immature green ( Chelonia mydas ) ( n = 1158) and hawksbill turtles ( Eretmochelys imbricata ) ( n = 514) from a long-term (1981–2021) in-water CMR program at Aldabra Atoll, Seychelles, were analyzed for 10 sites (0.35–25 km apart). Site fidelity was not correlated with either season or turtle size. Green turtles had lower site fidelity than hawksbill turtles. Green turtles showed avoidance (i.e., opposite of fidelity) of three sites, while hawksbill turtles displayed high fidelity to two sites. Sites displaying non-random behavior (avoidance and/or fidelity) did not share the same benthic habitat types. Results indicate that fidelity can be detected at a fine scale with CMR, but that further exploration into the habitat characteristics of the sites and the ecological roles of both species at the atoll is needed.

Cryptic diversification, phenotypic plasticity, and host specialization in a sponge-dwelling goby - Ariel Wang; Sarah Yerrace; Luke Tornabene; Simon J. Brandl; Christopher J. Freeman; Carole C. Baldwin; Jordan M. Casey (Coral Reefs, 2024)

Differential advances in budburst timing among black spruce, white spruce and balsam fir across Canada - Diego S. Podadera; Lorena Balducci; Sergio Rossi; Fabrizio Cartenì; Valérie Néron; Rémi Saint-Amant; Stefano Mazzoleni; Jacques Régnière; Eric R.D. Moise; Joseph J. Bowden; Jean-Noël Candau; Alain Dupont; et al. (Agricultural and Forest Meteorology, 2024)

Wave, light, and dissolved oxygen exposures drive novel coastal eelgrass (Zostera pacifica) transplant performance - Rilee D. Sanders; Adam K. Obaza; Benjamin C. Grime; Mathilde Lindhart; Luke P. Miller; Kristen E. Elsmore; Olivia C. Carmack; Tom K. Ford; James J. Leichter (Frontiers in Marine Science, 2024)
The high ecological and economic value of seagrass has been long recognized, with these foundational habitats providing myriad ecosystem services. Yet through cumulative anthropogenic impacts, seagrasses are exhibiting extensive declines globally. A litany of studies and active restoration trials have demonstrated practical methodologies to restore seagrass habitats and effectively return critical habitat functions to degraded coastal zone systems worldwide. Seagrass loss along the U.S. West Coast has precipitated decades of seagrass protection, conservation, and restoration efforts. Yet, mitigation transplanting efforts have prioritized Zostera marina (narrow-leaved eelgrass) in shallow, protected environments, while a dearth of information is available on species inhabiting offshore islands and exposed mainland coasts. In this study, we conducted a novel transplant of Zostera pacifica , a wide-leaved species found in depths of 7 – 20 m along the offshore islands and mainland coast of California. Transplants were conducted at three geographically distinct sites in Santa Monica Bay, coupled with continuous monitoring of biophysical parameters providing insight into physical drivers at transplant and donor sites. Utilizing in situ data, and environmental thresholds adapted from the literature for Z. marina , we performed exposure analyses to evaluate factors influencing Z. pacifica transplant performance. Exceedances of threshold values for environmental parameters, specifically, wave exposure and near-bed flow speeds ( H rms > 0.59 m and U rms > 0.1 m s -1 ), photosynthetically active radiation (< 3 and > 5 mol m -2 day -1 ) and dissolved oxygen (< 3 mg O 2 L -1 ) exposure impacted transplant survivorship. These results suggest Z. pacifica persist in biophysically dynamic conditions and are sensitive to exceedances of thresholds, underlining the importance of pre-transplant site-selection processes to this species. These data represent the first holistic study of Z. pacifica transplanting on an exposed mainland coast, which provides a view into the baseline environmental envelopes within existing Z. pacifica habitat, and further, may serve as a model for investigating scalable open coast seagrass restoration for temperate regions.

Predicting spring phenology in deciduous broadleaf forests: NEON phenology forecasting community challenge - Kathryn I. Wheeler; Michael C. Dietze; David LeBauer; Jody A. Peters; Andrew D. Richardson; Arun A. Ross; R. Quinn Thomas; Kai Zhu; Uttam Bhat; Stephan Munch; Raphaela Floreani Buzbee; Min Chen; et al. (Agricultural and Forest Meteorology, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Regional storm surge hazard quantification using Gaussian process metamodeling techniques - WoongHee Jung; Alexandros A. Taflanidis; Norberto C. Nadal-Caraballo; Madison C. Yawn; Luke A. Aucoin (Natural Hazards, 2024)

A multi‐population approach supports common patterns in marine growth and maturation decision in Atlantic salmon ( Salmo salar L.) from southern Europe - Cécile Tréhin; Etienne Rivot; Valentin Santanbien; Rémi Patin; Stephen D. Gregory; Ludivine Lamireau; Frédéric Marchand; William R. C. Beaumont; Luke J. Scott; Robert Hillman; Anne‐Laure Besnard; Pierre‐Yves Boisson; et al. (Journal of Fish Biology, 2024)
This study provides a regional picture of long‐term changes in Atlantic salmon growth at the southern edge of their distribution, using a multi‐population approach spanning 49 years and five populations. We provide empirical evidence of salmon life history being influenced by a combination of common signals in the marine environment and population‐specific signals. We identified an abrupt decline in growth from 1976 and a more recent decline after 2005. As these declines have also been recorded in northern European populations, our study significantly expands a pattern of declining marine growth to include southern European populations, thereby revealing a large‐scale synchrony in marine growth patterns for almost five decades. Growth increments during their sea sojourn were characterized by distinct temporal dynamics. At a coarse temporal resolution, growth during the first winter at sea seemed to gradually improve over the study period. However, the analysis of finer seasonal growth patterns revealed ecological bottlenecks of salmon life histories at sea in time and space. Our study reinforces existing evidence of an impact of early marine growth on maturation decision, with small‐sized individuals at the end of the first summer at sea being more likely to delay maturation. However, each population was characterized by a specific probabilistic maturation reaction norm, and a local component of growth at sea in which some populations have better growth in some years might further amplify differences in maturation rate. Differences between populations were smaller than those between sexes, suggesting that the sex‐specific growth threshold for maturation is a well‐conserved evolutionary phenomenon in salmon. Finally, our results illustrate that although most of the gain in length occurs during the first summer at sea, the temporal variability in body length at return is buffered against the decrease in post‐smolt growth conditions. The intricate combination of growth over successive seasons, and its interplay with the maturation decision, could be regulating body length by maintaining diversity in early growth trajectories, life histories, and the composition of salmon populations.

Elevated CO 2 interacts with nutrient inputs to restructure plant communities in phosphorus‐limited grasslands - Christopher R. Taylor; Luke C. England; J. Ben Keane; Jessica A. C. Davies; Jonathan R. Leake; Iain P. Hartley; Simon M. Smart; Victoria Janes‐Bassett; Gareth K. Phoenix (Global Change Biology, 2024)
Globally pervasive increases in atmospheric CO 2 and nitrogen (N) deposition could have substantial effects on plant communities, either directly or mediated by their interactions with soil nutrient limitation. While the direct consequences of N enrichment on plant communities are well documented, potential interactions with rising CO 2 and globally widespread phosphorus (P) limitation remain poorly understood. We investigated the consequences of simultaneous elevated CO 2 (eCO 2 ) and N and P additions on grassland biodiversity, community and functional composition in P‐limited grasslands. We exposed soil‐turf monoliths from limestone and acidic grasslands that have received >25 years of N additions (3.5 and 14 g m −2 year −1 ) and 11 (limestone) or 25 (acidic) years of P additions (3.5 g m −2 year −1 ) to eCO 2 (600 ppm) for 3 years. Across both grasslands, eCO 2 , N and P additions significantly changed community composition. Limestone communities were more responsive to eCO 2 and saw significant functional shifts resulting from eCO 2 –nutrient interactions. Here, legume cover tripled in response to combined eCO 2 and P additions, and combined eCO 2 and N treatments shifted functional dominance from grasses to sedges. We suggest that eCO 2 may disproportionately benefit P acquisition by sedges by subsidising the carbon cost of locally intense root exudation at the expense of co‐occurring grasses. In contrast, the functional composition of the acidic grassland was insensitive to eCO 2 and its interactions with nutrient additions. Greater diversity of P‐acquisition strategies in the limestone grassland, combined with a more functionally even and diverse community, may contribute to the stronger responses compared to the acidic grassland. Our work suggests we may see large changes in the composition and biodiversity of P‐limited grasslands in response to eCO 2 and its interactions with nutrient loading, particularly where these contain a high diversity of P‐acquisition strategies or developmentally young soils with sufficient bioavailable mineral P.

Microbiome mediating methane and nitrogen transformations in a subterranean estuary - Sebastian Euler; Luke C. Jeffrey; Damien T. Maher; Scott G. Johnston; Ryo Sugimoto; Douglas R. Tait (Environmental Microbiology, 2024)
Subterranean estuaries (STEs) are important coastal biogeochemical reactors facilitating unique niches for microbial communities. A common approach in determining STE greenhouse gas and nutrient fluxes is to use terrestrial endmembers, not accounting for microbially mediated transformations throughout the STE. As such, the microbial ecology and spatial distribution of specialists that cycle compounds in STEs remain largely underexplored. In this study, we applied 16S rRNA amplicon sequencing with paired biogeochemical characterisations to spatially evaluate microbial communities transforming greenhouse gases and nutrients in an STE. We show that methanogens are most prevalent at the terrestrial end (up to 2.81% relative abundance) concomitant to the highest porewater methane, carbon dioxide and dissolved organic carbon concentrations (0.41 ± 0.02 μM, 273.31 ± 6.05 μM and 0.51 ± 0.02 mM, respectively). Lower ammonium concentrations corresponded with abundant nitrifying and ammonia‐oxidising prokaryotes in the mixing zone (up to 11.65% relative abundance). Methane, ammonium and dissolved organic carbon concentrations all decreased by >50% from the terrestrial to the oceanic end of the 15 m transect. This study highlights the STE's hidden microbiome zonation, as well as the importance of accounting for microbial transformations mitigating nutrient and greenhouse gas fluxes to the coastal ecosystems.

Challenges of classifying and mapping perennial freshwater systems within highly variable climate zones: A case study in the Murray Darling Basin, Australia - Danielle C. Verdon-Kidd; Steven G. Sandi; Angela G. Metcalfe; Luke J. Kidd (Science of The Total Environment, 2023)

Synthesis and characterization of high-density biosynthetic fuels from myrtenal - Michael D. Garrison; C. Luke Keller; Josanne-Dee Woodroffe; Eric M. Nagel; Benjamin G. Harvey (Fuel, 2023)

Effects of a megafire vary with fire severity and forest type: The impact of Australia's ‘Black Summer’ fires on the superb lyrebird (Menura novaehollandiae), an iconic forest species - Alex C. Maisey; Luke Collins; Graeme Newell; Andrew F. Bennett (Biological Conservation, 2023)

The Hypervariable Tpr Multigene Family of Theileria Parasites, Defined by a Conserved, Membrane-Associated, C-Terminal Domain, Includes Several Copies with Defined Orthology Between Species - Nicholas C. Palmateer; James B. Munro; Sushma Nagaraj; Jonathan Crabtree; Roger Pelle; Luke Tallon; Vish Nene; Richard Bishop; Joana C. Silva (Journal of Molecular Evolution, 2023)
Multigene families often play an important role in host-parasite interactions. One of the largest multigene families in Theileria parva , the causative agent of East Coast fever, is the T. parva repeat ( Tpr ) gene family. The function of the putative Tpr proteins remains unknown. The initial publication of the T. parva reference genome identified 39 Tpr family open reading frames (ORFs) sharing a conserved C-terminal domain. Twenty-eight of these are clustered in a central region of chromosome 3, termed the “ Tpr locus”, while others are dispersed throughout all four nuclear chromosomes. The Tpr locus contains three of the four assembly gaps remaining in the genome, suggesting the presence of additional, as yet uncharacterized, Tpr gene copies. Here, we describe the use of long-read sequencing to attempt to close the gaps in the reference assembly of T. parva (located among multigene families clusters), characterize the full complement of Tpr family ORFs in the T. parva reference genome, and evaluate their evolutionary relationship with Tpr homologs in other Theileria species. We identify three new Tpr family genes in the T. parva reference genome and show that sequence similarity among paralogs in the Tpr locus is significantly higher than between genes outside the Tpr locus. We also identify sequences homologous to the conserved C-terminal domain in five additional Theileria species. Using these sequences, we show that the evolution of this gene family involves conservation of a few orthologs across species, combined with gene gains/losses, and species-specific expansions.

Observing the full ocean volume using Deep Argo floats - Nathalie V. Zilberman; Virginie Thierry; Brian King; Matthew Alford; Xavier André; Kevin Balem; Nathan Briggs; Zhaohui Chen; Cécile Cabanes; Laurent Coppola; Giorgio Dall’Olmo; Damien Desbruyères; et al. (Frontiers in Marine Science, 2023)
The ocean is the main heat reservoir in Earth’s climate system, absorbing most of the top-of-the-atmosphere excess radiation. As the climate warms, anomalously warm and fresh ocean waters in the densest layers formed near Antarctica spread northward through the abyssal ocean, while successions of warming and cooling events are seen in the deep-ocean layers formed near Greenland. The abyssal warming and freshening expands the ocean volume and raises sea level. While temperature and salinity characteristics and large-scale circulation of upper 2000 m ocean waters are well monitored, the present ocean observing network is limited by sparse sampling of the deep ocean below 2000 m. Recently developed autonomous robotic platforms, Deep Argo floats, collect profiles from the surface to the seafloor. These instruments supplement satellite, Core Argo float, and ship-based observations to measure heat and freshwater content in the full ocean volume and close the sea level budget. Here, the value of Deep Argo and planned strategy to implement the global array are described. Additional objectives of Deep Argo may include dissolved oxygen measurements, and testing of ocean mixing and optical scattering sensors. The development of an emerging ocean bathymetry dataset using Deep Argo measurements is also described.

Ti3C2Tx MXene coated carbon fibre electrodes for high performance structural supercapacitors - Bhagya Dharmasiri; Ken Aldren S. Usman; Si Alex Qin; Joselito M. Razal; Ngon T. Tran; Piers Coia; Timothy Harte; Luke C. Henderson (Chemical Engineering Journal, 2023)

Outdoor environmental exposome and the burden of tuberculosis: Findings from nearly two million adults in northwestern China - Jia-Xin Li; Qiyun Luan; Beibei Li; Shyamali C. Dharmage; Joachim Heinrich; Michael S. Bloom; Luke D. Knibbs; Igor Popovic; Li Li; Xuemei Zhong; Aimin Xu; Chuanjiang He; et al. (Journal of Hazardous Materials, 2023)

Geoethical issues around water security for the City of Cape Town (South Africa) and groundwater resilience in uncertain circumstances: development of the Atlantis, Cape Flats and Table Mountain Group Aquifers - Dylan Blake; Christopher J. H. Hartnady; E. Rowena Hay; David C. McGibbon; Luke C. Towers; Kornelius Riemann; Rui T. Hugman (Sustainable Water Resources Management, 2023)

Impacts of coral bleaching on reef fish abundance, biomass and assemblage structure at remote Aldabra Atoll, Seychelles: insights from two survey methods - Anna Koester; Cesc Gordó−Vilaseca; Nancy Bunbury; Sebastian C. A. Ferse; Amanda Ford; Philip Haupt; Luke A’Bear; Maria Bielsa; April Jasmine Burt; Jake Letori; Emma Mederic; Ella Nancy; et al. (Frontiers in Marine Science, 2023)
Introduction Coral bleaching immediately impacts the reef benthos, but effects on fish communities are less well understood because they are often delayed and confounded by anthropogenic interactions. Methods We assessed changes in fish abundance, biomass and community composition before and after the 2015/16 coral bleaching event at Aldabra Atoll, Seychelles, where local human impacts are minimal, but reefs suffered 50% bleaching-induced coral mortality. We monitored 12 shallow (2–5 m water depth) and nine deep (15 m water depth) permanent survey sites using two survey methods: indicator surveys recording 84 taxa over six years (pre-: 2014; post-bleaching: 2016–2019, 2021), sizing fish based on six size-class categories, and extended fish surveys recording 198 taxa over two years (pre-: 2015; post-bleaching: 2020) with size estimates to the nearest cm (excluding fish < 8 cm). Results During indicator surveys, mean fish abundance did not change on deep reefs. However, abundance increased by 77% on shallow reefs between 2014 and 2016, which was mainly driven by increases in herbivores and omnivores, likely as a response to elevated turf algae cover following coral mortality. Overall (and functional group-specific) indicator fish biomass did not differ between 2014 and 2016 and remained at or above pre-bleaching levels throughout 2016–2021. In contrast, extended fish surveys in 2015 and 2020 showed a 55–60% reduction in overall abundance on shallow and deep reefs, and a 69% reduction in biomass on shallow reefs, with decreases in biomass occurring in all functional groups. Biomass on deep reefs did not differ between 2015 and 2020. Multivariate analysis of both data sets revealed immediate and long-lasting differences between pre- and post-bleaching fish community compositions, driven largely by herbivorous, omnivorous and piscivorous taxa. Discussion Results from the indicator surveys suggest that the bleaching event had limited impact on fish abundance and biomass, while the extended surveys recorded changes in abundance and biomass which would otherwise have gone undetected. Our findings improve understanding of the shift a broad community of fish undergoes following a mass coral bleaching event and highlights the value of survey methods that include the full suite of species to detect ecological responses to environmental drivers.

Methanogens limited to lower rhizosphere and to an atypical salt marsh niche along a pristine intertidal mangrove continuum - Sebastian Euler; Luke C. Jeffrey; Damien T. Maher; Scott G. Johnston; Ryo Sugimoto; Douglas R. Tait (Limnology and Oceanography, 2023)
Mangroves are valuable ecosystems that facilitate primary production, carbon sequestration, and regulation of greenhouse gas (GHG) cycles in coastal sediments, with microorganisms playing key roles. Specialized bacteria and archaea compete for energy and resources in mangrove sediments to inhabit optimal ecological niches and can produce or consume methane (CH 4 )—a potent GHG—in the process. CH 4 cycling in mangroves has gained growing attention, yet uncertainties regarding functional and spatial distributions of microorganisms remain. Here, we demonstrate that in a pristine mangrove forest, CH 4 concentrations and methanogen communities are concentrated within lower or below rhizosphere depths. We also reveal atypical niches for methanogens in the upper tidal salt marsh zone where vegetation is sparse and highest methanogens abundances were detected at deepest depths (4715 reads g −1 ) despite relatively high redox potentials (> 250 mV). Pore water CH 4 concentrations were highest at the deepest depth within the mangrove forest (max. 3.40 ± 0.21 μ M) and coincided with the highest sediment CH 4 fluxes (276.4 ± 54.2 μ mol m −2 d −1 ) and methanotroph abundances at the surface (1309 reads g −1 ). Sediment CH 4 oxidation fractions between the deepest (60 cm) and shallowest (5 cm) depths were estimated between 18.8% and 64.9%. Positive correlation between crab burrows and CH 4 fluxes suggests that CH 4 from deeper sediment and salt marsh niches can be transported via conduits to the atmosphere. The spatial data from this study highlights the importance of investigating CH 4 dynamics across estuarine ecosystem gradients to better understand the complex roles of vital coastal vegetation zones in the face of a changing climate.

Does physical activity moderate the association between shorter leukocyte telomere length and incident coronary heart disease? Data from 54,180 UK Biobank participants - Meiruo Xiang; Luke C. Pilling; David Melzer; Ben Kirk; Gustavo Duque; Rui Liu; George A. Kuchel; Andrew R. Wood; Brad Metcalf; Breno S. Diniz; Melvyn Hillsdon; Chia-Ling Kuo (GeroScience, 2023)
Telomere shortening is a biological aging hallmark. The effect of short telomere length may be targeted by increased physical activity to reduce the risk of multiple aging-related diseases, including coronary heart disease (CHD). The objective was to assess the moderation effect of accelerometer-based physical activity (aPA) on the association between shorter leukocyte telomere length (LTL) relatively in the population sample and incident CHD. Data were from the UK Biobank participants with well-calibrated accelerometer data for at least 6.5 days ( n = 54,180). Relative mean LTL at baseline (5–6 years prior to aPA assessment) was measured in T/S ratio, using a multiplex quantitative polymerase chain reaction (qPCR) technology, by comparing the amount of the telomere amplification product (T) to that of a single-copy gene (S). aPA measures included total number of events (at least 10-s continued physical activity > 32 milligravities [mg]), total volume, mean duration, mean intensity, and peak intensity of all events. LTL, aPA measures, and their interactions were associated with incident CHD (mean follow-up 6.8 years) using Cox proportional hazards models adjusting for covariates. Longer LTL (relative to the sample distribution) was associated with reduced incidence of CHD (adjusted hazard ratio [aHR] = 0.94 per standard deviation [SD] increase in LTL, [95% CI, 0.90 to 0.99], P = .010). Incidence of CHD was reduced by higher total volume of aPA (aHR = 0.82 per SD increase in LTL, [95% CI, 0.71 to 0.95], P = .010) but increased by higher total number of events (aHR = 1.11 per SD increase in LTL, [95% CI, 1.02 to 1.21], P = .020) after controlling for other aPA measures and covariates. However, none of the interactions between LTL and aPA measures was statistically significant ( P = .171).

40 years of changes in sea surface temperature along the Western Iberian Coast - Beatriz Biguino; Carlos Antunes; Luísa Lamas; Luke J. Jenkins; João Miguel Dias; Ivan D. Haigh; Ana C. Brito (Science of The Total Environment, 2023)

Evaluating the influence of nature connection and values on conservation attitudes at a tropical deforestation frontier - Katarzyna M. Mikołajczak; Jos Barlow; Alexander C. Lees; Christopher D. Ives; Micha Strack; Oriana Trindade de Almeida; Agnis C. Souza; Frazer Sinclair; Luke Parry (Conservation Biology, 2023)
Inner phenomena, such as personal motivations for pursuing sustainability, may be critical levers for improving conservation outcomes. Most conservation research and policies, however, focus on external phenomena (e.g., ecological change or economic processes). We explored the factors shaping 9 conservation attitudes toward forest and wildlife protection among colonist farmers around an Amazonian deforestation frontier. Our data comprised 241 face‐to‐face quantitative surveys, complemented with qualitative insights from open‐ended questionnaire responses and opportunistic semistructured interviews. To account for the full spectrum of possible inner motivations, we employed measures of nature connection (indicating biospheric motivation) and personal values organized around the traditionalism (traditionalist through to high openness to change) and universalism dimensions (egoistic through to altruistic motivations). We used averaged beta‐binomial generalized linear models to assess the role of external factors (socioeconomic, sociodemographic, and environmental) and personal (inner) motivations on the variation in attitudes. Each attitude was modeled separately. The relative importance of each predictor was judged by the proportion of models where it appeared as significant. Proconservation views were expressed by the majority (at least 65%) of the respondents in 7 out of the 9 attitude models. The most consistent predictors were emotional nature connection and personal values (significant in 4–6 out of 9 models), rather than external phenomena (significant in 0–5 models). However, the poorest farmers had lower scores on the agreement with prioritizing nature over development (𝛽 = –0.52, 95% CI: –0.96 to –0.07). Qualitative data also indicated that economic barriers hinder forest conservation on farms. These results suggest that biospheric, traditionalistic, and altruistic motivations promote people's proconservation attitudes, but nurturing these latent motivations is unlikely to improve conservation outcomes if material poverty remains unaddressed. Integrating the inner–outer perspective into conservation thinking and practical interventions could foster environmental stewardship and increase human well‐being.

Primary and pharmaceutical care usage concurrent associations with a severe smoke episode and low ambient air pollution in early life - Myriam Ziou; Caroline X. Gao; Amanda J. Wheeler; Graeme R. Zosky; Nicola Stephens; Luke D. Knibbs; Grant J. Williamson; Shannon M. Melody; Alison J. Venn; Marita F. Dalton; Shyamali C. Dharmage; Fay H. Johnston (Science of The Total Environment, 2023)

Cascading disasters and mental health: The February 2021 winter storm and power crisis in Texas, USA - Margaret M. Sugg; Luke Wertis; Sophia C. Ryan; Shannon Green; Devyani Singh; Jennifer D. Runkle (Science of The Total Environment, 2023)

Drilling 1100-km-long seafloor ridges reveals how palaeoshorelines control carbonate shelf morphologies (North West Shelf, Australia) - Ulysse Lebrec; Rosine Riera; Michael O'Leary; Jody M. Webster; Yusuke Yokoyama; Luke A. Gliganic; Simon C. Lang; Victorien Paumard (Quaternary Science Reviews, 2023)

Intramammary and systemic use of antimicrobials and their association with resistance in generic Escherichia coli recovered from fecal samples from Canadian dairy herds: A cross-sectional study - Mariana Fonseca; Luke C. Heider; Henrik Stryhn; J.Trenton McClure; David Léger; Daniella Rizzo; Landon Warder; Simon Dufour; Jean-Philippe Roy; David F. Kelton; David Renaud; Herman W. Barkema; et al. (Preventive Veterinary Medicine, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Historical pesticide applications for the treatment of eastern spruce budworm infestations in New Brunswick - Shane Heartz; David A. MacLean; Rob C. Johns; Drew Carleton; Luke Amos‐Binks; Quinn Anderson; Yue Yu; Andrew D. Lewis; Dan Lavigne; Joseph B. Burant; Christopher B. Edge (Ecology, 2023)
Pesticides have been used in Canada since 1945 as part of large‐scale aerial spray applications to control insect pests on forested lands. Some of the pesticides used historically were efficacious, nonselective, persistent, and have led to serious impacts on the environment. A well known, and extensively documented example is the large‐scale aerial spray programs in New Brunswick, Canada. From 1952 to 1993, 97% of the 6.2 million ha of the forested lands of New Brunswick were treated with at least one application of one insecticide, the majority of which were applied to control outbreaks of eastern spruce budworm ( Choristoneura fumiferana ). The most well known insecticide was dichlorodiphenyltrichloroethane (DDT), applied from 1952 to 1968, which still persists in treated soils and adjacent water bodies, and caused the individual and cumulative ecosystem effects that can still be measured today. The insecticides that replaced DDT were nonpersistent and unlikely to be found today. However, during the years of application some of the insecticides were likely to have impacted local ecosystems to some degree. To aid future studies on the efficacy and environmental impact of these insecticides we created a digital spatial data set of known pesticide application in New Brunswick forestry from 1952 to 1993. The data set includes active ingredient, formulation, application rate, tank mix, aircraft type, and other ancillary information. The current version of the data is available on the New Brunswick Department of Natural Resources and Energy Development, GIS Open Data Page and in the supplemental material. Use of the data set for academic and educational purposes is encouraged, provided that both this data paper and the data source are properly cited; the Government of New Brunswick should be acknowledged as the data source (Open Government License http://www.snb.ca/e/2000/data-E.html ).

Antimicrobial use and its association with the isolation of and antimicrobial resistance in Campylobacter spp. recovered from fecal samples from Canadian dairy herds: A cross-sectional study - Mariana Fonseca; Luke C. Heider; Henrik Stryhn; J.Trenton McClure; David Léger; Daniella Rizzo; Landon Warder; Simon Dufour; Jean-Philippe Roy; David F. Kelton; David Renaud; Herman W. Barkema; et al. (Preventive Veterinary Medicine, 2023)

Comparing anesthetic stations and environmental DNA sampling to determine community composition of cryptobenthic coral reef fishes of Vava’u, Kingdom of Tonga - Marta C. Gómez-Buckley; Ramón Gallego; Vanessa Arranz; Tuikolongahau Halafihi; Karen Stone; Mark Erdmann; Luke M. Tornabene (Coral Reefs, 2023)

To seal or not to seal following an antimicrobial infusion at dry-off? A systematic review and multivariate meta-analysis of the incidence and prevalence of intramammary infections post-calving in dairy cows - Mohamed Afifi; Henrik Stryhn; Javier Sanchez; Luke C. Heider; Fidèle Kabera; Jean-Philippe Roy; Sandra Godden; Simon Dufour (Preventive Veterinary Medicine, 2023)

Nonequilibrium spherulitic magnetite in the Ryugu samples - Elena Dobrică; Hope A. Ishii; John P. Bradley; Kenta Ohtaki; Adrian J. Brearley; Takaaki Noguchi; Toru Matsumoto; Akira Miyake; Yohei Igami; Mitsutaka Haruta; Hikaru Saito; Satoshi Hata; et al. (Geochimica et Cosmochimica Acta, 2023)

Growth rate and projected age at sexual maturity for immature hawksbill turtles and green turtles foraging in the remote marine protected area of Aldabra Atoll, Seychelles - Cheryl L. Sanchez; Nancy Bunbury; Jeanne A. Mortimer; Luke A’Bear; Michael Betts; Rainer von Brandis; April J. Burt; Lorraine Cooke; Janske van de Crommenacker; Jock C. Currie; Naomi Doak; Frauke Fleischer-Dogley; et al. (Marine Biology, 2023)
Changes in marine ecosystems from human stressors, and concerns over how species will respond to these changes have emphasized the importance of understanding and monitoring crucial demographic parameters for population models. Long-lived, migratory, marine vertebrates such as sea turtles are particularly vulnerable to changes. Life-history parameters like growth-in-body size can be largely influenced by environmental processes which can impact population growth. We analyzed a 40-year (1981–2021) capture-mark-recapture dataset from the protected UNESCO World Heritage Site, Aldabra Atoll, Seychelles, to estimate key population parameters, including body growth, for immature green turtles ( Chelonia mydas ) and hawksbill turtles ( Eretmochelys imbricata ). Curved carapace length (CCL) range was 34.3–110.9 cm (mean ± SD: 51.0 ± 11.4 cm, n = 1191) for green turtles and 28.7–89.4 cm (47.7 ± 14.4 cm, n = 538) for hawksbill turtles. Recapture events, with an 11-month minimum period, revealed a mean annual growth rate of 3.2 ± 1.5 cm year −1 for green turtles (n = 75) and 2.8 ± 1.4 cm year −1 for hawksbill turtles (n = 110). Hawksbill turtles exhibited a non-monotonic growth rate while no significant growth-size relationship was detected for green turtles. Green turtle mean annual growth per 10-cm size class was highest in the larger size classes (50‒69.9 cm). Hawksbill turtle growth rate was highest in the larger size classes (50‒69.9 cm) then declined in the largest size class (70‒79.9 cm). Green turtles and hawksbill turtles may spend > 8 and 18 years, respectively, using Aldabra, Seychelles, as a foraging ground.

Carbon uptake in Eurasian boreal forests dominates the high‐latitude net ecosystem carbon budget - Jennifer D. Watts; Mary Farina; John S. Kimball; Luke D. Schiferl; Zhihua Liu; Kyle A. Arndt; Donatella Zona; Ashley Ballantyne; Eugénie S. Euskirchen; Frans‐Jan W. Parmentier; Manuel Helbig; Oliver Sonnentag; et al. (Global Change Biology, 2023)
Arctic‐boreal landscapes are experiencing profound warming, along with changes in ecosystem moisture status and disturbance from fire. This region is of global importance in terms of carbon feedbacks to climate, yet the sign (sink or source) and magnitude of the Arctic‐boreal carbon budget within recent years remains highly uncertain. Here, we provide new estimates of recent (2003–2015) vegetation gross primary productivity (GPP), ecosystem respiration ( R eco ), net ecosystem CO 2 exchange (NEE; R eco − GPP), and terrestrial methane (CH 4 ) emissions for the Arctic‐boreal zone using a satellite data‐driven process‐model for northern ecosystems (TCFM‐Arctic), calibrated and evaluated using measurements from >60 tower eddy covariance (EC) sites. We used TCFM‐Arctic to obtain daily 1‐km 2 flux estimates and annual carbon budgets for the pan‐Arctic‐boreal region. Across the domain, the model indicated an overall average NEE sink of −850 Tg CO 2 ‐C year −1 . Eurasian boreal zones, especially those in Siberia, contributed to a majority of the net sink. In contrast, the tundra biome was relatively carbon neutral (ranging from small sink to source). Regional CH 4 emissions from tundra and boreal wetlands (not accounting for aquatic CH 4 ) were estimated at 35 Tg CH 4 ‐C year −1 . Accounting for additional emissions from open water aquatic bodies and from fire, using available estimates from the literature, reduced the total regional NEE sink by 21% and shifted many far northern tundra landscapes, and some boreal forests, to a net carbon source. This assessment, based on in situ observations and models, improves our understanding of the high‐latitude carbon status and also indicates a continued need for integrated site‐to‐regional assessments to monitor the vulnerability of these ecosystems to climate change.

The timing of heat waves has multiyear effects on milkweed and its insect community - Olivia L. Cope; Luke N. Zehr; Anurag A. Agrawal; William C. Wetzel (Ecology, 2023)
Extreme heat events are becoming more frequent and intense as climate variability increases, and these events inherently vary in their timing. We predicted that the timing of a heat wave would determine its consequences for insect communities owing to temporal variation in the susceptibility of host plants to heat stress. We subjected common milkweed ( Asclepias syriaca ) plants to in‐field experimental heat waves to investigate how the timing of heat waves, both seasonally and relative to a biotic stressor (experimental herbivory), affected their ecological consequences. We found that heat waves had multiyear, timing‐specific effects on plant–insect communities. Early‐season heat waves led to greater and more persistent effects on plants and herbivore communities than late‐season heat waves. Heat waves following experimental herbivory had reduced consequences. Our results show that extreme climate events can have complex, lasting ecological effects beyond the year of the event—and that timing is key to understanding those effects.

Can spatial food web subsidies associated with river hydrology and lateral connectivity be detected using stable isotopes? - Kirk O. Winemiller; Marcelo C. Andrade; Caroline C. Arantes; Thethela Bokhutlo; Luke M. Bower; Eduardo R. Cunha; Friedrich W. Keppeler; Edwin O. López-Delgado; Yasmin Quintana; David E. Saenz; Kevin B. Mayes; Clint R. Robertson (Food Webs, 2023)

Spatio-temporal storm surge emulation using Gaussian Process techniques - Aikaterini P. Kyprioti; Christopher Irwin; Alexandros A. Taflanidis; Norberto C. Nadal-Caraballo; Madison C. Yawn; Luke A. Aucoin (Coastal Engineering, 2023)

Sensitivity analysis of severe accident calculations for the estimation of CANDU-specific OILs - Andrew C. Morreale; Manit D. Shah; Luke S. Lebel; Morgan J. Brown (Annals of Nuclear Energy, 2023)

Distinguishing borings and burrows in intraclasts: Evidence from the Cambrian (Furongian) of North China - Yazhou Hu; Luke C. Strotz; Dirk Knaust; Jiayue Wang; Yue Liang; Zhifei Zhang (Sedimentary Geology, 2023)

Prediction of fluid surge in partially-filled clean-bore and transverse baffled tanks of multiple designs under the United Nations Model Regulations - Zhemin Cai; Manudha T. Herath; Luke P. Djukic; Daniel C. Rodgers; Garth M.K. Pearce (Ocean Engineering, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Flexible carbon fiber based structural supercapacitor composites with solvate ionic liquid-epoxy solid electrolyte - Bhagya Dharmasiri; Filip Stojcevski; Ken Aldren S. Usman; Si Alex Qin; Joselito M. Razal; Egan H. Doeven; Paul S. Francis; Timothy U. Connell; Yanting Yin; Gunther G. Andersson; Ameya Borkar; Luke C. Henderson (Chemical Engineering Journal, 2023)

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Whole-Ecosystem Experiment Illustrates Short Timescale Hydrodynamic, Light, and Nutrient Control of Primary Production in a Terminal Slough - Luke C. Loken; Steven Sadro; Leah E. K. Lenoch; Paul R. Stumpner; Randy A. Dahlgren; Jon R. Burau; Erwin E. Van Nieuwenhuyse (Estuaries and Coasts, 2022)
Estuaries are among the most productive of aquatic ecosystems. Yet the collective understanding of patterns and drivers of primary production in estuaries is incomplete, in part due to complex hydrodynamics and multiple controlling factors that vary at a range of temporal and spatial scales. A whole-ecosystem experiment was conducted in a deep, pelagically dominated terminal channel of the Sacramento-San Joaquin Delta (California, USA) that seasonally appears to become nitrogen limited, to test whether adding calcium nitrate would stimulate primary productivity or increase phytoplankton density. Production did not respond consistently to fertilization, in part because nitrate and phytoplankton were dispersed away from the manipulated area within 1–3 days. Temporal and spatial patterns of gross primary production were more strongly related to stratification and light availability (i.e., turbidity) than nitrogen, highlighting the role of hydrodynamics in regulating system production. Similarly, chlorophyll was positively related not only to stratification but also to nitrogen—with a positive interaction—suggesting stratification may trigger nutrient limitation. The average rate of primary production (4.3 g O 2 m −2 d −1 ), metabolic N demand (0.023 mg N L −1 d −1 ), and ambient dissolved inorganic nitrogen concentration (0.03 mg N L −1 ) indicate that nitrogen can become limiting in time and space, especially during episodic stratification events when phytoplankton are isolated within the photic zone, or farther upstream where water clarity increases, dispersive flux decreases, and stratification is stronger and more frequent. The role of hydrodynamics in organizing habitat connectivity and regulating physical and chemical processes at multiple temporal and spatial scales is critical for determining resource availability and evaluating biogeochemical processes in estuaries.

Metabolic and physical function are improved with lifelong 15% calorie restriction in aging male mice - Emily C. Peters; Luke Safayan; Tyler J. Marx; Emily Ngu; Anastasiia Vasileva; India Zappia; William H. Powell; Frank A. Duca; Jennifer H. Stern (Biogerontology, 2022)
Chronic calorie restriction (CR) results in lengthened lifespan and reduced disease risk. Many previous studies have implemented 30–40% calorie restriction to investigate these benefits. The goal of our study was to investigate the effects of calorie restriction, beginning at 4 months of age, on metabolic and physical changes induced by aging. Male C57BL/6NCrl calorie restricted and ad libitum fed control mice were obtained from the National Institute on Aging (NIA) and studied at 10, 18, 26, and 28 months of age to better understand the metabolic changes that occur in response to CR in middle age and advanced age. Food intake was measured in ad libitum fed controls to assess the true degree of CR (15%) in these mice. We found that 15% CR decreased body mass and liver triglyceride content, improved oral glucose clearance, and increased all limb grip strength in 10- and 18-month-old mice. Glucose clearance in ad libitum fed 26- and 28-month-old mice is enhanced relative to younger mice but was not further improved by CR. CR decreased basal insulin concentrations in all age groups and improved insulin sensitivity and rotarod time to fall in 28-month-old mice. The results of our study demonstrate that even a modest reduction (15%) in caloric intake may improve metabolic and physical health. Thus, moderate calorie restriction may be a dietary intervention to promote healthy aging with improved likelihood for adherence in human populations.

Hybridisation and chloroplast capture between distinct Themeda triandra lineages in Australia - Luke T. Dunning; Jill K. Olofsson; Alexander S. T. Papadopulos; Samuel G. S. Hibdige; Oriane Hidalgo; Ilia J. Leitch; Paulo C. Baleeiro; Sinethemba Ntshangase; Nigel Barker; Richard W. Jobson (Molecular Ecology, 2022)
Ecotypes are distinct populations within a species that are adapted to specific environmental conditions. Understanding how these ecotypes become established, and how they interact when reunited, is fundamental to elucidating how ecological adaptations are maintained. This study focuses on Themeda triandra , a dominant grassland species across Asia, Africa and Australia. It is the most widespread plant in Australia, where it has distinct ecotypes that are usually restricted to either wetter and cooler coastal regions or the drier and hotter interior. We generate a reference genome for T. triandra and use whole genome sequencing for over 80 Themeda accessions to reconstruct the evolutionary history of T. triandra and related taxa. Organelle phylogenies confirm that Australia was colonized by T. triandra twice, with the division between ecotypes predating their arrival in Australia. The nuclear genome provides evidence of differences in the dominant ploidal level and gene‐flow among the ecotypes. In northern Queensland there appears to be a hybrid zone between ecotypes with admixed nuclear genomes and shared chloroplast haplotypes. Conversely, in the cracking claypans of Western Australia, there is cytonuclear discordance with individuals possessing the coastal chloroplast and interior clade nuclear genome. This chloroplast capture is potentially a result of adaptive introgression, with selection detected in the rpoC2 gene which is associated with water use efficiency. The reason that T. triandra is the most widespread plant in Australia appears to be a result of distinct ecotypic genetic variation and genome duplication, with the importance of each depending on the geographic scale considered.

Using Biological Responses to Monitor Freshwater Post-Spill Conditions over 3 years in Blacktail Creek, North Dakota, USA - Aїda M. Farag; David D. Harper; Isabelle M. Cozzarelli; Douglas B. Kent; Adam C. Mumford; Denise M. Akob; Travis Schaeffer; Luke R. Iwanowicz (Archives of Environmental Contamination and Toxicology, 2022)

Warmer and drier conditions have increased the potential for large and severe fire seasons across south‐eastern Australia - Luke Collins; Hamish Clarke; Michael F. Clarke; Sarah C. McColl Gausden; Rachael H. Nolan; Trent Penman; Ross Bradstock (Global Ecology and Biogeography, 2022)
Aim The aims were: (1) to identify the environmental drivers of interannual variation in wildfire extent and severity; (2) to examine temporal trends in climatic potential for large and severe wildfires; and (3) to assess whether environmental conditions experienced during the 2019–2020 mega‐fire season were anomalous. Location South‐eastern Australia. Time period 1953–2020. Major taxa studied Temperate forests. Methods We used satellite‐derived fire severity mapping from 1988 to 2020 to model the effects of drought, weather and fuels on the annual area burned and the proportion of the area burned that was impacted by high‐severity fire across four bioregions. Trends in wildfire extent and severity were then estimated from 1953 to 2020 using these derived models and gridded climate data to assess changes in climatic potential for large and severe wildfires. Estimates of wildfire extent and severity for the 2019–2020 fire season were then assessed against prior seasons (1953–2019). Results Annual area burned was positively related to the severity of seasonal drought and frequency of fire weather conditions that promote substantial daily fire growth. Wildfire severity was elevated in years with severe fire weather and increased with increasing antecedent drought in years without severe fire weather. Fuels had a lesser effect on wildfire extent and severity than climate. Potential fire extent and severity have increased over time in response to an increased severity of drought and worsening fire weather conditions. Estimates of wildfire extent and severity during the 2019–2020 fire season approached the upper extreme within each bioregion, owing to widespread extreme climatic conditions. Main conclusions The climatic potential for large and severe forest fires has increased across south‐eastern Australia since the 1950s, probably because of anthropogenic climate change. The magnitude and severity of the 2019–2020 fires reflected climatic conditions that are driving an increase in the size and severity of wildfires.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Global increase in methane production under future warming of lake bottom waters - Joachim Jansen; Richard Iestyn Woolway; Benjamin M. Kraemer; Clément Albergel; David Bastviken; Gesa A. Weyhenmeyer; Rafael Marcé; Sapna Sharma; Sebastian Sobek; Lars J. Tranvik; Marjorie Perroud; Malgorzata Golub; et al. (Global Change Biology, 2022)
Lakes are significant emitters of methane to the atmosphere, and thus are important components of the global methane budget. Methane is typically produced in lake sediments, with the rate of methane production being strongly temperature dependent. Local and regional studies highlight the risk of increasing methane production under future climate change, but a global estimate is not currently available. Here, we project changes in global lake bottom temperatures and sediment methane production rates from 1901 to 2099. By the end of the 21st century, lake bottom temperatures are projected to increase globally, by an average of 0.86–2.60°C under Representative Concentration Pathways (RCPs) 2.6–8.5, with greater warming projected at lower latitudes. This future warming of bottom waters will likely result in an increase in methane production rates of 13%–40% by the end of the century, with many low‐latitude lakes experiencing an increase of up to 17 times the historical (1970–1999) global average under RCP 8.5. The projected increase in methane production will likely lead to higher emissions from lakes, although the exact magnitude of the emission increase requires more detailed regional studies.

Genomic analyses show extremely perilous conservation status of African and Asiatic cheetahs ( Acinonyx jubatus ) - Stefan Prost; Ana Paula Machado; Julia Zumbroich; Lisa Preier; Sarita Mahtani‐Williams; Rene Meissner; Katerina Guschanski; Jaelle C. Brealey; Carlos Rodríguez Fernandes; Paul Vercammen; Luke T. B. Hunter; Alexei V. Abramov; et al. (Molecular Ecology, 2022)
We live in a world characterized by biodiversity loss and global environmental change. The extinction of large carnivores can have ramifying effects on ecosystems like an uncontrolled increase in wild herbivores, which in turn can have knock‐on impacts on vegetation regeneration and communities. Cheetahs ( Acinonyx jubatus ) serve important ecosystem functions as apex predators; yet, they are quickly heading towards an uncertain future. Threatened by habitat loss, human‐wildlife conflict and illegal trafficking, there are only approximately 7100 individuals remaining in nature. We present the most comprehensive genome‐wide analysis of cheetah phylogeography and conservation genomics to date, assembling samples from nearly the entire current and past species' range. We show that their phylogeography is more complex than previously thought, and that East African cheetahs ( A. j. raineyi ) are genetically distinct from Southern African individuals ( A. j. jubatus ), warranting their recognition as a distinct subspecies. We found strong genetic differentiation between all classically recognized subspecies, thus refuting earlier findings that cheetahs show only little differentiation. The strongest differentiation was observed between the Asiatic and all the African subspecies. We detected high inbreeding in the Critically Endangered Iranian ( A. j. venaticus ) and North‐western ( A. j. hecki ) subspecies, and show that overall cheetahs, along with snow leopards, have the lowest genome‐wide heterozygosity of all the big cats. This further emphasizes the cheetah's perilous conservation status. Our results provide novel and important information on cheetah phylogeography that can support evidence‐based conservation policy decisions to help protect this species. This is especially relevant in light of ongoing and proposed translocations across subspecies boundaries, and the increasing threats of illegal trafficking.

Brassicaceae host plants mask the feedback from the previous year's soil history on bacterial communities, except when they experience drought - Andrew J. C. Blakney; Luke D. Bainard; Marc St‐Arnaud; Mohamed Hijri (Environmental Microbiology, 2022)
Summary Soil history operates through time to influence the structure and biodiversity of soil bacterial communities. Examining how different soil histories endure will help clarify the rules of bacterial community assembly. In this study, we established three different soil histories in field trials; the following year these plots were planted with five different Brassicaceae species. We hypothesized that the previously established soil histories would continue to structure the subsequent Brassicaceae bacterial root and rhizosphere communities. We used a MiSeq 16S rRNA metabarcoding strategy to determine the impact of different soil histories on the structure and biodiversity of the bacterial root and rhizosphere communities from the five different Brassicaceae host plants. We found that the Brassicaceae hosts were consistently significant factors in structuring the bacterial communities. Four host plants ( Sinapis alba , Brassica napus , B . juncea , B . carinata ) formed similar bacterial communities, regardless of different soil histories. Camelina sativa host plants structured phylogenetically distinct bacterial communities compared to the other hosts, particularly in their roots. Soil history established the previous year was only a significant factor for bacterial community structure when the feedback of the Brassicaceae host plants was weakened, potentially due to limited soil moisture during a dry year. Understanding how soil history is involved in the structure and biodiversity of bacterial communities through time is a limitation in microbial ecology and is required for employing microbiome technologies in improving agricultural systems.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Human and animal subsistence in northern Iberia during the Late Chalcolithic-Bronze Age: biomolecular insights from Muela de Borja, Ebro Valley - Laura C. Viñas-Caron; Isidro Aguilera; Tina Jakob; Joe W. Walser; Luke Spindler; Maria Fontanals-Coll; Michelle Alexander (Archaeological and Anthropological Sciences, 2022)

Short‐term movement dynamics of the world’s largest sea cucumbers (genus Thelenota ) - Benjamin C. T. Gray; Luke A. Calvert; Steven W. Purcell (Marine Ecology, 2022)
Movement studies on marine animals can inform conservation and fishery management planning through data that explain likely dispersals and home‐ranging behaviours. Relatively few studies are documented for exploited marine invertebrates, despite many having a high ecological and commercial value. We assessed the diurnal movement patterns of Thelenota ananas and Thelenota anax , the world's largest sea cucumbers, which are highly exploited throughout the Indo‐Pacific. At two coral reef sites at Lizard Island, northern Australia, we tracked the 2‐hourly displacement of individuals from morning to nightfall. Movement of T . ananas was more reef‐associated and tortuous than T . anax . Displacement rates averaged 80 cm h −1 (±8 SE) for T . ananas and 73 cm h −1 (±20) for T . anax . Body size accounted for half of the variation in displacement for T . ananas . Mobility peaked in the late afternoon or early evening for both species, and animals tended to reverse their direction of travel after midday. The data reflect a pattern of animals meandering out from their reef shelters onto sandy lagoon floors to forage, before returning to the reefs. This empirical evidence offers further support that these holothuroids contribute to the formation of “reef halos”. The exceptionally high movement rates and patterns found in this study should inform the design of spatial management measures.

Climate variability and aridity modulate the role of leaf shelters for arthropods: A global experiment - Gustavo Q. Romero; Thiago Gonçalves‐Souza; Tomas Roslin; Robert J. Marquis; Nicholas A.C. Marino; Vojtech Novotny; Tatiana Cornelissen; Jerome Orivel; Shen Sui; Gustavo Aires; Reuber Antoniazzi; Wesley Dáttilo; et al. (Global Change Biology, 2022)
Current climate change is disrupting biotic interactions and eroding biodiversity worldwide. However, species sensitive to aridity, high temperatures, and climate variability might find shelter in microclimatic refuges, such as leaf rolls built by arthropods. To explore how the importance of leaf shelters for terrestrial arthropods changes with latitude, elevation, and climate, we conducted a distributed experiment comparing arthropods in leaf rolls versus control leaves across 52 sites along an 11,790 km latitudinal gradient. We then probed the impact of short‐ versus long‐term climatic impacts on roll use, by comparing the relative impact of conditions during the experiment versus average, baseline conditions at the site. Leaf shelters supported larger organisms and higher arthropod biomass and species diversity than non‐rolled control leaves. However, the magnitude of the leaf rolls’ effect differed between long‐ and short‐term climate conditions, metrics (species richness, biomass, and body size), and trophic groups (predators vs. herbivores). The effect of leaf rolls on predator richness was influenced only by baseline climate, increasing in magnitude in regions experiencing increased long‐term aridity, regardless of latitude, elevation, and weather during the experiment. This suggests that shelter use by predators may be innate, and thus, driven by natural selection. In contrast, the effect of leaf rolls on predator biomass and predator body size decreased with increasing temperature, and increased with increasing precipitation, respectively, during the experiment. The magnitude of shelter usage by herbivores increased with the abundance of predators and decreased with increasing temperature during the experiment. Taken together, these results highlight that leaf roll use may have both proximal and ultimate causes. Projected increases in climate variability and aridity are, therefore, likely to increase the importance of biotic refugia in mitigating the effects of climate change on species persistence.

Combined Effects of Hydrological Drought and Reduced Food Availability on the Decline of the Little Penguins in South Australia - Diane Colombelli-Négrel; Darfiana Nur; Hannah C. C. Auricht; Kenneth D. Clarke; Luke M. Mosley; Peter Dann (Frontiers in Marine Science, 2022)
Droughts in many regions of the world are increasing in frequency and severity which, coupled with effects from anthropogenic water extraction and diversion, are reducing river discharges. Yet to date, few studies have investigated the impacts of hydrological droughts (i.e., reduced river outflows to the ocean) on seabirds. Here, we examined the consequences of the “Millennium Drought” on the local decline of an iconic Australian seabird, the little penguin ( Eudyptula minor ). We analysed monthly and annual penguin numbers in relation to river outflow, rainfall, the characteristics of the coastal waters (sea surface temperatures and chlorophyll- a concentrations), and local abundance of key predators and prey species. We found a negative association between monthly penguin numbers and both sea surface temperatures and river outflow. Annual penguin numbers were positively associated with southern garfish numbers (our local indicator of food availability) but negatively associated with annual chlorophyll- a concentrations. Our findings emphasizing the need for further research into the effect of hydrological droughts on seabird populations and for improved river management that account for potential downstream impacts on the coastal environment receiving freshwater from rivers.

Correction to: Exploring the missing heritability in subjects with hearing loss, enlarged vestibular aqueducts, and a single or no pathogenic SLC26A4 variant - Jeroen J. Smits; Suzanne E. de Bruijn; Cornelis P. Lanting; Jaap Oostrik; Luke O’Gorman; Tuomo Mantere; M. F. van Dooren; S. G. Kant; H. H. W. de Gier; E. H. Hoefsloot; M. P. van der Schroeff; L. J. C. Rotteveel; et al. (Human Genetics, 2022)

Exploring the missing heritability in subjects with hearing loss, enlarged vestibular aqueducts, and a single or no pathogenic SLC26A4 variant - Jeroen J. Smits; Suzanne E. de Bruijn; Cornelis P. Lanting; Jaap Oostrik; Luke O’Gorman; Tuomo Mantere; M. F. van Dooren; S. G. Kant; H. H. W. de Gier; E. H. Hoefsloot; M. P. van der Schroeff; L. J. C. Rotteveel; et al. (Human Genetics, 2022)
Pathogenic variants in SLC26A4 have been associated with autosomal recessive hearing loss (arHL) and a unilateral or bilateral enlarged vestibular aqueduct (EVA). SLC26A4 is the second most frequently mutated gene in arHL. Despite the strong genotype–phenotype correlation, a significant part of cases remains genetically unresolved. In this study, we investigated a cohort of 28 Dutch index cases diagnosed with HL in combination with an EVA but without (M0) or with a single (M1) pathogenic variant in SLC26A4 . To explore the missing heritability, we first determined the presence of the previously described EVA-associated haplotype (Caucasian EVA (CEVA)), characterized by 12 single nucleotide variants located upstream of SLC26A4 . We found this haplotype and a delimited V1-CEVA haplotype to be significantly enriched in our M1 patient cohort (10/16 cases). The CEVA haplotype was also present in two M0 cases (2/12). Short- and long-read whole genome sequencing and optical genome mapping could not prioritize any of the variants present within the CEVA haplotype as the likely pathogenic defect. Short-read whole-genome sequencing of the six M1 cases without this haplotype and the two M0/CEVA cases only revealed previously overlooked or misinterpreted splice-altering SLC26A4 variants in two cases, who are now genetically explained. No deep-intronic or structural variants were identified in any of the M1 subjects. With this study, we have provided important insights that will pave the way for elucidating the missing heritability in M0 and M1 SLC26A4 cases. For pinpointing the pathogenic effect of the CEVA haplotype, additional analyses are required addressing defect(s) at the RNA, protein, or epigenetic level.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Oviposition behaviour and emergence through time of the small blue butterfly (Cupido minimus) in a nature reserve in Bedfordshire, UK - Esme Ashe-Jepson; Andrew J. Bladon; Greg Herbert; Gwen E. Hitchcock; Richard Knock; Colin B. H. Lucas; Sarah H. Luke; Edgar C. Turner (Journal of Insect Conservation, 2022)
Abstract Climate change affects butterflies in many ways, influencing the timing of emergence and reproduction, habitat preferences, and behaviour. The small blue ( Cupido minimus Fuessley, 1775) is highly specialised in its host plant requirements, feeding on the seeds of a single species, kidney vetch ( Anthyllis vulneraria ), on which the larvae occur singly to avoid cannibalism. The butterfly is likely to be vulnerable to temperature-related changes in oviposition, adult emergence, and host plant flowering times, and is, therefore, a good model species for investigating climate change-related impacts. Using 26 years of data from the national UK Butterfly Monitoring Scheme (1993–2019) from one nature reserve, and 4 years of targeted egg searches (2006, 2007, 2008, 2020) from three reserves in Bedfordshire, UK, we investigated the effects of local temperature on small blue emergence date and total abundance, whether flowerhead or local environmental characteristics predicted small blue oviposition behaviour, and whether this changed between years. Small blue adults emerged on earlier dates over time, and earlier in years with higher maximum February temperatures. Total adult abundance was not predicted by monthly temperatures or total abundance in the previous year. Oviposition behaviour was broadly consistent across years, with egg presence more likely and egg abundance higher on kidney vetch flowerheads that were taller than the surrounding vegetation, and surrounded by taller vegetation and fewer mature flowerheads. The effect of solar radiation differed between years, with a negative effect on the probability of egg presence in 2007 and 2008, but a positive effect in 2020. Egg abundance per flowerhead was highly variable between years, with 2006 having four times more eggs per flowerhead than other years. This was likely driven by high adult abundance in 2006, which could have increased competition for flowerheads. Implications for insect conservation Our results indicate that management for greater availability of taller kidney vetch amongst taller vegetation would encourage small blue oviposition on a greater number of flowerheads, providing a possible means of reducing competition and increasing larval survival, and that this would be effective despite variation in adult abundance between years. The high level of competition we observed in the year with the highest adult abundance indicates that higher numbers of host plants should be encouraged to reduce competition and larval cannibalism in peak years, increasing the likelihood of long-term population persistence and growth.

Fish scale shape follows predictable patterns of variation based on water column position, body size, and phylogeny - Jessica T. Grady; Luke M. Bower; C. M. Gienger; Rebecca E. Blanton (Evolutionary Ecology, 2022)

Spatial pattern analysis of line‐segment data in ecology - Luke A. Yates; Barry W. Brook; Jessie C. Buettel (Ecology, 2022)
The spatial analysis of linear features (lines and curves) is a challenging and rarely attempted problem in ecology. Existing methods are typically expressed in abstract mathematical formalism, making it difficult to assess their relevance and transferability into an ecological setting. We introduce a set of concrete and accessible methods to analyze the spatial patterning of line‐segment data. The methods include Monte Carlo techniques based on a new generalization of Ripley's ‐function and a class of line‐segment processes that can be used to specify parametric models: parameters are estimated using maximum likelihood and models compared using information‐theoretic principles. We apply the new methods to fallen tree (dead log) data collected from two 1‐ha Australian tall eucalypt forest plots. Our results show that the spatial pattern of the fallen logs is best explained by plot‐level spatial heterogeneity in combination with a slope‐dependent nonuniform distribution of fallen‐log orientations. These methods are of a general nature and are applicable to any line‐segment data. In the context of forest ecology, the integration of fallen logs as linear structural features in a landscape with the point locations of living trees, and a quantification of their interactions, can yield new insights into the functional and structural role of tree fall in forest communities and their enduring post‐mortem ecological legacy as spatially distributed decomposing logs.

Submersibles Greatly Enhance Research on the Diversity of Deep-Reef Fishes in the Greater Caribbean - D. Ross Robertson; Luke Tornabene; Claudia C. Lardizabal; Carole C. Baldwin (Frontiers in Marine Science, 2022)
Understanding the diversity and ecology of deep-reef fishes is challenging. Due to intensive and widely dispersed sampling, the Greater Caribbean (GC) fauna of species found on shallow reefs is much better characterized than the fauna of deep-reef species restricted to mesophotic (40–130 m) and rariphotic (130–300 m) depths. Our knowledge about deep-reef fishes is based on ship-board sampling and the recent use of rebreather diving, remotely operated vehicles (ROVs), baited remote underwater videos, and crewed submersibles. Submersible research on GC deep-reef fishes began in the 1960s and has flourished over the last decade through research by the Smithsonian Institution’s Deep Reef Observation Project (DROP). Here we quantify the contribution of submersible research, particularly the surge by DROP, to our understanding of the diversity of the deep-reef fish fauna of the GC. We compared shallow- and deep-reef fish faunas of three GC sites subjected to DROP research to faunas of three sites without such research. DROP increased the size of the deep faunas at three islands ∼9-fold, and they have deep-reef faunas ∼2–4 times the size of those of the other three sites. Those deep-reef faunas have high proportions of small cryptobenthic fishes, which also represent a major component of shallow faunas. That research increased the rate of discovery (collection) of new species of deep-reef fishes ∼6-fold and accounts for 31% of the deep-reef species first discovered within the GC. Substantial numbers of new species at each of the three DROP islands were not found at the other two. This indicates that other parts of the GC likely harbor many undetected deep-reef fishes, and that the size of the deep-reef fauna of the GC is significantly underestimated. These results show that small research submersibles are versatile, highly productive tools for deep-reef studies. They allow long-duration dives at any depth, while offering unparalleled views of their surroundings to study the ecology of deep-reef fishes (e.g., DROP’s definition of the rariphotic assemblage from fish depth distributions). Submersibles can efficiently collect reef fishes of a broad range of taxa, ecotypes and sizes, leading to a more comprehensive understanding of the regional GC deep-reef fish fauna.

Contrasting climate velocity impacts in warm and cool locations show that effects of marine warming are worse in already warmer temperate waters - Philina A. English; Eric J. Ward; Christopher N. Rooper; Robyn E. Forrest; Luke A. Rogers; Karen L. Hunter; Andrew M. Edwards; Brendan M. Connors; Sean C. Anderson (Fish and Fisheries, 2022)
Species responses to climate change are often measured at broad spatiotemporal scales, which can miss the fine‐scale changes that are most relevant to conservation and fisheries management. We develop a scaleable geostatistical approach to assess how juvenile and adult fish distributions have been shaped by changes in bottom temperature and dissolved oxygen over a recent decade of warming in the northeast Pacific. Across 38 demersal fishes, biomass trends were associated negatively with warming and positively with dissolved oxygen, but when trends in both biomass and climate were converted to velocities—the speed and direction a population would have to move to maintain consistent conditions—the effect of temperature change differed depending on local conditions. In the warmest locations, warming velocities were associated with negative biotic velocities for 19 of 69 species‐maturity combinations, and yet were almost always associated with stable or positive biotic velocities in the coolest locations (64 of 69). These spatially consistent biomass declines (negative biotic velocities) in the warmest locations and increases in cooler locations suggest a redistribution of species with the potential for new ecological and fisheries interactions. After controlling for temperature, the more spatially consistent effects of dissolved oxygen were often negative, suggesting a mechanism other than hypoxia avoidance—potentially changes in primary production. Our approach identifies the species and locations that are most sensitive to observed changes in the environment at any scale, thus facilitating future vulnerability assessments.

Habitat value of bivalve shellfish and seaweed aquaculture for fish and invertebrates: Pathways, synthesis and next steps - Seth J. Theuerkauf; Luke T. Barrett; Heidi K. Alleway; Barry A. Costa‐Pierce; Adam St. Gelais; Robert C. Jones (Reviews in Aquaculture, 2022)
Aquaculture can have negative environmental impacts, adding to the suite of anthropogenic stressors that challenge coastal ecosystems. However, a growing body of scientific evidence indicates that the commercial cultivation of bivalve shellfish and seaweed can deliver valuable ecosystem goods and services, including provision of new habitats for fish and mobile invertebrate species. We completed a systematic literature review of studies focused on understanding habitat‐related interactions associated with bivalve and seaweed aquaculture, and a brief meta‐analysis of 65 studies to evaluate fish and mobile macroinvertebrate populations at farms and reference sites. Bivalve and seaweed aquaculture were associated with higher abundance ( n = 59, range: 0.05× to 473×, median lnRR = 0.67) and species richness ( n = 29, range: 0.68× to 4.3×, median lnRR = 0.13) of wild, mobile macrofauna. Suspended or elevated mussel and oyster culture yielded the largest increases in wild macrofaunal abundance and species richness. We describe the major mechanisms and pathways by which bivalve and seaweed aquaculture may positively influence the structure and function of faunal communities—including provision of structured habitat, provision of food resources and enhanced reproduction and recruitment—and identify the role of the species cultivated and cultivation gear in affecting habitat value. Given the continued deterioration of coastal habitats and increasing investments into their restoration, understanding how industry activities such as aquaculture can be designed to deliver food within ecological limits and have positive influences on ecosystem goods and services is essential in ensuring ecological, social and economic objectives can be achieved.

Vapor pressure deficit helps explain biogenic volatile organic compound fluxes from the forest floor and canopy of a temperate deciduous forest - Paul C. Stoy; Amy M. Trowbridge; Mario B. Siqueira; Livia Souza Freire; Richard P. Phillips; Luke Jacobs; Susanne Wiesner; Russell K. Monson; Kimberly A. Novick (Oecologia, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Altered functional network connectivity and working memory dysfunction in adolescents with epilepsy - Jennifer Vannest; Rupa Radhakrishnan; Ana M. Gutierrez-Colina; Shari L. Wade; Thomas Maloney; Angela Combs; Luke Turnier; Shelby Merder; Mekibib Altaye; Tzipi-Horowitz-Kraus; Avani C. Modi (Brain Imaging and Behavior, 2021)

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

Scaling up private land conservation to meet recovery goals for grassland birds - David C. Pavlacky; Christian A. Hagen; Anne M. Bartuszevige; Rich Iovanna; Thomas Luke George; David E. Naugle (Conservation Biology, 2021)
Long‐term population declines have elevated recovery of grassland avifauna to among the highest conservation priorities in North America. Because most of the Great Plains is privately owned, recovery of grassland bird populations depends on voluntary conservation with strong partnerships between private landowners and resource professionals. Despite large areas enrolled in voluntary practices through U.S. Department of Agriculture's Lesser Prairie‐chicken ( Tympanuchus pallidicinctus ) Initiative (LPCI), the effectiveness of Farm Bill investments for meeting wildlife conservation goals remains an open question. Our objectives were to evaluate extents to which Conservation Reserve Program (CRP) and LPCI‐grazing practices influence population densities of grassland birds; estimate relative contributions of practices to regional bird populations; and evaluate percentages of populations conserved relative to vulnerability of species. We designed a large‐scale impact‐reference study and used the Integrated Monitoring in Bird Conservation Regions program to evaluate bird population targets of the Playa Lakes Joint Venture. We used point transect distance sampling to estimate density and population size for 35 species of grassland birds on private lands enrolled in native or introduced CRP plantings and LPCI‐prescribed grazing. Treatment effects indicated CRP plantings increased densities of three grassland obligates vulnerable to habitat loss, and LPCI grazing increased densities of four species requiring heterogeneity in dense, tall‐grass structure ( α = 0.1). Population estimates in 2016 indicated the practices conserved breeding habitat for 4.5 million birds (90% CI: 4.0–5.1), and increased population sizes of 16 species , totaling 1.8 million birds (CI: 1.4–2.4). Conservation practices on private land benefited the most vulnerable grassland obligate species (AIC c weight = 0.53). By addressing habitat loss and degradation in agricultural landscapes, conservation on private land provides a solution to declining avifauna of North America and scales up to meet population recovery goals for the most imperiled grassland birds.

Assessing the Resiliency of Salt Marshes Under Increasing Nitrogen Loading - Sarah C. Crosby; Nicole C. Spiller; Devan S. Healy; Lauren Brideau; Luke M. Stewart; Jamie M.P. Vaudrey; Kasey E. Tietz; Peter J. Fraboni (Estuaries and Coasts, 2021)

Warm winters and cool springs negatively influence recruitment of Atlantic salmon ( Salmo salar L.) in a southern England chalk stream - Jessica E. Marsh; Rasmus B. Lauridsen; William D. Riley; Olivia M. Simmons; Céline Artero; Luke J. Scott; William R. C. Beaumont; William A. Beaumont; John Davy‐Bowker; Thomas Lecointre; Dylan E. Roberts; Stephen D. Gregory (Journal of Fish Biology, 2021)
Previous work suggests that juvenile salmon recruitment in rain‐fed rivers is negatively influenced by warm and wet winters and cool springs. We tested whether this is generally applicable to a southern England chalk stream characterized by comparatively stable discharges and temperatures. We found that warm spawning and cool emergence temperatures negatively influenced juvenile recruitment between 2015 and 2020. Together these findings suggest an ability to predict juvenile productivity from water temperature records around spawning and fry emergence, thereby allowing time for management interventions in years of unfavourable temperatures.

Environmental controls on holocene reef development along the eastern brazilian margin - Belinda Dechnik; Alex C. Bastos; Laura S. Vieira; Jody M. Webster; Stewart Fallon; Yusuke Yokoyama; Juan-Carlos Braga; Manuel A. Pereira; Luke Nothdurft; Kelsey Sanborn; Rodrigo L. Moura; Gilberto Amado-filho (Coral Reefs, 2021)

New insights into the mechanisms underlying 5-fluorouracil-induced intestinal toxicity based on transcriptomic and metabolomic responses in human intestinal organoids - Daniela Rodrigues; Terezinha de Souza; Luke Coyle; Matteo Di Piazza; Bram Herpers; Sofia Ferreira; Mian Zhang; Johanna Vappiani; Daniel C. Sévin; Attila Gabor; Anthony Lynch; Seung-Wook Chung; et al. (Archives of Toxicology, 2021)
5-Fluorouracil (5-FU) is a widely used chemotherapeutical that induces acute toxicity in the small and large intestine of patients. Symptoms can be severe and lead to the interruption of cancer treatments. However, there is limited understanding of the molecular mechanisms underlying 5-FU-induced intestinal toxicity. In this study, well-established 3D organoid models of human colon and small intestine (SI) were used to characterize 5-FU transcriptomic and metabolomic responses. Clinically relevant 5-FU concentrations for in vitro testing in organoids were established using physiologically based pharmacokinetic simulation of dosing regimens recommended for cancer patients, resulting in exposures to 10, 100 and 1000 µM. After treatment, different measurements were performed: cell viability and apoptosis; image analysis of cell morphological changes; RNA sequencing; and metabolome analysis of supernatant from organoids cultures. Based on analysis of the differentially expressed genes, the most prominent molecular pathways affected by 5-FU included cell cycle, p53 signalling, mitochondrial ATP synthesis and apoptosis. Short time-series expression miner demonstrated tissue-specific mechanisms affected by 5-FU, namely biosynthesis and transport of small molecules, and mRNA translation for colon; cell signalling mediated by Rho GTPases and fork-head box transcription factors for SI. Metabolomic analysis showed that in addition to the effects on TCA cycle and oxidative stress in both organoids, tissue-specific metabolic alterations were also induced by 5-FU. Multi-omics integration identified transcription factor E2F1, a regulator of cell cycle and apoptosis, as the best key node across all samples. These results provide new insights into 5-FU toxicity mechanisms and underline the relevance of human organoid models in the safety assessment in drug development.

Steps to diversify priority‐setting research in conservation: reflections on de Gracia 2021 - Tommaso Jucker; Tatsuya Amano; Alexandra Bell; Emma E. Garnett; Jan Laurens Geffert; Miriam K. Guth; Andrew Hacket‐Pain; Sarah H. Luke; Hannah S. Mumby; Matheus Nunes; Tim Rademacher; David C. Rose; et al. (Conservation Biology, 2021)

The killer within: Endogenous bacteria accelerate oyster mortality during sustained anoxia - Michael R. S. Coffin; Jeff C. Clements; Luc A. Comeau; Thomas Guyondet; Michelle Maillet; Laura Steeves; Keryn Winterburn; José M. F. Babarro; Martin A. Mallet; Rémy Haché; Luke A. Poirier; Saswati Deb; et al. (Limnology and Oceanography, 2021)
Sustained periods of anoxia, driven by eutrophication, threaten coastal marine systems and can lead to mass mortalities of even resilient animals such as bivalves. While mortality rates under anoxia are well‐studied, the specific mechanism(s) of mortality are less clear. We used a suite of complementary techniques (LT50, histology, 16S rRNA amplicon sequencing, and valvometry) to show that the proliferation of anaerobic bacteria within eastern oysters ( Crassostrea virginica ) accelerates mortality rate under anoxic conditions. Manipulative laboratory experiments revealed that oyster survival under anoxic conditions was halved when bacteria were present compared to when they were excluded by the broad‐spectrum antibiotic chloramphenicol. Histological assessments supported this mechanism and showed infiltration of bacteria in oysters that were not treated with antibiotics compared to a general lack of bacteria when oysters were treated with antibiotics. 16S rRNA amplicon sequencing failed to identify any particular genera of bacteria responsible for mortality, rather a diversity of endogenous anaerobic and/or sulfate‐reducing bacteria were common among oysters. In addition, monitoring of oyster valve gaping behavior in the field revealed that oysters showed remarkable valve closure synchrony when first exposed to anoxia. However, oysters periodically opened throughout anoxia/hypoxia in both the lab and field, suggesting that the infiltration of exogenous bacteria from the environment may also influence mortality rates under natural settings. Coupled with previous studies, we posit that mass mortality events in a wide range of coastal bivalves are likely the result of co‐morbidity from asphyxiation and bacterial processes.

Automated methods for efficient and accurate electroretinography - Luke T. Havens; Alexandra C. N. Kingston; Daniel I. Speiser (Journal of Comparative Physiology A, 2021)

Submarine groundwater discharge drives nitrous oxide source/sink dynamics in a metropolitan estuary - Michael J. Reading; Douglas R. Tait; Damien T. Maher; Luke C. Jeffrey; Rogger E. Correa; James P. Tucker; Haile A. Shishaye; Isaac R. Santos (Limnology and Oceanography, 2021)
Coastal waterways can be significant sources of the potent greenhouse gas nitrous oxide (N 2 O) due to nitrogen inputs and eutrophication. Here, we quantify groundwater derived N 2 O inputs and atmospheric emissions within a modified urban embayment (Sydney Harbour, Australia). Overall, we found low N 2 O saturation (91–171%) and air–water fluxes (−2.2 to 24.6 μ mol m −2 d −1 ). Concentrations were highest in upstream brackish areas and a commercial/industrial subembayment. Dissolved inorganic nitrogen concentrations were low and inversely correlated to N 2 O throughout the harbor. N 2 O surface water dynamics were apparently driven by saline submarine groundwater discharge, as quantified by the radioisotope tracer radon‐222. Groundwater discharge was highest within the embayments and mangrove‐lined upper estuary. While groundwater was a net N 2 O source to surface waters, two upstream sub‐embayments featured groundwater N 2 O concentrations lower than surface water, suggesting a sink driven by surface waters recirculating in intertidal sediments. Surface‐water N 2 O was undersaturated within one upstream embayment, likely due to N 2 O consumption within sediments. Contrastingly, the downstream embayments featured higher groundwater N 2 O and accounted for 45% ± 21% of the groundwater N 2 O flux. Sydney Harbour was a net source of N 2 O to the atmosphere (mean 0.6 ± 0.3 μ mol m −2 d −1 ) with larger N 2 O fluxes occurring from relatively small areas. N 2 O emissions (expressed in CO 2 equilivents) were equivalent to 17% of CO 2 emission estimates from previous studies. The low N 2 O emissions in Sydney Harbour contrast with other modified estuaries which often emit higher N 2 O fluxes due to larger nitrogen inputs.

Mechanisms matter: Predicting the ecological impacts of global change - Victoria L. Boult; Luke C. Evans (Global Change Biology, 2021)
The ability of mechanistic models to reliably extrapolate to novel conditions could position them as the gold standard in understanding the impacts of global change, but exactly how mechanistic models can be used most effectively remains to be determined. In this issue, Desforges et al. present a mechanistic physiological model to understand the drivers of muskox population dynamics. We took this as an opportunity to discuss the potential for, and challenges of, using mechanistic models to predict ecological responses to environmental change.

Improving the Accuracy of Krill Target Strength Using a Shape Catalog - Fiona Bairstow; Sven Gastauer; Luke Finley; Tom Edwards; C. Tom A. Brown; So Kawaguchi; Martin J. Cox (Frontiers in Marine Science, 2021)
Antarctic krill are subject to precautionary catch limits, based on biomass estimates, to ensure human activities do not adversely impact their important ecological role. Accurate target strength models of individual krill underpin biomass estimates. These models are scaled using measured and estimated distributions of length and orientation. However, while the length distribution of a krill swarm is accessible from net samples, there is currently limited consensus on the method for estimating krill orientation distribution. This leads to a limiting factor in biomass calculations. In this work, we consider geometric shape as a variable in target strength calculations and describe a practical method for generating a catalog of krill shapes. A catalog of shapes produces a more variable target strength response than an equivalent population of a scaled generic shape. Furthermore, using a shape catalog has the greatest impact on backscattering cross-section (linearized target strength) where the dominant scattering mechanism is mie scattering, irrespective of orientation distribution weighting. We suggest that shape distributions should be used in addition to length and orientation distributions to improve the accuracy of krill biomass estimates.

Markov dependencies in the song syntax of Hermit Thrush (Catharus guttatus) - Luke C. McLean; Sean P. Roach (Journal of Ornithology, 2021)

Hydrological, geochemical and land use drivers of greenhouse gas dynamics in eleven sub-tropical streams - Luke F. Andrews; Praktan D. Wadnerkar; Shane A. White; Xiaogang Chen; Rogger E. Correa; Luke C. Jeffrey; Isaac R. Santos (Aquatic Sciences, 2021)
Greenhouse gas (GHG) emissions from freshwater streams are poorly quantified in sub-tropical climates, especially in the southern hemisphere where land use is rapidly changing. Here, we examined the distribution, potential drivers, and emissions of carbon dioxide (CO 2 ), nitrous oxide (N 2 O) and methane (CH 4 ) from eleven Australian freshwater streams with varying catchment land uses yet similar hydrology, geomorphology, and climate. These sub-tropical streams were a source of CO 2 (74 ± 39 mmol m −2 day −1 ), CH 4 (0.04 ± 0.06 mmol m −2 day −1 ), and N 2 O (4.01 ± 5.98 µmol m −2 day −1 ) to the atmosphere. CO 2 accounted for ~ 97% of all CO 2 -equivalent emissions with CH 4 (~ 1.5%) and N 2 O (~ 1.5%) playing a minor role. Episodic rainfall events drove changes in stream GHG due to the release of soil NO x (nitrate + nitrite) and dissolved organic carbon (DOC). Groundwater discharge as traced by radon ( 222 Rn, a natural groundwater tracer) was not an apparent source of CO 2 and CH 4 , but was a source of N 2 O in both agricultural and forest catchments. Land use played a subtle role on greenhouse gas dynamics. CO 2 and CH 4 increased with catchment forest cover during the wet period, while N 2 O and CH 4 increased with agricultural catchment area during the dry period. Overall, this study showed how DOC and NO x , land use, and rainfall events interact to drive spatial and temporal dynamics of GHG emissions in sub-tropical streams using multiple linear regression modelling. Increasing intensive agricultural land use will likely decrease regional CO 2 and CH 4 emissions, but increase N 2 O.

Individual behavioural traits not social context affects learning about novel objects in archerfish - Nick A. R. Jones; Helen C. Spence-Jones; Mike Webster; Luke Rendell (Behavioral Ecology and Sociobiology, 2021)
Learning can enable rapid behavioural responses to changing conditions but can depend on the social context and behavioural phenotype of the individual. Learning rates have been linked to consistent individual differences in behavioural traits, especially in situations which require engaging with novelty, but the social environment can also play an important role. The presence of others can modulate the effects of individual behavioural traits and afford access to social information that can reduce the need for ‘risky’ asocial learning. Most studies of social effects on learning are focused on more social species; however, such factors can be important even for less-social animals, including non-grouping or facultatively social species which may still derive benefit from social conditions. Using archerfish, Toxotes chatareus , which exhibit high levels of intra-specific competition and do not show a strong preference for grouping, we explored the effect of social contexts on learning. Individually housed fish were assayed in an ‘open-field’ test and then trained to criterion in a task where fish learnt to shoot a novel cue for a food reward—with a conspecific neighbour visible either during training, outside of training or never (full, partial or no visible presence). Time to learn to shoot the novel cue differed across individuals but not across social context. This suggests that social context does not have a strong effect on learning in this non-obligatory social species; instead, it further highlights the importance that inter-individual variation in behavioural traits can have on learning. Significance statement Some individuals learn faster than others. Many factors can affect an animal’s learning rate—for example, its behavioural phenotype may make it more or less likely to engage with novel objects. The social environment can play a big role too—affecting learning directly and modifying the effects of an individual’s traits. Effects of social context on learning mostly come from highly social species, but recent research has focused on less-social animals. Archerfish display high intra-specific competition, and our study suggests that social context has no strong effect on their learning to shoot novel objects for rewards. Our results may have some relevance for social enrichment and welfare of this increasingly studied species, suggesting there are no negative effects of short- to medium-term isolation of this species—at least with regards to behavioural performance and learning tasks.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Atmospheric stilling and warming air temperatures drive long‐term changes in lake stratification in a large oligotrophic lake - Jonathan T. Stetler; Scott Girdner; Jeremy Mack; Luke A. Winslow; Taylor H. Leach; Kevin C. Rose (Limnology and Oceanography, 2021)
Lake surface temperatures are warming in many regions and have the potential to alter seasonal thermal stratification. However, the effects of climate change on thermal stratification can be difficult to characterize because trends in thermal stratification can be regulated by changes in multiple climate variables and other characteristics, such as water clarity. Here, we use long‐term (1993–2017) data from near‐pristine Crater Lake (Oregon) to understand long‐term changes in the depth and strength of summer stratification, measured by the center of buoyancy and Schmidt Stability, respectively. The depth of stratification has shoaled significantly (2.4 m decade −1 ), while stratification strength exhibited no long‐term trend. Empirical observations and modeling scenarios demonstrate that atmospheric stilling at Crater Lake is associated with the 25‐year shoaling trend as spring wind speeds declined over the observation period. While summer lake surface water and air temperatures warmed during the study period, spring air temperatures were variable and correlated with summer Schmidt Stability. Our results indicate that warmer spring air temperature resulted in earlier onset of stratification and stronger summer stratification. The observed shoaling of stratification depth at Crater Lake may have important ecological consequences, especially for non‐motile primary producers who can become constrained within a thinner epilimnion and exposed to higher solar radiation and reduced upwelling of nutrients. Driven by climate changes, many large lakes may be experiencing similar trends in seasonal stratification.

Monitoring wetland water quality related to livestock grazing in amphibian habitats - Kelly L. Smalling; Jennifer C. Rowe; Christopher A. Pearl; Luke R. Iwanowicz; Carrie E. Givens; Chauncey W. Anderson; Brome McCreary; Michael J. Adams (Environmental Monitoring and Assessment, 2021)
Land use alteration such as livestock grazing can affect water quality in habitats of at-risk wildlife species. Data from managed wetlands are needed to understand levels of exposure for aquatic life stages and monitor grazing-related changes afield. We quantified spatial and temporal variation in water quality in wetlands occupied by threatened Oregon spotted frog ( Rana pretiosa ) at Klamath Marsh National Wildlife Refuge in Oregon, United States (US). We used analyses for censored data to evaluate the importance of habitat type and grazing history in predicting concentrations of nutrients, turbidity, fecal indicator bacteria (FIB; total coliforms, Escherichia coli ( E. coli ), and enterococci), and estrogenicity, an indicator of estrogenic activity. Nutrients (orthophosphate and ammonia) and enterococci varied over time and space, while E. coli , total coliforms, turbidity, and estrogenicity were more strongly associated with local livestock grazing metrics. Turbidity was correlated with several grazing-related constituents and may be particularly useful for monitoring water quality in landscapes with livestock use. Concentrations of orthophosphate and estrogenicity were elevated at several sites relative to published health benchmarks, and their potential effects on Rana pretiosa warrant further investigation. Our data provided an initial assessment of potential exposure of amphibians to grazing-related constituents in western US wetlands. Increased monitoring of surface water quality and amphibian population status in combination with controlled laboratory toxicity studies could help inform future research and targeted management strategies for wetlands with both grazing and amphibians of conservation concern.

Long‐term change in the avifauna of undisturbed Amazonian rainforest: ground‐foraging birds disappear and the baseline shifts - Philip C Stouffer; Vitek Jirinec; Cameron L. Rutt; Richard O. Bierregaard; Angélica Hernández‐Palma; Erik I. Johnson; Stephen R. Midway; Luke L. Powell; Jared D. Wolfe; Thomas E. Lovejoy (Ecology Letters, 2021)
How are rainforest birds faring in the Anthropocene? We use bird captures spanning > 35 years from 55 sites within a vast area of intact Amazonian rainforest to reveal reduced abundance of terrestrial and near‐ground insectivores in the absence of deforestation, edge effects or other direct anthropogenic landscape change. Because undisturbed forest includes far fewer terrestrial and near‐ground insectivores than it did historically, today’s fragments and second growth are more impoverished than shown by comparisons with modern ‘control’ sites. Any goals for bird community recovery in Amazonian second growth should recognise that a modern bird community will inevitably differ from a baseline from > 35 years ago. Abundance patterns driven by landscape change may be the most conspicuous manifestation of human activity, but biodiversity declines in undisturbed forest represent hidden losses, possibly driven by climate change, that may be pervasive in intact Amazonian forests and other systems considered to be undisturbed.

Role of Sea Surface Microlayer Properties in Cloud Formation - Brianna N. Hendrickson; Sarah D. Brooks; Daniel C. O. Thornton; Richard H. Moore; Ewan Crosbie; Luke D. Ziemba; Craig A. Carlson; Nicholas Baetge; Jessica A. Mirrielees; Alyssa N. Alsante (Frontiers in Marine Science, 2021)
To date, the relative contribution of primary marine organic matter to the subset of atmospheric particles that nucleate cloud droplets is highly uncertain. Here, cloud condensation nuclei (CCN) measurements were conducted on aerosolized sea surface microlayer (SML) samples collected from the North Atlantic Ocean during the NASA North Atlantic Aerosols and Marine Ecosystems Study (NAAMES), κ values were predicted for three representative high molecular weight (HMW) organic components of marine aerosol: 6-glucose, humic acid, and ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO). The predicted κ values for pure organic aerosols varied by only ±0.01 across all of the organics chosen. For the desalted SML samples, calculations assuming an organic composition of entirely RuBisCO provided the closest predicted κ values for the desalted SML samples with a mean κ value of 0.53 ± 0.10. These results indicate that it is the sea salt in the SML which drives the cloud formation potential of marine aerosols. While the presence of organic material from the ocean surface waters may increase aerosol mass due to enrichment processes, cloud formation potential of mixed organic/salt primary marine aerosols will be slightly weakened or unchanged compared to sea spray aerosol.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

A Small Nimble In Situ Fine-Scale Flux Method for Measuring Tree Stem Greenhouse Gas Emissions and Processes (S.N.I.F.F) - Luke C. Jeffrey; Damien T. Maher; Douglas R. Tait; Scott G. Johnston (Ecosystems, 2020)

Coastal carbon cycle changes following mangrove loss - James Z. Sippo; Christian J. Sanders; Isaac R. Santos; Luke C. Jeffrey; Mitchell Call; Yota Harada; Kylie Maguire; Dylan Brown; Stephen R. Conrad; Damien T. Maher (Limnology and Oceanography, 2020)
Global mangrove loss is occurring from deforestation and extreme climatic events, but changes to the coastal carbon cycle following mangrove mortality and/or loss are not well understood. In 2015/2016, a massive climate‐driven mangrove dieback event occurred over ~ 1000 km of Australian coastline. To assess carbon loss following mortality, carbon fluxes in adjacent living and dead forest areas were compared 8 and 20 months postforest dieback. Dead areas experienced an increase in soil CO 2 efflux by ~ 189%, and a decrease in oceanic dissolved inorganic carbon (DIC) outwelling of ~ 50% relative to living areas. DIC outwelling (predominantly carbonate alkalinity) and soil CO 2 efflux accounted for 81% and 16% of losses from the living forest, in comparison to 51% and 47%, respectively, from the dead forest. The dieback drove a shift from a dominance of oceanic carbon outwelling to increased atmospheric CO 2 emissions and decreased alkalinity exports. This shift was likely driven by increased oxygen sediment permeation and the loss of mangrove net primary productivity. Combining our new observations with literature data, we found a logarithmic relationship between soil carbon loss and time since mangrove loss. Using this relationship, we estimate ongoing global carbon losses from historical mangrove deforestation and dieback could be 13.7 ± 9.4 Tg C yr −1 , which is eightfold higher than previous estimates and offsets global mangrove carbon burial by ~ 60%. Even if no future deforestation occurred, we estimate ongoing carbon losses to the atmosphere and ocean from current global mangrove losses of 27 Tg C over the next 30 yr.

Disentangling dimensions of phytochemical diversity: alpha and beta have contrasting effects on an insect herbivore - Andrea E. Glassmire; Luke N. Zehr; William C. Wetzel (Ecology, 2020)
Phytochemical diversity is comprised of two main dimensions—the average (alpha) within‐plant neighbors or the difference (beta) in the composition of chemicals between plant neighbors. Research, however, has primarily examined the consequences of phytochemical diversity on herbivore performance through a single dimension, even though diversity is multidimensional. Furthermore, the ecological role of phytochemical diversity is not well understood because each of these dimensions exhibits unique biological effects on herbivore performance. Therefore, it has been difficult to tease apart the relative importance of alpha and beta chemical diversities on plant–herbivore interactions. We experimentally manipulated alpha and beta diversities along a chemical gradient to disentangle the relative effects of these dimensions on the performance of a mobile generalist herbivore, Trichoplusia ni (Hübner), using 16 genotypes from the Solanum pennellii introgression lines. First, we found contrasting effects of alpha and beta diversities on herbivore performance. Second, when comparing diversity across and within chemical classes, herbivore performance was reduced when plant neighbors had greater diversity within chemical classes that are biologically inhibiting at higher quantities (i.e., quantitative defenses such as phenolics and acyl sugars). However, herbivore performance was enhanced when plant neighbors had higher levels of chemical classes that are biologically toxic (i.e., qualitative defenses such as alkaloids). Finally, herbivores performed better on plant dicultures compared to monocultures, and performance was positively associated with plant dicultures only when there were high levels of average alpha diversity within plant neighbors. Our results suggest T. ni generalist caterpillars do better when plant neighbors are chemically different because differences provide options for them to choose or to switch between plants to balance chemical uptake. Overall, herbivores interact with a large diversity of plant chemicals at multiple scales, and our results indicate that not all chemical diversity is equal: specific dimensions of phytochemical diversity have unique effects on the dynamics of herbivore performance.

The relationship of parental longevity with the aging brain—results from UK Biobank - Qu Tian; Luke C. Pilling; Janice L. Atkins; David Melzer; Luigi Ferrucci (GeroScience, 2020)

Land use drives nitrous oxide dynamics in estuaries on regional and global scales - Michael J. Reading; Douglas R. Tait; Damien T. Maher; Luke C. Jeffrey; Arun Looman; Ceylena Holloway; Haile A. Shishaye; Summer Barron; Isaac R. Santos (Limnology and Oceanography, 2020)
Urban and agricultural development of coastal catchments is known to increase dissolved nitrogen inputs into estuaries; however, much less is known about how land use influences the production of the powerful greenhouse gas nitrous oxide (N 2 O). Here, we assess dissolved N 2 O dynamics in four nearby estuaries across a regional land use gradient and summarize the literature to put the observations into global perspective. During summer dry conditions, N 2 O saturation ranged from 131.4% ± 45.0% in the most pristine system (28% modified) to 198.6% ± 52.3% within the most modified urban system (91% modified). The N 2 O saturation in the wetter winter campaign was higher and more variable than the summer dry campaign (range 84.7–677.7%) likely due to direct transport of N 2 O into the estuaries from catchment runoff and/or produced through denitrification fueled by high nitrate inputs. During both seasons, N 2 O was lowest in areas adjacent to fringing mangroves and highest in upstream fresh/saltwater mixing areas. Coupling our results with previously published N 2 O data from 50 estuarine systems worldwide revealed that estuarine N 2 O increases concomitantly with catchment modification, dissolved inorganic nitrogen availability, and decreasing oxygen concentrations. Based on these results, a 1% increase in anthropogenic modification to global catchments (i.e., agricultural development and/or urbanization) may increase estuarine N 2 O saturation by 2.6% ± 1.2%. These findings indicate that future estuarine N 2 O emissions are likely to increase as anthropogenic modification of coastal catchments intensifies.

Acute exercise-related cognitive effects are not attributable to changes in end-tidal CO2 or cerebral blood velocity - Leena N. Shoemaker; Luke C. Wilson; Samuel J. E. Lucas; Liana Machado; James D. Cotter (European Journal of Applied Physiology, 2020)

Using spatial characteristics of apex carnivore communication and reproductive behaviors to predict responses to future human development - Veronica Yovovich; Maximilian L. Allen; Luke T. Macaulay; Christopher C. Wilmers (Biodiversity and Conservation, 2020)

The importance of including habitat-specific behaviour in models of butterfly movement - Luke C. Evans; Richard M. Sibly; Pernille Thorbek; Ian Sims; Tom H. Oliver; Richard J. Walters (Oecologia, 2020)
Dispersal is a key process affecting population persistence and major factors affecting dispersal rates are the amounts, connectedness and properties of habitats in landscapes. We present new data on the butterfly Maniola jurtina in flower-rich and flower-poor habitats that demonstrates how movement and behaviour differ between sexes and habitat types, and how this effects consequent dispersal rates. Females had higher flight speeds than males, but their total time in flight was four times less. The effect of habitat type was strong for both sexes, flight speeds were ~ 2.5 × and ~ 1.7 × faster on resource-poor habitats for males and females, respectively, and flights were approximately 50% longer. With few exceptions females oviposited in the mown grass habitat, likely because growing grass offers better food for emerging caterpillars, but they foraged in the resource-rich habitat. It seems that females faced a trade-off between ovipositing without foraging in the mown grass or foraging without ovipositing where flowers were abundant. We show that taking account of habitat-dependent differences in activity, here categorised as flight or non-flight, is crucial to obtaining good fits of an individual-based model to observed movement. An important implication of this finding is that incorporating habitat-specific activity budgets is likely necessary for predicting longer-term dispersal in heterogeneous habitats, as habitat-specific behaviour substantially influences the mean (> 30% difference) and kurtosis (1.4 × difference) of dispersal kernels. The presented IBMs provide a simple method to explicitly incorporate known activity and movement rates when predicting dispersal in changing and heterogeneous landscapes.

Phenological responses in a sycamore–aphid–parasitoid system and consequences for aphid population dynamics: A 20 year case study - Vicki L. Senior; Luke C. Evans; Simon R. Leather; Tom H. Oliver; Karl L. Evans (Global Change Biology, 2020)
Species interactions have a spatiotemporal component driven by environmental cues, which if altered by climate change can drive shifts in community dynamics. There is insufficient understanding of the precise time windows during which inter‐annual variation in weather drives phenological shifts and the consequences for mismatches between interacting species and resultant population dynamics—particularly for insects. We use a 20 year study on a tri‐trophic system: sycamore Acer pseudoplatanus , two associated aphid species Drepanosiphum platanoidis and Periphyllus testudinaceus and their hymenopteran parasitoids. Using a sliding window approach, we assess climatic drivers of phenology in all three trophic levels. We quantify the magnitude of resultant trophic mismatches between aphids and their plant hosts and parasitoids, and then model the impacts of these mismatches, direct weather effects and density dependence on local‐scale aphid population dynamics. Warmer temperatures in mid‐March to late‐April were associated with advanced sycamore budburst, parasitoid attack and (marginally) D. platanoidis emergence. The precise time window during which spring weather advances phenology varies considerably across each species. Crucially, warmer temperatures in late winter delayed the emergence of both aphid species. Seasonal variation in warming rates thus generates marked shifts in the relative timing of spring events across trophic levels and mismatches in the phenology of interacting species. Despite this, we found no evidence that aphid population growth rates were adversely impacted by the magnitude of mismatch with their host plants or parasitoids, or direct impacts of temperature and precipitation. Strong density dependence effects occurred in both aphid species and probably buffered populations, through density‐dependent compensation, from adverse impacts of the marked inter‐annual climatic variation that occurred during the study period. These findings explain the resilience of aphid populations to climate change and uncover a key mechanism, warmer winter temperatures delaying insect phenology, by which climate change drives asynchronous shifts between interacting species.

Food and temperature stressors have opposing effects in determining flexible migration decisions in brown trout ( Salmo trutta ) - Louise C. Archer; Stephen A. Hutton; Luke Harman; Stephen D. McCormick; Michael N. O’Grady; Joseph P. Kerry; W. Russell Poole; Patrick Gargan; Philip McGinnity; Thomas E. Reed (Global Change Biology, 2020)
With rapid global change, organisms in natural systems are exposed to a multitude of stressors that likely co‐occur, with uncertain impacts. We explored individual and cumulative effects of co‐occurring environmental stressors on the striking, yet poorly understood, phenomenon of facultative migration. We reared offspring of a brown trout population that naturally demonstrates facultative anadromy (sea migration), under different environmental stressor treatments and measured life history responses in terms of migratory tactics and freshwater maturation rates. Juvenile fish were exposed to reduced food availability, temperatures elevated to 1.8°C above natural conditions or both treatments in combination over 18 months of experimental tank rearing. When considered in isolation, reduced food had negative effects on the size, mass and condition of fish across the experiment. We detected variable effects of warm temperatures (negative effects on size and mass, but positive effect on lipids). When combined with food restriction, temperature effects on these traits were less pronounced, implying antagonistic stressor effects on morphological traits. Stressors combined additively, but had opposing effects on life history tactics: migration increased and maturation rates decreased under low food conditions, whereas the opposite occurred in the warm temperature treatment. Not all fish had expressed maturation or migration tactics by the end of the study, and the frequency of these ‘unassigned’ fish was higher in food deprivation treatments, but lower in warm treatments. Fish showing migration tactics were smaller and in poorer condition than fish showing maturation tactics, but were similar in size to unassigned fish. We further detected effects of food restriction on hypo‐osmoregulatory function of migrants that may influence the fitness benefits of the migratory tactic at sea. We also highlight that responses to multiple stressors may vary depending on the response considered. Collectively, our results indicate contrasting effects of environmental stressors on life history trajectories in a facultatively migratory species.

Racial/Ethnic Differences in Comprehension of Biospecimen Collection: a Nationwide University of Rochester Cancer Center NCI Community Oncology Research Program Study - Matthew Asare; Charles E. Heckler; Eva Culakova; Charles S. Kamen; Amber S. Kleckner; Lori M. Minasian; David S. Wendler; Michelle Feige; Carol J. Weil; Joan Long; Sharon K. Cole; Adedayo A. Onitilo; et al. (Journal of Cancer Education, 2020)

circRNAs expressed in human peripheral blood are associated with human aging phenotypes, cellular senescence and mouse lifespan - Shahnaz Haque; Ryan M. Ames; Karen Moore; Luke C. Pilling; Luanne L. Peters; Stefania Bandinelli; Luigi Ferrucci; Lorna W. Harries (GeroScience, 2020)
Circular RNAs (circRNAs) are an emerging class of non-coding RNA molecules that are thought to regulate gene expression and human disease. Despite the observation that circRNAs are known to accumulate in older organisms and have been reported in cellular senescence, their role in aging remains relatively unexplored. Here, we have assessed circRNA expression in aging human blood and followed up age-associated circRNA in relation to human aging phenotypes, mammalian longevity as measured by mouse median strain lifespan and cellular senescence in four different primary human cell types. We found that circRNAs circDEF6 , c ircEP300 , circFOXO3 and circFNDC3B demonstrate associations with parental longevity or hand grip strength in 306 subjects from the InCHIANTI study of aging, and furthermore, circFOXO3 and circEP300 also demonstrate differential expression in one or more human senescent cell types. Finally, four circRNAs tested showed evidence of conservation in mouse. Expression levels of one of these, circPlekhm1 , was nominally associated with lifespan. These data suggest that circRNA may represent a novel class of regulatory RNA involved in the determination of aging phenotypes, which may show future promise as both biomarkers and future therapeutic targets for age-related disease.

Cerebrovascular haemodynamics during isometric resistance exercise with and without the Valsalva manoeuvre - Blake G. Perry; Tom De Hamel; Kate N. Thomas; Luke C. Wilson; Travis D. Gibbons; James D. Cotter (European Journal of Applied Physiology, 2020)

Regional environmental variation and local species interactions influence biogeographic structure on oyster reefs - Jonathan H. Grabowski; Tarik C. Gouhier; James E. Byers; Luke F. Dodd; A. Randall Hughes; Michael F. Piehler; David L. Kimbro (Ecology, 2020)
Although species interactions are often assumed to be strongest at small spatial scales, they can interact with regional environmental factors to modify food web dynamics across biogeographic scales. The eastern oyster ( Crassostrea virginica ) is a widespread foundational species of both ecological and economic importance. The oyster and its associated assemblage of fish and macroinvertebrates is an ideal system to investigate how regional differences in environmental variables influence trophic interactions and food web structure. We quantified multiple environmental factors, oyster reef properties, associated species, and trophic guilds on intertidal oyster reefs within 10 estuaries along 900 km of the southeastern United States. Geographical gradients in fall water temperature and mean water depth likely influenced regional (i.e., the northern, central and southern sections of the SAB) variation in oyster reef food web structure. Variation in the biomass of mud crabs, an intermediate predator, was mostly (84.1%) explained by reefs within each site, and did not differ substantially among regions; however, regional variation in the biomass of top predators and of juvenile oysters also contributed to biogeographic variation in food web structure. In particular, region explained almost half (40.2%) of the variation in biomass of predators of blue crab, a top predator that was prevalent only in the central region where water depth was greater. Field experiments revealed that oyster mortality due to predation was greatest in the central region, suggesting spatial variation in the importance of trophic cascades. However, high oyster recruitment in the middle region probably compensates for this enhanced predation, potentially explaining why relatively less variation (17.9%) in oyster cluster biomass was explained by region. Region also explained over half of the variation in biomass of mud crab predators (55.2%), with the southern region containing almost an order of magnitude more biomass than the other two regions. In this region, higher water temperatures in the fall corresponded with higher biomass of fish that consume mud crabs and of fish that consume juvenile and forage fish, whereas biomas of their prey (mud crabs and juvenile and forage fish, respectively) was generally low in the southern region. Collectively, these results show how environmental gradients interact with trophic cascades to structure food webs associated with foundation species across biogeographic regions.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Grading Herbaceous Biomass for Biorefineries: a Case Study Based on Chemical Composition and Biochemical Conversion - Amber Hoover; Rachel Emerson; C. Luke Williams; M. M. Ramirez-Corredores; Allison Ray; Kastli Schaller; Sergio Hernandez; Chenlin Li; Michelle Walton (BioEnergy Research, 2019)

Mesohabitat current velocity effects on Didymosphenia geminata and macroinvertebrates in a SE USA hypolimnetic tailwater - Matthew W. Green; Peter W. Blum; Stephanie C. Sellers; Michael M. Gangloff; Luke M. Jacobus; Shea R. Tuberty (Aquatic Ecology, 2019)

Unifying macroecology and macroevolution to answer fundamental questions about biodiversity - Brian J. McGill; Jonathan M. Chase; Joaquín Hortal; Isaac Overcast; Andrew J. Rominger; James Rosindell; Paulo A. V. Borges; Brent C. Emerson; Rampal S. Etienne; Michael J. Hickerson; D. Luke Mahler; Francois Massol; et al. (Global Ecology and Biogeography, 2019)
The study of biodiversity started as a single unified field that spanned both ecology and evolution and both macro and micro phenomena. But over the 20th century, major trends drove ecology and evolution apart and pushed an emphasis towards the micro perspective in both disciplines. Macroecology and macroevolution re‐emerged as self‐consciously distinct fields in the 1970s and 1980s, but they remain largely separated from each other. Here, we argue that despite the challenges, it is worth working to combine macroecology and macroevolution. We present 25 fundamental questions about biodiversity that are answerable only with a mixture of the views and tools of both macroecology and macroevolution.

MAPK, androgen, and glucocorticoid receptor phosphorylation following high-frequency resistance exercise non-functional overreaching - Justin X. Nicoll; Andrew C. Fry; Eric M. Mosier; Luke A. Olsen; Stephanie A. Sontag (European Journal of Applied Physiology, 2019)

The transcript expression levels of HNRNPM, HNRNPA0 and AKAP17A splicing factors may be predictively associated with ageing phenotypes in human peripheral blood - Benjamin P. Lee; Luke C. Pilling; Stefania Bandinelli; Luigi Ferrucci; David Melzer; Lorna W. Harries (Biogerontology, 2019)

Evaluation of chromatophores as natural marks for delta smelt: the effects of life-stage and light intensity - Gonzalo C. Castillo; Marade E. Sandford; Tien-Chieh Hung; Wan-Ru Yang; Galen Tigan; Luke Ellison; Joan C. Lindberg; Erwin E. Van Nieuwenhuyse (Environmental Biology of Fishes, 2019)

The provision and utility of earth science to decision-makers: synthesis and key findings - Mark C. Quigley; Luke G. Bennetts; Patricia Durance; Petra M. Kuhnert; Mark D. Lindsay; Keith G. Pembleton; Melanie E. Roberts; Christopher J. White (Environment Systems and Decisions, 2019)

The provision and utility of science and uncertainty to decision-makers: earth science case studies - Mark C. Quigley; Luke G. Bennetts; Patricia Durance; Petra M. Kuhnert; Mark D. Lindsay; Keith G. Pembleton; Melanie E. Roberts; Christopher J. White (Environment Systems and Decisions, 2019)

Wetland methane emissions dominated by plant‐mediated fluxes: Contrasting emissions pathways and seasons within a shallow freshwater subtropical wetland - Luke C. Jeffrey; Damien T. Maher; Scott G. Johnston; Brendan P. Kelaher; Andy Steven; Douglas R. Tait (Limnology and Oceanography, 2019)
Wetlands represent the largest natural source of methane; however, very few studies have simultaneously quantified the three main atmospheric flux pathways (i.e., diffusive, ebullition, and plant‐mediated). Unlike better‐studied northern hemisphere systems, many Australian subtropical wetlands undergo extreme wet/dry oscillations, which may strongly impact methane dynamics. We assessed diurnal methane emissions of multiple pathways during three distinct seasonal events within an Australian freshwater wetland. Six‐fold higher methane emissions occurred during summer compared to autumn floods (which followed an extensive dry‐period) and winter/cool conditions. Over three seasons, diffusion represented the highest average areal fluxes (25.9 ± 73.2 mmol m −2 d −1 ) but were within range of fluxes through water lily aerenchyma (20.8 ± 41.5 mmol m −2 d −1 ). Average ebullition rates were 5.5 ± 9.7 mmol m −2 d −1 . Water column CH 4 displayed high spatiotemporal variability, ranging from 55.0 to 253.5 μ mol L −1 . Time series δ 13 C–CH 4 isotope measurements revealed an oxidation fraction of ~ 15% at night‐time and ~ 36% during day‐time, and night‐time diffusive fluxes were consistently ~ three‐fold higher than day‐time fluxes. By aggregating seasons and weighting for changes in lily coverage, plant‐mediated fluxes accounted for ~ 59% of the annual methane emissions, whereas ebullition and diffusion each accounted for ~ 20%. The up‐scaled annual area‐weighted wetland methane flux (combined pathways) was 27.3 ± 36.7 mmol m −2 d −1 . We contend that water lilies ( Nymphaea sp.) are the significant carbon source, mediator, and conduit for methane fluxes in this system, and the extremely large seasonal variability of methane emissions reflect dynamic redox oscillations driven by oscillating wet and dry conditions.

Clinical Outcomes of CADASIL-Associated NOTCH3 Mutations in 451,424 European Ancestry Community Volunteers - Jane A. H. Masoli; Luke C. Pilling; George A. Kuchel; David Melzer (Translational Stroke Research, 2019)

Circulation analogues and uncertainty in the time-evolution of extreme event probabilities: evidence from the 1947 Central European heatwave - Luke J. Harrington; Friederike E. L. Otto; Tim Cowan; Gabriele C. Hegerl (Climate Dynamics, 2019)

Early life social and ecological determinants of global DNA methylation in wild spotted hyenas - Zachary M. Laubach; Christopher D. Faulk; Dana C. Dolinoy; Luke Montrose; Tamara R. Jones; Donna Ray; Malit O. Pioon; Kay E. Holekamp (Molecular Ecology, 2019)
Environmental factors early in life can have lasting influence on the development and phenotypes of animals, but the underlying molecular modifications remain poorly understood. We examined cross‐sectional associations among early life socioecological factors and global DNA methylation in 293 wild spotted hyenas ( Crocuta crocuta ) in the Masai Mara National Reserve, Kenya, grouped according to three age classes (cub, subadult and adult). Explanatory variables of interest included annual maternal rank based on outcomes of dyadic agonistic interactions, litter size, wild ungulate prey density and anthropogenic disturbance in the year each hyena was born based on counts of illegal livestock in the Reserve. The dependent variable of interest was global DNA methylation, assessed via the LUminometric Methylation Assay, which provides a percentage methylation value calculated at CCGG sites across the genome. Among cubs, we observed approximately 2.75% higher CCGG methylation in offspring born to high‐ than low‐ranking mothers. Among cubs and subadults, higher anthropogenic disturbance corresponded with greater %CCGG methylation. In both cubs and adults, we found an inverse association between prey density measured before a hyena was 3 months old and %CCGG methylation. Our results suggest that maternal rank, anthropogenic disturbance and prey availability early in life are associated with later life global DNA methylation. Future studies are required to understand the extent to which these DNA methylation patterns relate to adult phenotypes and fitness outcomes.

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

Decoupled trophic responses to long‐term recovery from acidification and associated browning in lakes - Taylor H. Leach; Luke A. Winslow; Nicole M. Hayes; Kevin C. Rose (Global Change Biology, 2019)
Increases in the concentration of dissolved organic matter (DOM) have been documented in many inland waters in recent decades, a process known as “browning”. Previous studies have often used space‐for‐time substitution to examine the direct consequences of increased DOM on lake ecosystems. However, browning often occurs concomitant with other ecologically important water chemistry changes that may interact with or overwhelm any potential ecological response to browning itself. Here we examine a long‐term (~20 year) dataset of 28 lakes in the Adirondack Park, New York, USA, that have undergone strong browning in response to recovery from acidification. With these data, we explored how primary producer and zooplankton consumer populations changed during this time and what physical and chemical changes best predicted these long‐term ecosystem changes. Our results indicate that changes in primary producers are likely driven by reduced water clarity due to browning, independent of changes in nutrients, counter to previously hypothesized primary producer response to browning. In contrast, declines in calcium concomitant with browning play an important role in driving long‐term declines in zooplankton biomass. Our results indicate that responses to browning at different trophic levels are decoupled from one another. Concomitant chemical changes have important implications for our understanding of the response of aquatic ecosystems to browning.

Root biomass variation of cocoa and implications for carbon stocks in agroforestry systems - Kira A. Borden; Luke C. N. Anglaaere; Stephen Adu-Bredu; Marney E. Isaac (Agroforestry Systems, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Fine-Scale Effects of Boat Moorings on Soft Sediment Communities Masked in Large-Scale Comparisons - Assunta C. Macolino; Katherine A. Dafforn; Luke H. Hedge; Alistair G. B. Poore; Emma L. Johnston (Frontiers in Marine Science, 2019)

The skeletal muscle fiber: a mechanically sensitive cell - Luke A. Olsen; Justin X. Nicoll; Andrew C. Fry (European Journal of Applied Physiology, 2019)

Groundwater as a source of dissolved organic matter to coastal waters: Insights from radon and CDOM observations in 12 shallow coastal systems - Jackie R. Webb; Isaac R. Santos; Damien T. Maher; Douglas R. Tait; Tyler Cyronak; Mahmood Sadat‐Noori; Paul Macklin; Luke C. Jeffrey (Limnology and Oceanography, 2019)
The influence of groundwater and pore‐water exchange on dissolved organic matter (DOM) dynamics in coastal surface waters remains poorly understood. Here, we combine bottom up (i.e., groundwater‐derived flux estimates) and top down (i.e., water column response) evidence to assess whether groundwater exchange drives DOM dynamics in shallow coastal waters. We rely on automated chromophoric DOM (CDOM, a proxy for DOM) and radon ( 222 Rn, groundwater proxy) measurements over tidal time scales in 12 shallow systems, including tidal freshwater wetlands, estuaries, mangroves, coral reefs, coastal lakes, a saltmarsh, and a residential canal estate. Groundwater‐derived dissolved organic carbon (DOC) fluxes ranged from 2 ± 2 mmol m −2 d −1 in a coral reef to 1941 ± 1325 mmol m −2 d −1 in a mangrove tidal creek. These groundwater fluxes replaced surface water DOC inventories on time scales ranging from ~ 0.5 d to several weeks. Systems with short replacement times displayed positive correlations between radon and CDOM in surface waters. Groundwater exchange diluted surface water DOC in four systems. Using multiple lines of evidence, we interpreted groundwater to be an important source of DOM to surface waters in 4 out of the 12 systems, including an offshore coral reef lagoon with low surface water DOC concentrations. Groundwater discharge was a negligible source of DOM in systems with high surface water DOC and CDOM concentrations such as tidal freshwater wetlands and coastal lakes. This investigation highlights the high variability in groundwater‐derived DOC fluxes and responses in the water column, and demonstrates that submarine groundwater discharge and advective pore‐water exchange should be considered in coastal carbon budgets.

Inter-Laboratory Characterization of the Velocity Field in the FDA Blood Pump Model Using Particle Image Velocimetry (PIV) - Prasanna Hariharan; Kenneth I. Aycock; Martin Buesen; Steven W. Day; Bryan C. Good; Luke H. Herbertson; Ulrich Steinseifer; Keefe B. Manning; Brent A. Craven; Richard A. Malinauskas (Cardiovascular Engineering and Technology, 2018)

Ten‐year assessment of the 100 priority questions for global biodiversity conservation - Tommaso Jucker; Bonnie Wintle; Gorm Shackelford; Pierre Bocquillon; Jan Laurens Geffert; Tim Kasoar; Eszter Kovacs; Hannah S. Mumby; Chloé Orland; Judith Schleicher; Eleanor R. Tew; Aiora Zabala; et al. (Conservation Biology, 2018)
In 2008, a group of conservation scientists compiled a list of 100 priority questions for the conservation of the world's biodiversity. However, now almost a decade later, no one has yet published a study gauging how much progress has been made in addressing these 100 high‐priority questions in the peer‐reviewed literature. We took a first step toward reexamining the 100 questions to identify key knowledge gaps that remain. Through a combination of a questionnaire and a literature review, we evaluated each question on the basis of 2 criteria: relevance and effort. We defined highly relevant questions as those that – if answered – would have the greatest impact on global biodiversity conservation and quantified effort based on the number of review publications addressing a particular question, which we used as a proxy for research effort. Using this approach, we identified a set of questions that, despite being perceived as highly relevant, have been the focus of relatively few review publications over the past 10 years. These questions covered a broad range of topics but predominantly tackled 3 major themes: conservation and management of freshwater ecosystems, role of societal structures in shaping interactions between people and the environment, and impacts of conservation interventions. We believe these questions represent important knowledge gaps that have received insufficient attention and may need to be prioritized in future research.

An integrative species delimitation approach reveals fine-scale endemism and substantial unrecognized avian diversity in the Philippine Archipelago - Peter A. Hosner; Luke C. Campillo; Michael J. Andersen; Luis A. Sánchez-González; Carl H. Oliveros; Rolly C. Urriza; Robert G. Moyle (Conservation Genetics, 2018)

Exploitation of data from breeding programs supports rapid implementation of genomic selection for key agronomic traits in perennial ryegrass - Luke W. Pembleton; Courtney Inch; Rebecca C. Baillie; Michelle C. Drayton; Preeti Thakur; Yvonne O. Ogaji; German C. Spangenberg; John W. Forster; Hans D. Daetwyler; Noel O. I. Cogan (Theoretical and Applied Genetics, 2018)

The effects of two different doses of ultraviolet-A light exposure on nitric oxide metabolites and cardiorespiratory outcomes - Chris Monaghan; Luke C. McIlvenna; Luke Liddle; Mia Burleigh; Richard B. Weller; Bernadette O. Fernandez; Martin Feelisch; David J. Muggeridge; Chris Easton (European Journal of Applied Physiology, 2018)
Purpose The present study investigated different doses of ultraviolet-A (UV-A) light on plasma nitric oxide metabolites and cardiorespiratory variables. Methods Ten healthy male participants completed three experimental conditions, 7 days apart. Participants were exposed to no light (CON); 10 J cm 2 (15 min) of UV-A light (UVA10) and 20 J cm 2 (30 min) of UV-A light (UVA20) in a randomized order. Plasma nitrite [NO 2 − ] and nitrate [NO 3 − ] concentrations, blood pressure (BP), and heart rate (HR) were recorded before, immediately after exposure and 30 min post-exposure. Whole body oxygen utilization ( $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 ), resting metabolic rate (RMR) and skin temperature were recorded continuously. Results None of the measured parameters changed significantly during CON (all P > 0.05). $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 and RMR were significantly reduced immediately after UVA10 ( P < 0.05) despite no change in plasma [NO 2 − ] ( P > 0.05). Immediately after exposure to UVA20, plasma [NO 2 − ] was higher ( P = 0.014) and $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 and RMR tended to be lower compared to baseline ( P = 0.06). There were no differences in [NO 2 − ] or $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 at the 30 min time point in any condition. UV-A exposure did not alter systolic BP, diastolic BP or MAP (all P > 0.05). UV-A light did not alter plasma [NO 3 − ] at any time point (all P > 0.05). Conclusions This study demonstrates that a UV-A dose of 20 J cm 2 is necessary to increase plasma [NO 2 − ] although a smaller dose is capable of reducing $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 and RMR at rest. Exposure to UV-A did not significantly reduce BP in this cohort of healthy adults. These data suggest that exposure to sunlight has a meaningful acute impact on metabolic function.

Nicotine-induced activation of caudate and anterior cingulate cortex in response to errors in schizophrenia - Lauren V. Moran; Luke E. Stoeckel; Kristina Wang; Carolyn E. Caine; Rosemond Villafuerte; Vanessa Calderon; Justin T. Baker; Dost Ongur; Amy C. Janes; A. Eden Evins; Diego A. Pizzagalli (Psychopharmacology, 2018)

Threat of Predation Does Not Affect Crassostrea virginica Filtration - Luke F. Dodd; Joseph C. Caracappa; Stephen R. Fegley; Jonathan H. Grabowski; Michael F. Piehler (Estuaries and Coasts, 2018)

Sexually Dimorphic Effects of Early-Life Exposures to Endocrine Disruptors: Sex-Specific Epigenetic Reprogramming as a Potential Mechanism - Carolyn McCabe; Olivia S. Anderson; Luke Montrose; Kari Neier; Dana C. Dolinoy (Current Environmental Health Reports, 2017)

Seasonality of change: Summer warming rates do not fully represent effects of climate change on lake temperatures - Luke A. Winslow; Jordan S. Read; Gretchen J. A. Hansen; Kevin C. Rose; Dale M. Robertson (Limnology and Oceanography, 2017)
Responses in lake temperatures to climate warming have primarily been characterized using seasonal metrics of surface‐water temperatures such as summertime or stratified period average temperatures. However, climate warming may not affect water temperatures equally across seasons or depths. We analyzed a long‐term dataset (1981–2015) of biweekly water temperature data in six temperate lakes in Wisconsin, U.S.A. to understand (1) variability in monthly rates of surface‐ and deep‐water warming, (2) how those rates compared to summertime average trends, and (3) if monthly heterogeneity in water temperature trends can be predicted by heterogeneity in air temperature trends. Monthly surface‐water temperature warming rates varied across the open‐water season, ranging from 0.013 in August to 0.073°C yr −1 in September (standard deviation [SD]: 0.025°C yr −1 ). Deep‐water trends during summer varied less among months (SD: 0.006°C yr −1 ), but varied broadly among lakes (–0.056°C yr −1 to 0.035°C yr −1 , SD: 0.034°C yr −1 ). Trends in monthly surface‐water temperatures were well correlated with air temperature trends, suggesting monthly air temperature trends, for which data exist at broad scales, may be a proxy for seasonal patterns in surface‐water temperature trends during the open water season in lakes similar to those studied here. Seasonally variable warming has broad implications for how ecological processes respond to climate change, because phenological events such as fish spawning and phytoplankton succession respond to specific, seasonal temperature cues.

Are long-term fish assemblage changes in a large US river related to the Asian Carp invasion? Test of the hostile take-over and opportunistic dispersal hypotheses - Mark Pyron; Jesse C. Becker; Kyle J. Broadway; Luke Etchison; Mario Minder; Dawn DeColibus; M. Chezem; Kevin H. Wyatt; Brent A. Murry (Aquatic Sciences, 2017)

DNA Sequencing as a Tool to Monitor Marine Ecological Status - Kelly D. Goodwin; Luke R. Thompson; Bernardo Duarte; Tim Kahlke; Andrew R. Thompson; João C. Marques; Isabel Caçador (Frontiers in Marine Science, 2017)

Effects of habitat features on size-biased predation on salmon by bears - Luke C. Andersson; John D. Reynolds (Oecologia, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Dictyocaulosis in dairy cows in Brazil: an epidemiological, clinical-pathological and therapeutic approach - Luan C. Henker; Claiton I. Schwertz; Neuber J. Lucca; Manoela M. Piva; Patricia Giacomin; Anderson Gris; Leandro A. Rhoden; Luke J. Norbury; Aleksandro S. da Silva; Rafael A. da Rosa; Ricardo E. Mendes (Acta Parasitologica, 2017)
An outbreak of severe parasitic pneumonia caused by

Groundwater, Acid and Carbon Dioxide Dynamics Along a Coastal Wetland, Lake and Estuary Continuum - Luke C. Jeffrey; Damien T. Maher; Isaac R. Santos; Ashly McMahon; Douglas R. Tait (Estuaries and Coasts, 2016)

Climate change and habitat conversion favour the same species - Luke O. Frishkoff; Daniel S. Karp; Jon R. Flanders; Jim Zook; Elizabeth A. Hadly; Gretchen C. Daily; Leithen K. M'Gonigle (Ecology Letters, 2016)
Land‐use change and climate change are driving a global biodiversity crisis. Yet, how species' responses to climate change are correlated with their responses to land‐use change is poorly understood. Here, we assess the linkages between climate and land‐use change on birds in Neotropical forest and agriculture. Across > 300 species, we show that affiliation with drier climates is associated with an ability to persist in and colonise agriculture. Further, species shift their habitat use along a precipitation gradient: species prefer forest in drier regions, but use agriculture more in wetter zones. Finally, forest‐dependent species that avoid agriculture are most likely to experience decreases in habitable range size if current drying trends in the Neotropics continue as predicted. This linkage suggests a synergy between the primary drivers of biodiversity loss. Because they favour the same species, climate and land‐use change will likely homogenise biodiversity more severely than otherwise anticipated.

Repeated invasions into the twilight zone: evolutionary origins of a novel assemblage of fishes from deep Caribbean reefs - Luke Tornabene; James L. Van Tassell; D. Ross Robertson; Carole C. Baldwin (Molecular Ecology, 2016)
Mesophotic and deeper reefs of the tropics are poorly known and underexplored ecosystems worldwide. Collectively referred to as the ‘twilight zone’, depths below ~30–50 m are home to many species of reef fishes that are absent from shallower depths, including many undescribed and endemic species. We currently lack even a basic understanding of the diversity and evolutionary origins of fishes on tropical mesophotic reefs. Recent submersible collections in the Caribbean have provided new specimens that are enabling phylogenetic reconstructions that incorporate deep‐reef representatives of tropical fish genera. Here, we investigate evolutionary depth transitions in the family Gobiidae (gobies), the most diverse group of tropical marine fishes. Using divergence‐time estimation coupled with stochastic character mapping to infer the timing of shallow‐to‐deep habitat transitions in gobies, we demonstrate at least four transitions from shallow to mesophotic depths. Habitat transitions occurred in two broad time periods (Miocene, Pliocene–Pleistocene), and may have been linked to the availability of underutilized niches, as well as the evolution of morphological/behavioural adaptations for life on deep reefs. Further, our analysis shows that at least three evolutionary lineages that invaded deep habitats subsequently underwent speciation, reflecting another unique mode of radiation within the Gobiidae. Lastly, we synthesize depth distributions for 95 species of Caribbean gobies, which reveal major bathymetric faunal breaks at the boundary between euphotic and mesophotic reefs. Ultimately, our study is the first rigorous investigation into the origin of Caribbean deep‐reef fishes and provides a framework for future studies that utilize rare, deep‐reef specimens.

Area, climate heterogeneity, and the response of climate niches to ecological opportunity in island radiations of A nolis lizards - Adam C. Algar; D. Luke Mahler (Global Ecology and Biogeography, 2016)
Aim Rates of climate niche evolution underlie numerous fundamental ecological processes and patterns. However, while climate niche conservatism varies markedly among regions and clades, the source of this variation remains poorly understood. We tested whether ecological opportunity can stimulate radiation within climate niche space at biogeographic scales, predicting that rates of climate niche evolution will scale with geographic area and climate heterogeneity. Location Caribbean Methods We quantified two temperature axes (mean temperature and temperature seasonality of species' localities) of the climate niche for 130 A nolis species on C uba, H ispaniola, P uerto R ico, J amaica and the northern and southern L esser A ntilles. Using a species‐level phylogeny, we fitted macroevolutionary models that either constrained rates of climate niche evolution or allowed them to vary among regions. Next, we regressed region‐specific evolutionary rates against area, species richness and climate heterogeneity. We evaluated whether results were robust to uncertainty in phylogenetic and biogeographic reconstructions and the assumed mode of evolution. Results For both niche axes, an O rnstein‐ U hlenbeck model that allowed the net rate of evolution (σ 2 ) to vary among island groups fit the data considerably better than a single‐rate B rownian motion model. Nagelkerke pseudo‐ R 2 values of the fit of these OU models to mean temperature and seasonality axes were 0.43 and 0.66, respectively. Evolutionary rates for both axes were higher in larger areas, which also have more species. Only the rate of mean occupied temperature evolution was positively related to climate heterogeneity, and only after accounting for region size. Conclusions Rates of climate niche evolution scale consistently with the area available for radiation, but responses to climate heterogeneity vary among niche axes. For the mean temperature axis, climate heterogeneity generated additional opportunities for radiation, but for seasonality it did not. Overall, the physical setting in which a clade diversifies can influence where it falls on the evolutionary continuum, from climate niche conservatism to radiation.

Targeted genotyping-by-sequencing permits cost-effective identification and discrimination of pasture grass species and cultivars - Luke W. Pembleton; Michelle C. Drayton; Melissa Bain; Rebecca C. Baillie; Courtney Inch; German C. Spangenberg; Junping Wang; John W. Forster; Noel O. I. Cogan (Theoretical and Applied Genetics, 2016)

Sources of Biomass Feedstock Variability and the Potential Impact on Biofuels Production - C. Luke Williams; Tyler L. Westover; Rachel M. Emerson; Jaya Shankar Tumuluru; Chenlin Li (BioEnergy Research, 2016)

Natural history collections as windows on evolutionary processes - Michael W. Holmes; Talisin T. Hammond; Guinevere O. U. Wogan; Rachel E. Walsh; Katie LaBarbera; Elizabeth A. Wommack; Felipe M. Martins; Jeremy C. Crawford; Katya L. Mack; Luke M. Bloch; Michael W. Nachman (Molecular Ecology, 2016)
Natural history collections provide an immense record of biodiversity on Earth. These repositories have traditionally been used to address fundamental questions in biogeography, systematics and conservation. However, they also hold the potential for studying evolution directly. While some of the best direct observations of evolution have come from long‐term field studies or from experimental studies in the laboratory, natural history collections are providing new insights into evolutionary change in natural populations. By comparing phenotypic and genotypic changes in populations through time, natural history collections provide a window into evolutionary processes. Recent studies utilizing this approach have revealed some dramatic instances of phenotypic change over short timescales in response to presumably strong selective pressures. In some instances, evolutionary change can be paired with environmental change, providing a context for potential selective forces. Moreover, in a few cases, the genetic basis of phenotypic change is well understood, allowing for insight into adaptive change at multiple levels. These kinds of studies open the door to a wide range of previously intractable questions by enabling the study of evolution through time, analogous to experimental studies in the laboratory, but amenable to a diversity of species over longer timescales in natural populations.

Sorption and desorption of cadmium and zinc in two tropical soils amended with sugarcane-straw-derived biochar - Leônidas C. A. Melo; Aline P. Puga; Aline R. Coscione; Luke Beesley; Cleide A. Abreu; Otávio A. Camargo (Journal of Soils and Sediments, 2016)

Thermal niche predicts tolerance to habitat conversion in tropical amphibians and reptiles - Luke O. Frishkoff; Elizabeth A. Hadly; Gretchen C. Daily (Global Change Biology, 2015)
Habitat conversion is a major driver of the biodiversity crisis, yet why some species undergo local extinction while others thrive under novel conditions remains unclear. We suggest that focusing on species' niches, rather than traits, may provide the predictive power needed to forecast biodiversity change. We first examine two Neotropical frog congeners with drastically different affinities to deforestation and document how thermal niche explains deforestation tolerance. The more deforestation‐tolerant species is associated with warmer macroclimates across Costa Rica, and warmer microclimates within landscapes. Further, in laboratory experiments, the more deforestation‐tolerant species has critical thermal limits, and a jumping performance optimum, shifted ~2 °C warmer than those of the more forest‐affiliated species, corresponding to the ~3 °C difference in daytime maximum temperature that these species experience between habitats. Crucially, neither species strictly specializes on either habitat – instead habitat use is governed by regional environmental temperature. Both species track temperature along an elevational gradient, and shift their habitat use from cooler forest at lower elevations to warmer deforested pastures upslope. To generalize these conclusions, we expand our analysis to the entire mid‐elevational herpetological community of southern Costa Rica. We assess the climatological affinities of 33 amphibian and reptile species, showing that across both taxonomic classes, thermal niche predicts presence in deforested habitat as well as or better than many commonly used traits. These data suggest that warm‐adapted species carry a significant survival advantage amidst the synergistic impacts of land‐use conversion and climate change.

Comparison of senescence-associated miRNAs in primary skin and lung fibroblasts - Alice C. Holly; Sushma Grellscheid; Pieter van de Walle; David Dolan; Luke C. Pilling; Darren J. Daniels; Thomas von Zglinicki; Luigi Ferrucci; David Melzer; Lorna W. Harries (Biogerontology, 2015)

Pilea nguruensis (Urticaceae), a new species from the Eastern Arc Mountains, central Tanzania - I. Friis; I. Darbyshire; C. M. Wilmot-Dear; W. R. Q. Luke (Kew Bulletin, 2015)

A characterization of volatile organic compounds and secondary organic aerosol at a mountain site in the Southeastern United States - Michael Link; Yong Zhou; Brett Taubman; James Sherman; Hadi Morrow; Ian Krintz; Luke Robertson; Ryan Cook; Justine Stocks; Matthew West; Barkley C. Sive (Journal of Atmospheric Chemistry, 2015)

Eight-choice sound localization by manatees: performance abilities and head related transfer functions - Debborah E. Colbert-Luke; Joseph C. Gaspard; Roger L. Reep; Gordon B. Bauer; Kimberly Dziuk; Adrienne Cardwell; David A. Mann (Journal of Comparative Physiology A, 2015)

Thermal stress and predation risk trigger distinct transcriptomic responses in the intertidal snail Nucella lapillus - Nathaniel D. Chu; Luke P. Miller; Stefan T. Kaluziak; Geoffrey C. Trussell; Steven V. Vollmer (Molecular Ecology, 2014)
Thermal stress and predation risk have profound effects on rocky shore organisms, triggering changes in their feeding behaviour, morphology and metabolism. Studies of thermal stress have shown that underpinning such changes in several intertidal species are specific shifts in gene and protein expression (e.g. upregulation of heat‐shock proteins). But relatively few studies have examined genetic responses to predation risk. Here, we use next‐generation RNA sequencing (RNA‐seq) to examine the transcriptomic ( mRNA ) response of the snail Nucella lapillus to thermal stress and predation risk. We found that like other intertidal species, N. lapillus displays a pronounced genetic response to thermal stress by upregulating many heat‐shock proteins and other molecular chaperones. In contrast, the presence of a crab predator ( Carcinus maenas ) triggered few significant changes in gene expression in our experiment, and this response showed no significant overlap with the snail's response to thermal stress. These different gene expression profiles suggest that thermal stress and predation risk could pose distinct and potentially additive challenges for N. lapillus and that genetic responses to biotic stresses such as predation risk might be more complex and less uniform across species than genetic responses to abiotic stresses such as thermal stress.

Climate change enhances the negative effects of predation risk on an intermediate consumer - Luke P. Miller; Catherine M. Matassa; Geoffrey C. Trussell (Global Change Biology, 2014)
Predators are a major source of stress in natural systems because their prey must balance the benefits of feeding with the risk of being eaten. Although this ‘fear’ of being eaten often drives the organization and dynamics of many natural systems, we know little about how such risk effects will be altered by climate change. Here, we examined the interactive consequences of predator avoidance and projected climate warming in a three‐level rocky intertidal food chain. We found that both predation risk and increased air and sea temperatures suppressed the foraging of prey in the middle trophic level, suggesting that warming may further enhance the top‐down control of predators on communities. Prey growth efficiency, which measures the efficiency of energy transfer between trophic levels, became negative when prey were subjected to predation risk and warming. Thus, the combined effects of these stressors may represent an important tipping point for individual fitness and the efficiency of energy transfer in natural food chains. In contrast, we detected no adverse effects of warming on the top predator and the basal resources. Hence, the consequences of projected warming may be particularly challenging for intermediate consumers residing in food chains where risk dominates predator‐prey interactions.

Ebullitive methane emissions from oxygenated wetland streams - John T. Crawford; Emily H. Stanley; Seth A. Spawn; Jacques C. Finlay; Luke C. Loken; Robert G. Striegl (Global Change Biology, 2014)
Stream and river carbon dioxide emissions are an important component of the global carbon cycle. Methane emissions from streams could also contribute to regional or global greenhouse gas cycling, but there are relatively few data regarding stream and river methane emissions. Furthermore, the available data do not typically include the ebullitive (bubble‐mediated) pathway, instead focusing on emission of dissolved methane by diffusion or convection. Here, we show the importance of ebullitive methane emissions from small streams in the regional greenhouse gas balance of a lake and wetland‐dominated landscape in temperate North America and identify the origin of the methane emitted from these well‐oxygenated streams. Stream methane flux densities from this landscape tended to exceed those of nearby wetland diffusive fluxes as well as average global wetland ebullitive fluxes. Total stream ebullitive methane flux at the regional scale (103 Mg C yr −1 ; over 6400 km 2 ) was of the same magnitude as diffusive methane flux previously documented at the same scale. Organic‐rich stream sediments had the highest rates of bubble release and higher enrichment of methane in bubbles, but glacial sand sediments also exhibited high bubble emissions relative to other studied environments. Our results from a database of groundwater chemistry support the hypothesis that methane in bubbles is produced in anoxic near‐stream sediment porewaters, and not in deeper, oxygenated groundwaters. Methane interacts with other key elemental cycles such as nitrogen, oxygen, and sulfur, which has implications for ecosystem changes such as drought and increased nutrient loading. Our results support the contention that streams, particularly those draining wetland landscapes of the northern hemisphere, are an important component of the global methane cycle.

Functional structure of ant and termite assemblages in old growth forest, logged forest and oil palm plantation in Malaysian Borneo - Sarah H. Luke; Tom M. Fayle; Paul Eggleton; Edgar C. Turner; Richard G. Davies (Biodiversity and Conservation, 2014)

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

A gymnosperm affinity for Ricciisporites tuberculatus Lundblad: implications for vegetation and environmental reconstructions in the Late Triassic - Wolfram M. Kürschner; Luke Mander; Jennifer C. McElwain (Palaeobiodiversity and Palaeoenvironments, 2014)

Role of rapid sequence whole-body MRI screening in SDH-associated hereditary paraganglioma families - Kory W. Jasperson; Wendy Kohlmann; Amanda Gammon; Heidi Slack; Luke Buchmann; Jason Hunt; Anne C. Kirchhoff; Henry Baskin; Akram Shaaban; Joshua D. Schiffman (Familial Cancer, 2014)

Moving beyond the conceptual: specificity in regional climate change adaptation actions for biodiversity in South East Queensland, Australia - Luke P. Shoo; Julian O’Mara; Karin Perhans; Jonathan R. Rhodes; Rebecca K. Runting; Susanne Schmidt; Lochran W. Traill; Lui C. Weber; Kerrie A. Wilson; Catherine E. Lovelock (Regional Environmental Change, 2014)

Countryside biogeography of Neotropical reptiles and amphibians - Chase D. Mendenhall; Luke O. Frishkoff; Georgina Santos-Barrera; Jesús Pacheco; Eyobed Mesfun; Fernando Mendoza Quijano; Paul R. Ehrlich; Gerardo Ceballos; Gretchen C. Daily; Robert M. Pringle (Ecology, 2014)
The future of biodiversity and ecosystem services depends largely on the capacity of human‐dominated ecosystems to support them, yet this capacity remains largely unknown. Using the framework of countryside biogeography, and working in the Las Cruces system of Coto Brus, Costa Rica, we assessed reptile and amphibian assemblages within four habitats that typify much of the Neotropics: sun coffee plantations (12 sites), pasture (12 sites), remnant forest elements (12 sites), and a larger, contiguous protected forest (3 sites in one forest). Through analysis of 1678 captures of 67 species, we draw four primary conclusions. First, we found that the majority of reptile (60%) and amphibian (70%) species in this study used an array of habitat types, including coffee plantations and actively grazed pastures. Second, we found that coffee plantations and pastures hosted rich, albeit different and less dense, reptile and amphibian biodiversity relative to the 326‐ha Las Cruces Forest Reserve and neighboring forest elements. Third, we found that the small ribbons of “countryside forest elements” weaving through farmland collectively increased the effective size of a 326‐ha local forest reserve 16‐fold for reptiles and 14‐fold for amphibians within our 236‐km 2 study area. Therefore, countryside forest elements, often too small for most remote sensing techniques to identify, are contributing ∼95% of the available habitat for forest‐dependent reptiles and amphibians in our largely human‐dominated study region. Fourth, we found large and pond‐reproducing amphibians to prefer human‐made habitats, whereas small, stream‐reproducing, and directly developing species are more dependent on forest elements. Our investigation demonstrates that tropical farming landscapes can support substantial reptile and amphibian biodiversity. Our approach provides a framework for estimating the conservation value of the complex working landscapes that constitute roughly half of the global land surface, and which are experiencing intensification pressure worldwide.

A comparison of carbon and nitrogen stocks among land uses/covers in coastal Florida - R. Chelsea Nagy; B. Graeme Lockaby; Wayne C. Zipperer; Luke J. Marzen (Urban Ecosystems, 2014)

Patterns of rain forest plant endemism in subtropical Australia relate to stable mesic refugia and species dispersal limitations - Lui C. Weber; Jeremy VanDerWal; Susanne Schmidt; William J. F. McDonald; Luke P. Shoo (Journal of Biogeography, 2014)
Aim Our aims were to identify centres of endemism and to infer whether these areas have functioned as refugia for subtropical rain forest plants through historical climate fluctuations. Location Subtropical eastern A ustralia (23–33° S; 145–155° E). Methods We collated 25,000 records of 179 endemic rain forest plants to identify geographical areas with unusually high concentrations of endemic taxa and range‐restricted endemics. We then tested whether centres of endemism coincide with other features indicating refugia, including habitat stability over 120,000 years, and we related dispersal patterns to past habitat stability using seed weight as a surrogate for dispersal ability of endemic plant taxa. Results We identified five main centres of endemism. Historical stability and other processes affecting diversity, including current rainfall, rain forest area, and topographic complexity, explained 58% of variation in plant‐weighted endemism. Taxa with poor dispersal ability were concentrated in the areas that were most stable historically. Main conclusions Several lines of evidence suggest that centres of endemism have functioned as important refugia for subtropical rain forest taxa through historical climate fluctuations. The highest concentrations of range‐restricted endemic species occur in locations that are predicted to have maintained stable rain forest habitat over at least the past 120,000 years. This association was independent from other factors that were expected to promote diversity (i.e. rain forest area and current environmental suitability). These locations have disproportionately high concentrations of species with poor dispersal ability (large‐seeded species).

Development and characterization of 18 microsatellite loci for the spotted salamander (Ambystoma maculatum) using paired-end Illumina shotgun sequencing - William E. Peterman; Emily R. Brocato; Luke R. Pauley; Elsa C. Stuart; Raymond D. Semlitsch; Lori S. Eggert (Conservation Genetics Resources, 2013)

Development and characterization of 22 microsatellite loci for the ringed salamander (Ambystoma annulatum) using paired-end Illumina shotgun sequencing - William E. Peterman; Luke R. Pauley; Emily R. Brocato; Elsa C. Stuart; Raymond D. Semlitsch; Lori S. Eggert (Conservation Genetics Resources, 2013)

The structure of Pavlovian fear conditioning in the amygdala - Hadley C. Bergstrom; Craig G. McDonald; Smita Dey; Haying Tang; Reed G. Selwyn; Luke R. Johnson (Brain Structure and Function, 2013)

High-temperature neutron diffraction study of deuterated brucite - Hongwu Xu; Yusheng Zhao; Donald D. Hickmott; Nina J. Lane; Sven C. Vogel; Jianzhong Zhang; Luke L. Daemen (Physics and Chemistry of Minerals, 2013)

MRI volume of the medial frontal cortex predicts financial capacity in patients with mild Alzheimer’s disease - Luke E. Stoeckel; Christopher C. Stewart; H. Randall Griffith; Kristen Triebel; Ozioma C. Okonkwo; Jan A. den Hollander; Roy C. Martin; Katherine Belue; Jacquelynn N. Copeland; Lindy E. Harrell; John C. Brockington; David G. Clark; et al. (Brain Imaging and Behavior, 2013)

Neurons Activated During Fear Memory Consolidation and Reconsolidation are Mapped to a Common and New Topography in the Lateral Amygdala - Hadley C. Bergstrom; Craig G. McDonald; Smita Dey; Gina M. Fernandez; Luke R. Johnson (Brain Topography, 2013)

Niche incumbency, dispersal limitation and climate shape geographical distributions in a species‐rich island adaptive radiation - Adam C. Algar; D. Luke Mahler; Richard E. Glor; Jonathan B. Losos (Global Ecology and Biogeography, 2013)
Aim To test the role of climate, dispersal limitation and biotic interactions in limiting species' distributions within an island adaptive radiation by integrating species traits, phylogeny and estimates of dispersal cost into climate‐based species distribution models. Location H ispaniola. Methods Focusing on 26 species of A nolis lizards, we used multivariate adaptive regression splines to evaluate the contribution of climate, species interactions, phylogenetic history and dispersal limitation to species distributional limits. For each species, we mapped the morphological similarity of congenerics using traits of known ecological import and predicted that species would be less likely to occur in climatically suitable areas if they were inhabited by ecologically similar species. Dispersal limitation was incorporated by generating spatially explicit estimates of dispersal cost, based on inferred habitat suitability. We compared models including morphological similarity, dispersal cost, phylogeny and climate with climate‐only models. Results were evaluated against a null model that conserved the spatial structure of species occurrences. Results Climate had a dominant role in shaping species distributions. However, for over one‐third of species we also found evidence consistent with supplemental effects of species interactions, i.e. ecological niche incumbency. These species were less likely to occur in climatically suitable areas inhabited by a morphologically similar species. Dispersal limitation also supplemented climatic limits in most species. These results were robust to co‐variation with phylogeny and to comparison with our null model. Conclusions These results suggest that, rather than act as mutually exclusive alternatives, multiple dimensions of the ecological niche, including climatic limits, biotic interactions and dispersal capacity, interact to shape species distributions and that local interactions can influence the broad‐scale geography of species in a predictable way.

On the dimensionality of ecological stability - Ian Donohue; Owen L. Petchey; José M. Montoya; Andrew L. Jackson; Luke McNally; Mafalda Viana; Kevin Healy; Miguel Lurgi; Nessa E. O'Connor; Mark C. Emmerson (Ecology Letters, 2013)
Ecological stability is touted as a complex and multifaceted concept, including components such as variability, resistance, resilience, persistence and robustness. Even though a complete appreciation of the effects of perturbations on ecosystems requires the simultaneous measurement of these multiple components of stability, most ecological research has focused on one or a few of those components analysed in isolation. Here, we present a new view of ecological stability that recognises explicitly the non‐independence of components of stability. This provides an approach for simplifying the concept of stability. We illustrate the concept and approach using results from a field experiment, and show that the effective dimensionality of ecological stability is considerably lower than if the various components of stability were unrelated. However, strong perturbations can modify, and even decouple, relationships among individual components of stability. Thus, perturbations not only increase the dimensionality of stability but they can also alter the relationships among components of stability in different ways. Studies that focus on single forms of stability in isolation therefore risk underestimating significantly the potential of perturbations to destabilise ecosystems. In contrast, application of the multidimensional stability framework that we propose gives a far richer understanding of how communities respond to perturbations.

The tempo of genetic evolution in birds: body mass and climate effects - Len N. Gillman; Luke S. C. McCowan; Shane D. Wright (Journal of Biogeography, 2012)
Aim Negative relationships between body mass and substitution rates have previously been reported. However, most of these studies have involved contrasted taxa that, due to their highly divergent phylogenetic histories, also differ in many additional characteristics other than mass. In particular, there has been little examination of the potentially confounding effects of climate or population size. Here we test for differences in rates of microevolution among bird species that, although differing in mass, are nonetheless very closely related phylogenetic pairs. We additionally tested for latitudinal/elevational and population size effects across these contrasts. Location Global. Methods The tempo of microevolution within the cytochrome b gene of mitochondrial DNA was compared between closely related bird species that differed in body mass, using 130 phylogenetically independent species pairs. In order to minimize climate effects, pairs not having overlapping latitudinal ranges were discarded. In addition, a subset of pairs was identified and analysed that involved comparisons between species that have different latitudinal or elevational midpoints. Results Species with smaller mass had substitution rates marginally faster than those with larger mass (small : large median ratio = 1.05). However, this result was only statistically significant when data were pruned to eliminate comparisons in which population or range size also varied substantially between contrasted species. Latitude and elevation had a much stronger association with substitution rates than body mass within the subset of pairs ( n = 30) that also differed in their spatial distributions: lower elevation or latitude species had substantially more substitutions than those at higher latitudes or elevations (low : high ratio = 1.35). Furthermore, when the dataset was pruned of pairs in which body mass was confounded by latitude or elevation, the body mass effect was eliminated. Main conclusions Body mass is known to correlate with latitude, so that the latitudinal/elevational association with microevolution we found might either be additive to, or causal of, the body mass effect. These results are consistent with the evolutionary speed hypothesis, which suggests that latitudinal diversity gradients derive from variation in the rate of microevolution. Our findings also serve to raise concerns about biogeographical studies that use genetic distances between taxa to estimate time since divergence.

Did geckos ride the Palawan raft to the Philippines? - Cameron D. Siler; Jamie R. Oaks; Luke J. Welton; Charles W. Linkem; John C. Swab; Arvin C. Diesmos; Rafe M. Brown (Journal of Biogeography, 2012)
Aim We examine the genetic diversity within the lizard genus Gekko in the Philippine islands to understand the role of geography and geological history in shaping species diversity in this group. We test multiple biogeographical hypotheses of species relationships, including the recently proposed Palawan Ark Hypothesis. Location Southeast Asia and the Philippines. Methods Samples of all island endemic and widespread Philippine Gekko species were collected and sequenced for one mitochondrial gene (NADH dehydrogenase subunit 2) and one nuclear gene (phosducin). We used maximum likelihood and Bayesian phylogenetic methods to derive the phylogeny. Divergence time analyses were used to estimate the time tree of Philippine Gekko in order to test biogeographical predictions of species relationships. The phylogenetic trees from the posterior distribution of the Bayesian analyses were used for testing biogeographical hypotheses. Haplotype networks were created for the widespread species Gekko mindorensis to explore genetic variation within recently divergent clades. Results Both maximum likelihood and Bayesian phylogenetic analyses indicated that Philippine Gekko species are a diverse clade with a long history in the archipelago. Ancestral range reconstruction and divergence time analyses suggest a Palawan microcontinental origin for this clade, coinciding with Palawan’s separation from Asia beginning 30 Ma, with subsequent diversification in the oceanic Philippine islands. The widespread species G. mindorensis and G. monarchus diversified in the late Miocene/early Pliocene and are potentially complexes of numerous undescribed species. Main conclusions The view of the Philippine islands as a ‘fringing archipelago’ does not explain the pattern of species diversity in the genus Gekko . Philippine Gekko species have diversified within the archipelago over millions of years of isolation, forming a large diverse group of endemic species. Furthermore, the Philippine radiation of gekkonid lizards demonstrates biogeographical patterns most consistent with stochastic colonization followed by in situ diversification. Our results reveal the need to consider deeper time geological processes and their potential role in the evolution of some Philippine terrestrial organisms.

Single-Detector Simultaneous Optical Mapping of V m and [Ca2+]i in Cardiac Monolayers - James A. Scull; Luke C. McSpadden; Herman D. Himel; Nima Badie; Nenad Bursac (Annals of Biomedical Engineering, 2012)

Colonization, pathogenicity, host susceptibility, and therapeutics for Staphylococcus aureus: what is the clinical relevance? - Steven Y. C. Tong; Luke F. Chen; Vance G. Fowler (Seminars in Immunopathology, 2012)

The effect of land use systems on tree diversity: farmer preference and species composition of cocoa-based agroecosystems in Ghana - Luke C. N. Anglaaere; Joseph Cobbina; Fergus L. Sinclair; Morag A. McDonald (Agroforestry Systems, 2011)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

Plasma triglyceride concentrations are rapidly reduced following individual bouts of endurance exercise in women - Gregory C. Henderson; Ronald M. Krauss; Jill A. Fattor; Nastaran Faghihnia; Mona Luke-Zeitoun; George A. Brooks (European Journal of Applied Physiology, 2010)

Release of Plasmid DNA-Encoding IL-10 from PLGA Microparticles Facilitates Long-Term Reversal of Neuropathic Pain Following a Single Intrathecal Administration - Ryan Gene Soderquist; Evan M. Sloane; Lisa C. Loram; Jacqueline A. Harrison; Ellen C. Dengler; Scott M. Johnson; Luke D. Amer; Courtney S. Young; Makenzie T. Lewis; Stephen Poole; Matthew G. Frank; Linda R. Watkins; et al. (Pharmaceutical Research, 2010)

Skin cooling aids cerebrovascular function more effectively under severe than moderate heat stress - Rebekah A. I. Lucas; Philip N. Ainslie; Jui-Lin Fan; Luke C. Wilson; Kate N. Thomas; James D. Cotter (European Journal of Applied Physiology, 2010)

Thermal expansion and decomposition of jarosite: a high-temperature neutron diffraction study - Hongwu Xu; Yusheng Zhao; Sven C. Vogel; Donald D. Hickmott; Luke L. Daemen; Monika A. Hartl (Physics and Chemistry of Minerals, 2010)

Methylphenidate improves response inhibition but not reflection–impulsivity in children with attention deficit hyperactivity disorder (ADHD) - Elise E. DeVito; Andrew D. Blackwell; Luke Clark; Lindsey Kent; Anna Maria Dezsery; Danielle C. Turner; Michael R. F. Aitken; Barbara J. Sahakian (Psychopharmacology, 2009)

Mortalities caused by off-road vehicles (ORVs) to a key member of sandy beach assemblages, the surf clam Donax deltoides - Thomas A. Schlacher; Luke M. C. Thompson; Simon J. Walker (Hydrobiologia, 2008)

Physical damage to coastal dunes and ecological impacts caused by vehicle tracks associated with beach camping on sandy shores: a case study from Fraser Island, Australia - Luke M. C. Thompson; Thomas A. Schlacher (Journal of Coastal Conservation, 2008)

Population structure and diversity in sexual and asexual populations of the pathogenic fungus Melampsora lini - LUKE G. BARRETT; PETER H. THRALL; JEREMY J. BURDON; ADRIENNE B. NICOTRA; CELESTE C. LINDE (Molecular Ecology, 2008)
Many pathogens undergo both sexual and asexual reproduction to varying degrees, yet the ecological, genetic and evolutionary consequences of different reproductive strategies remain poorly understood. Here we investigate the population genetic structure of wild populations of the plant pathogen Melampsora lini on its host Linum marginale , using amplified fragment length polymorphism (AFLP) markers, two genes underlying pathogen virulence, and phenotypic variation in virulence. In Australia, M. lini occurs as two genetically and geographically divergent lineages (AA and AB), one of which is completely asexual (AB), and the other able to reproduce both clonally and sexually (AA). To quantify the genetic and evolutionary consequences of these different life histories, we sampled five populations in each of two biogeographical regions. Analysis of AFLP data obtained for 275 isolates revealed largely disjunct geographical distributions for the two different lineages, low genetic diversity within lineages, and strong genetic structure among populations within each region. We also detected significant divergence among populations for both Avr genes and virulence phenotypes, although generally these values were lower than those obtained with AFLP markers. Furthermore, isolates belonging to lineage AA collectively harboured significantly higher genotypic and phenotypic diversity than lineage AB isolates. Together these results illustrate the important roles of reproductive modes and geographical structure in the generation and maintenance of virulence diversity in populations of M. lini .

The Diasporin Pathway: a tumor progression-related transcriptional network that predicts breast cancer survival - Nigel P. S. Crawford; Renard C. Walker; Luanne Lukes; Jennifer S. Officewala; Robert W. Williams; Kent W. Hunter (Clinical & Experimental Metastasis, 2008)

Fine root dynamics in a loblolly pine forest are influenced by free‐air‐CO 2 ‐enrichment: a six‐year‐minirhizotron study - SETH G. PRITCHARD; ALLAN E. STRAND; M. LUKE McCORMACK; MICHEAL A. DAVIS; ADRIEN C. FINZI; ROBERT B. JACKSON; ROSER MATAMALA; HUGO H. ROGERS; RAM OREN (Global Change Biology, 2008)
Efforts to characterize carbon (C) cycling among atmosphere, forest canopy, and soil C pools are hindered by poorly quantified fine root dynamics. We characterized the influence of free‐air‐CO 2 ‐enrichment (ambient +200 ppm) on fine roots for a period of 6 years (Autumn 1998 through Autumn 2004) in an 18‐year‐old loblolly pine ( Pinus taeda ) plantation near Durham, NC, USA using minirhizotrons. Root production and mortality were synchronous processes that peaked most years during spring and early summer. Seasonality of fine root production and mortality was not influenced by atmospheric CO 2 availability. Averaged over all 6 years of the study, CO 2 enrichment increased average fine root standing crop (+23%), annual root length production (+25%), and annual root length mortality (+36%). Larger increase in mortality compared with production with CO 2 enrichment is explained by shorter average fine root lifespans in elevated plots (500 days) compared with controls (574 days). The effects of CO 2 ‐enrichment on fine root proliferation tended to shift from shallow (0–15 cm) to deeper soil depths (15–30) with increasing duration of the study. Diameters of fine roots were initially increased by CO 2 ‐enrichment but this effect diminished over time. Averaged over 6 years, annual fine root NPP was estimated to be 163 g dw m −2 yr −1 in CO 2 ‐enriched plots and 130 g dw m −2 yr −1 in control plots ( P = 0.13) corresponding to an average annual additional input of fine root biomass to soil of 33 g m −2 yr −1 in CO 2 ‐enriched plots. A lack of consistent CO 2 × year effects suggest that the positive effects of CO 2 enrichment on fine root growth persisted 6 years following minirhizotron tube installation (8 years following initiation of the CO 2 fumigation). Although CO 2 ‐enrichment contributed to extra flow of C into soil in this experiment, the magnitude of the effect was small suggesting only modest potential for fine root processes to directly contribute to soil C storage in south‐eastern pine forests.

Bioenergetic models for acetate and phosphate transport in bacteria important in enhanced biological phosphorus removal - Luke C. Burow; Amanda N. Mabbett; Alastair G. McEwan; Philip L. Bond; Linda L. Blackall (Environmental Microbiology, 2008)
Summary Most of our understanding of the physiology of microorganisms is the result of investigations in pure culture. However, in order to understand complex environmental processes, there is a need to investigate mixed microbial communities. This is true for enhanced biological phosphorus removal (EBPR), an environmental process that results in the enrichment of the polyphosphate‐accumulating organism Accumulibacter spp. and the glycogen non‐polyphosphate accumulating organism Defluviicoccus spp. We investigated acetate and inorganic phosphate (P i ) uptake in enrichments of Accumulibacter spp. and acetate uptake in enrichments of Defluviicoccus spp. For both enrichments, anaerobic acetate uptake assays in the presence of the protonophore, carbonyl cyanide m ‐chlorophenylhydrazone (CCCP) or the membrane potential ( Δψ ) uncoupler valinomycin, indicated that acetate is likely to be taken up by a permease‐mediated process driven by the Δψ . Further investigation with the sodium ionophore monensin suggested that anaerobic acetate uptake by Defluviicoccus spp. may in part be dependent on a sodium potential. Results of this study also suggest that Accumulibacter spp. generate a proton motive force (pmf or Δp ) for anaerobic acetate uptake by efflux of protons in symport with P i through an inorganic phosphate transport (Pit) system. In contrast, we suggest that the anaerobic Δp in Defluviicoccus spp. is generated by an efflux of protons across the cell membrane by the fumarate respiratory system, or by extrusion of sodium ions via decarboxylation of methylmalonyl‐CoA. Aerobic P i uptake by the Accumulibacter spp. enrichment was strongly inhibited in the presence of an ATPase inhibitor, suggesting that the phosphate‐specific transport (Pst) system is important even under relatively high concentrations of P i . Acetate permease activity in these microorganisms may play an important role in the competition for acetate in the often acetate‐limited EBPR process. Activity of a high‐velocity Pst system in Accumulibacter spp. may further explain its ability to compete strongly in EBPR.

Financial analysis of shaded cocoa in Ghana - Beatrice Darko Obiri; Geoff A. Bright; Morag A. McDonald; Luke C. N. Anglaaere; Joseph Cobbina (Agroforestry Systems, 2007)

Isopod infestation of postspawning Nassau grouper around Little Cayman Island - B. X. Semmens; K. E. Luke; P. G. Bush; C. M. R. McCoy; B. C. Johnson (Journal of Fish Biology, 2006)
Attacks by the isopod Excorallana tricornis tricornis on Nassau grouper Epinephelus striatus caught in Antillean fish traps around Little Cayman Island, Cayman Islands, are recorded. Divers reported heavily parasitized fish during the study period, suggesting that trapping did not exclusively precipitate parasitism. Parasitic infestations were reported to be common in Nassau grouper immediately following their spawning season in mid‐winter.

Identification and Characterization of a Host Reversibly Glycosylated Peptide that Interacts with the Tomato leaf curl virus V1 Protein - Luke A. Selth; Satish C. Dogra; M. Saif Rasheed; John. W. Randles; M. Ali Rezaian (Plant Molecular Biology, 2006)

Lack of effects of guanfacine on executive and memory functions in healthy male volunteers - Ulrich Müller; Luke Clark; Minh L. Lam; Rebecca M. Moore; C. Louise Murphy; Nicola K. Richmond; Ranbir S. Sandhu; Ingrid A. Wilkins; David K. Menon; Barbara J. Sahakian; Trevor W. Robbins (Psychopharmacology, 2005)

Mercury Policy and Science in Northeastern North America: The Mercury Action Plan of the New England Governors and Eastern Canadian Premiers - C. Mark Smith; Luke J. Trip (Ecotoxicology, 2005)

Solution structure of T4moC, the Rieske ferredoxin component of the toluene 4-monooxygenase complex - Lars Skjeldal; Francis C. Peterson; Jurgen F. Doreleijers; Luke A. Moe; Jeremie D. Pikus; William M. Westler; John L. Markley; Brian F. Volkman; Brian G. Fox (JBIC Journal of Biological Inorganic Chemistry, 2004)

Characterisation of early transcriptional changes involving multiple signalling pathways in the Mla13 barley interaction with powdery mildew ( Blumeria graminis f. sp. hordei ) - Ingo Hein; Edward I. Campbell; Mary Woodhead; Peter E. Hedley; Vanessa Young; Wayne L. Morris; Luke Ramsay; Joerg Stockhaus; Paul R. J. Birch; Gary D. Lyon; Adrian C. Newton (Planta, 2004)

Relative lack of cognitive effects of methylphenidate in elderly male volunteers - Luke Clark; Adam R. Aron; Jonathan Dowson; Barbara J Sahakian; Danielle C. Turner; Trevor W. Robbins (Psychopharmacology, 2003)

Elevation of Transgene Expression Level by Flanking Matrix Attachment Regions (MAR) is Promoter Dependent: A Study of the Interactions of Six Promoters with the RB7 3′ MAR - S. Luke Mankin; George C. Allen; Thomas Phelan; Steven Spiker; William F. Thompson (Transgenic Research, 2003)

Impact and management of purple loosestrife (Lythrum salicaria) in North America - Bernd Blossey; Luke C. Skinner; Janith Taylor (Biodiversity and Conservation, 2001)

Introduction of a plant intron into the luciferase gene ofPhotinus pyralis - S. Luke Mankin; George C. Allen; William F. Thompson (Plant Molecular Biology Reporter, 1997)